Separator for power storage device, power storage device assembly kit, and power storage device
A polyolefin-based separator with inorganic particles and a thermoplastic polymer layer forms crosslinking structures within the battery environment to address thermal runaway issues in lithium-ion batteries, particularly those with high-nickel positive electrodes, improving safety and stability.
Patent Information
- Application Number
- JP2023183554
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Priority Date
- 2020-10-30
- Filing Date
- 2023-10-25
- Publication Date
- 2025-02-05
- Estimated Expiration
- 2041-03-12
AI Technical Summary
Conventional polyolefin-based separators for lithium-ion batteries face challenges in preventing thermal runaway due to local short circuits, particularly in high-nickel NMC-based positive electrodes, which are prone to rapid thermal decomposition and explosion, and lack sufficient heat resistance and stability during high-temperature conditions.
A separator comprising a polyolefin substrate with inorganic particles and a thermoplastic polymer layer, featuring crosslinking structures formed by functional groups that react within the battery environment to enhance mechanical stability and prevent thermal runaway.
The proposed separator significantly reduces the risk of thermal runaway and explosion by maintaining structural integrity under high temperatures, enhancing safety in lithium-ion batteries, especially those with high-nickel positive electrodes.
Smart Images

Figure 0007626913000117 
Figure 0007626913000118 
Figure 0007626913000119
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a polyolefin microporous membrane, and to a separator for an electricity storage device and an electricity storage device each using the same. [Background technology]
[0002] Polyolefin microporous membranes exhibit excellent electrical insulation and ion permeability, and are therefore used as separators for power storage devices, such as battery separators and capacitor separators, etc. In particular, polyolefin microporous membranes are used as separators for lithium ion secondary batteries, which are mounted in a variety of products, including not only small electronic devices such as mobile phones and notebook computers, but also electric vehicles such as electric cars and electric motorcycles.
[0003] In recent years, there has been a demand for power storage devices, particularly in small electronic devices and electric vehicles, with higher output, higher energy density, improved cycle characteristics, etc. Accordingly, the safety standards for power storage devices have become stricter, and there is a demand for safer power storage devices that do not experience thermal runaway even if a local short circuit occurs, for example.
[0004] Patent Document 1 describes a separator for a lithium ion secondary battery, which includes a porous membrane, an inorganic particle layer formed on at least one surface of the porous membrane and in which inorganic particles account for 80 volume % or more of the entire layer, and a porous resin layer formed on the surface of the inorganic particle layer and integrated with the inorganic particle layer, for the purpose of suppressing separation between the separator and the electrodes and improving the heat resistance of the separator.
[0005] Patent Document 2 describes a separator that includes a porous crosslinked polyolefin substrate and an inorganic porous layer laminated on a part or all of the surface thereof, for the purpose of improving shutdown characteristics and meltdown characteristics.
[0006] Patent Document 3 describes a crosslinked polyolefin separator that includes a porous polyolefin substrate having siloxane crosslinks and a polymer binder layer located on at least one surface thereof, for the purpose of reducing thickness, weight, volume, etc. while maintaining mechanical and thermal stability.
[0007] Patent Document 4 describes a separator for an electricity storage device that contains a silane-modified polyolefin, with the aim of achieving both a shutdown function and high-temperature rupture resistance and ensuring the safety, output and / or cycle stability of the electricity storage device, and is characterized in that a silane crosslinking reaction of the silane-modified polyolefin is initiated upon contact with an electrolyte.
[0008] Patent Documents 5 and 6 describe a separator comprising a porous substrate containing a crosslinked silane-modified polyolefin and an inorganic coating layer located on the substrate, with the aim of providing a separator that combines the properties of electrode adhesion, heat resistance, mechanical properties, high battery output, and long life.
[0009] On the other hand, in order to ensure the safety of the battery, it has been proposed to achieve both the activation of the shutdown function and an improvement in the film rupture temperature by forming a crosslinked structure in the separator (Patent Documents 7 to 14). For example, Patent Documents 7 to 12 describe a silane crosslinked structure formed by contacting a silane-modified polyolefin-containing separator with water. Patent Document 13 describes a crosslinked structure formed by ring-opening of norbornene by irradiation with ultraviolet light, electron beams, etc. Patent Document 14 describes that the insulating layer of the separator contains a (meth)acrylic acid copolymer having a crosslinked structure, a styrene-butadiene rubber binder, etc.
[0010] The components used in lithium-ion batteries include positive and negative electrode materials, electrolytes, and separators. Of these components, the separator is required to be inert to electrochemical reactions or surrounding components due to its insulating properties. On the other hand, for the negative electrode material of lithium-ion batteries, a technology has been established since the beginning of their development to suppress the decomposition of the electrolyte on the surface of the negative electrode by forming a solid electrolyte interface (SEI) through a chemical reaction during the first charge (Non-Patent Document 3). Even if polyolefin resin is used for the separator, an oxidation reaction is induced on the positive electrode surface under high voltage, and cases of blackening and surface deterioration of the separator have been reported.
[0011] Based on the above concept, in order to adopt a chemical structure that is inactive to electrochemical reactions or other chemical reactions as a material for separators for electricity storage devices, microporous polyolefin membranes have been widely developed and put to practical use.
[0012] It has also been proposed that, when producing a separator for an electricity storage device, a single microporous membrane or a laminate of multiple microporous membranes is used as a substrate, and a functional layer or membrane such as a thermoplastic resin layer, a heat-resistant resin layer, or a water-soluble resin layer is formed on the surface of the substrate (Patent Documents 16 to 19).
[0013] It has also been proposed that, when producing a separator for an electricity storage device, a single microporous membrane or a laminate of multiple microporous membranes is used as a substrate, and an active layer, such as a polyvinylidene fluoride (PVDF)-based resin-containing layer or a layer containing a PVDF-based resin and an inorganic filler, is formed on the surface of the substrate (Patent Documents 18 and 20).
[0014] In addition, when producing a separator for an electricity storage device, it has been proposed to use a single microporous membrane or a laminate of multiple microporous membranes as a substrate and form a heat-resistant resin layer such as wholly aromatic polyamide (also called aramid) on the surface of the substrate (Patent Document 16), or to laminate a porous membrane containing aramid or the like and a porous membrane containing a water-soluble resin such as cellulose ether on both sides of the substrate, respectively (Patent Document 19).
[0015] However, as long as polyolefin is used as the resin, there is a limit to the performance improvement even if the mechanical microporous structure of the separator is improved. For example, the heat resistance stability of the separator above the melting point of polyolefin, or the affinity or liquid retention with the electrolyte due to the electronegativity of the olefin unit is insufficient, and therefore the permeability of Li ions or their solvated ion clusters through the separator is not satisfactory. [Prior art documents] [Patent documents]
[0016] [Patent Document 1] JP 2020-64879 A [Patent Document 2] Korean Patent No. 10-1943491 [Patent Document 3] Korean Patent Publication No. 2019-0108438 [Patent Document 4] International Publication No. 2020 / 075866 [Patent Document 5] Korean Patent Publication No. 10-2018-0147041 [Patent Document 6] Korean Patent Publication No. 10-2018-0147042 [Patent Document 7] Japanese Patent Application Publication No. 9-216964 [Patent Document 8] WO 97 / 44839 [Patent Document 9] Japanese Patent Application Publication No. 11-144700 [Patent Document 10] Japanese Patent Application Publication No. 11-172036 [Patent Document 11] JP 2001-176484 A [Patent Document 12] JP 2000-319441 A [Patent Document 13] JP 2011-071128 A [Patent Document 14] JP 2014-056843 A [Patent Document 15] Japanese Unexamined Patent Application Publication No. 10-261435 [Patent Document 16] International Publication No. 2008 / 156033 [Patent Document 17] Japanese Patent No. 6580234 [Patent Document 18] Japanese Patent No. 6367453 [Patent Document 19] International Publication No. 2012 / 018132 [Patent Document 20] Korean Patent Publication No. 10-2020-0026172 [Non-Patent Document]
[0017] [Non-Patent Document 1] Pekka Pyykko and Michiko Atsumi, "Molecular Single-Bond Covalent Radii for Elements 1 - 118", Chem. Eur. J., 2009, 15, 186 - 197 [Non-Patent Document 2] Robin Walsh, "Bond dissociation energy values in silicon-containing compounds and some of their implications", Acc. Chem. Res., 1981, 14, 246 - 252 [Non-Patent Document 3] Lithium-Ion Secondary Batteries (2nd Edition), published by Nikkan Kogyo Shimbun [Non-Patent Document 4] Fundamental Polymer Chemistry, published by Tokyo Kagaku Dojin [Non-Patent Document 5] ACS Appl. Mater. Interfaces 2014, 6, 22594 - 22601 [Non-Patent Document 6] Energy Storage Materials 2018, 10, 246 - 267 [Non-Patent Document 7] The Chemistry of Organic Silicon Compounds Vol.2, Wiley (1998), Chap.4 Summary of the Invention [Problem to be solved by the invention]
[0018] An object of the present disclosure is to provide a separator for an electricity storage device that is safer, and an electricity storage device and the like that use the same.
[0019] For example, there is room for improvement in safety when a local short circuit occurs in the separators for an electricity storage device described in Patent Documents 1 to 6. Therefore, in a first embodiment, an object of the present disclosure is to provide a separator for an electricity storage device and an electricity storage device that are safer and have a reduced possibility of thermal runaway due to a local short circuit.
[0020] In recent years, the output and energy density of lithium-ion secondary batteries for use in mobile devices or vehicles have been increasing, while miniaturization of battery cells and stable cycle charge / discharge performance during long-term use are being demanded. For this reason, a separator that is thin (e.g., 15 μm or less) and high quality (e.g., having uniform physical properties and no resin aggregates) is required. Furthermore, the standard of battery safety has become stricter than before, and as described in Patent Documents 7 and 8, a separator having a shutdown function and high-temperature membrane rupture property, and a stable manufacturing method thereof are expected. In this regard, the lower the shutdown temperature level, the more desirable it is, and the higher the membrane rupture temperature level, the more desirable it is.
[0021] However, the crosslinking methods described in Patent Documents 7 to 14 are all performed in-process during separator film formation or in a batch immediately after separator film formation. Therefore, after the formation of the crosslinked structure described in Patent Documents 7 to 14, the separator must be coated and slit, and the internal stress increases in the subsequent lamination and winding process with the electrodes, which may cause the manufactured battery to deform. For example, when a crosslinked structure is formed by heating, the internal stress of the separator having the crosslinked structure may increase at room temperature or room temperature. Furthermore, when a crosslinked structure is formed by light irradiation such as ultraviolet light or electron beams, the light irradiation may become non-uniform, and the crosslinked structure may become non-homogeneous. This is thought to be because the periphery of the crystal part of the resin constituting the separator is easily crosslinked by electron beams.
[0022] Patent Document 15 describes a technique for improving the cycle characteristics of a lithium-ion secondary battery by adding succinimides or the like to an electrolyte solution. However, the technique described in Patent Document 15 does not aim to improve the cycle characteristics by specifying the structure of the separator.
[0023] Furthermore, in the formation of a resin functional layer or resin functional film on a separator substrate as described in Patent Documents 16 to 19, there is room for improvement in terms of safety in a nail penetration test of an electricity storage device including the separator.
[0024] In addition, as shown in Non-Patent Document 5, in recent years, high nickel NMC type positive electrodes have been attracting attention as one of the leading candidates for increasing the capacity of LIB batteries. However, as the ratio of NMC changes from the conventional (1:1:1) to (4:3:3), (6:2:2), (8:1:1), etc., the heat resistance of the positive electrode crystal structure decreases, and O2 is easily released along with thermal decomposition, which continuously leads to ignition or explosion of organic matter in the battery. In particular, the decomposition reaction of the NMC(622) or NMC(811) positive electrode is more prominent in the low temperature region than that of the conventional NMC(111) or NMC(433). In addition, in a similar trend, there is a problem of crystal instability (thermal decomposition) in the constituent positive electrodes such as LAC type positive electrodes other than NMC. Therefore, there is a potential problem of a positive electrode that is prone to thermal decomposition or O2 release in increasing the capacity of LIB batteries.
[0025] On the other hand, Non-Patent Document 6 clarifies a series of time-dependent changes in chemical and physical changes in the heat generation inside the battery caused by partial short circuit after nail penetration during a series of processes in a battery nail penetration test. In particular, the O2 release phenomenon during the decomposition of the positive electrode described in Non-Patent Document 5 tends to be strongly related to the sudden switch from the heat generation mode of the battery to the runaway mode.
[0026] From the above, batteries composed of high nickel content NMC-based positive electrodes, which are expected to have high battery capacity and energy density, have the problem of rapidly igniting and exploding in a short time in nail penetration tests compared to conventional NMC-based batteries, and it is necessary to significantly suppress peripheral short circuits when a nail penetrates. Such batteries are difficult to handle safely in the event of destruction during accidents or disasters in vehicle applications, and improving nail penetration safety by simulating destruction modes is a major challenge.
[0027] Furthermore, conventional coating of PVDF-based resins onto separator substrates as described in Patent Documents 18 and 20 has a problem in suppressing heat shrinkage, and there is room for improvement in heat shrinkability at high temperatures (e.g., 200°C or higher) and hot box test properties.
[0028] Furthermore, as shown in Non-Patent Document 5, in recent years, high nickel NMC type positive electrodes have been attracting attention as one of the leading candidates for increasing the capacity of LIB batteries. However, as the NMC ratio changes from the conventional (1:1:1) to (4:3:3), (6:2:2), (8:1:1), etc., the heat resistance of the positive electrode crystal structure decreases, and O2 is easily released with thermal decomposition, which continuously leads to ignition or explosion of organic matter in the battery. In particular, NMC (622) or NMC (811) positive electrodes, which are expected to have high battery capacity and high energy density, start to decompose at around 150°C to 160°C. In order to safely handle LIBs with such a positive electrode configuration even in the event of an accident or fire in an in-vehicle application, it is an issue to improve the heat resistance stability at 150°C.
[0029] Furthermore, conventional coating of heat-resistant resins and / or water-soluble resins onto separator substrates as described in Patent Documents 16 and 19 leaves room for improvement in terms of bar impact destruction tests at high temperatures (e.g., 150°C or higher) of electricity storage devices equipped with separators.
[0030] Furthermore, as shown in Non-Patent Document 5, in recent years, high nickel NMC type positive electrodes have been attracting attention as one of the leading candidates for increasing the capacity of LIB batteries. However, as the ratio of NMC changes from the conventional (1:1:1) to (4:3:3), (6:2:2), (8:1:1), etc., the heat resistance of the positive electrode crystal structure decreases (for example, crystal decomposition and O2 release at about 250°C), and O2 is easily released along with thermal decomposition, which continuously leads to ignition or explosion of organic matter in the battery. In particular, in the case of high nickel content such as NMC (622) or NMC (811) positive electrodes, decomposition begins at around 150°C to 160°C. Currently, research institutes and companies in various countries are conducting research on stabilizing the crystal structure of high nickel content NMC, and although improvements have been seen through surface treatment of NMC or adjustment of the content of trace impurities, the crystal decomposition and O2 release at 150°C to 160°C have not been fundamentally solved. In addition to NMC, there is also a problem of crystal instability (thermal decomposition) in the constituent cathodes of LAC cathodes and other materials. When high-energy density LIBs using such cathode materials are deployed in automotive applications, ensuring safety in the unlikely event of a vehicle collision is an issue. In other words, it is required that the battery does not explode even in high-temperature conditions such as fires when the battery structure is destroyed by external force. Therefore, research is required to improve battery safety under the most severe conditions such as NMC cathodes, assuming crystal decomposition from 150°C.
[0031] Therefore, in a second embodiment, the present disclosure aims to provide a separator for an electricity storage device that can improve at least one of the safety of the electricity storage device, for example, safety in a nail penetration test, heat shrinkability and hot box test properties, and high-temperature bar impact destruction test properties, as well as an electricity storage device assembly kit, an electricity storage device, and a method for manufacturing an electricity storage device that use the separator. [Means for solving the problem]
[0032] Examples of embodiments of the present disclosure are listed in the following sections. [1] A separator for an electricity storage device comprising at least one each of an A layer containing a polyolefin, a B layer containing inorganic particles, and a C layer containing a thermoplastic polymer, The polyolefin contained in the layer A has one or more functional groups, The separator for an electricity storage device, wherein the functional groups include functional groups that undergo a condensation reaction with each other within the electricity storage device to form a cross-linked structure through a siloxane bond. [2] When TOF-SIMS measurement of a 100 μm square area was performed on the above-mentioned layer A, one or more island structures containing an alkali metal and / or an alkaline earth metal were detected, and the size of the island structure was 9 μm 2 More than 245μm 2 2. The separator for an electricity storage device according to item 1, comprising the following region: [3] 3. The separator for an electricity storage device according to item 2, wherein the separator has two or more island structures containing the alkali metal and / or alkaline earth metal, and both the minimum and maximum values of the distance between the weighted center of gravity positions of the island structures are 6 μm or more and 135 μm or less. [4] 4. The separator for use in an electricity storage device according to item 2 or 3, wherein the island structure contains an alkaline earth metal, and the alkaline earth metal is calcium. [5] 4. The separator for an electricity storage device according to item 2 or 3, wherein the alkali metal and / or alkaline earth metal is at least one selected from the group consisting of lithium, sodium, magnesium, potassium, and strontium. [6] 5. The separator for an electricity storage device according to any one of items 1 to 4, wherein the layer B is an inorganic porous layer containing inorganic particles and a resin binder. [7] 7. The separator for use in an electricity storage device according to item 6, wherein the resin binder has a glass transition temperature (Tg) of -50°C to 90°C. [8] 8. The power storage device separator according to any one of items 1 to 7, wherein the content of inorganic particles in the layer B is 5% by mass to 99% by mass based on the total mass of the layer B. [9] 9. The separator for an electricity storage device according to any one of items 1 to 8, wherein the inorganic particles are at least one selected from the group consisting of alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, iron oxide, silicon nitride, titanium nitride, boron nitride, silicon carbide, aluminum oxide hydroxide, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, diatomaceous earth, silica sand, and glass fiber.
[10] 10. The power storage device separator according to any one of items 1 to 9, wherein the thermoplastic polymer contained in the layer C contains a (meth)acrylic acid ester or (meth)acrylic acid as a polymerization unit.
[11] 11. The separator for an electricity storage device according to any one of items 1 to 10, wherein the ratio of the area of the layer C covering the layer B is 5% to 98%.
[12] 12. The separator for an electricity storage device according to any one of items 1 to 11, wherein the thermoplastic polymer contained in the layer C contains at least one fluorine atom-containing vinyl compound selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE).
[13] 13. The separator for an electricity storage device according to any one of items 1 to 12, wherein, when the thermal response index when the separator for an electricity storage device after immersion in an electrolyte is heated to 150° C. at 2° C. / min is fitted to equation (1) using a least squares approximation method, the range of rate is 3.5≦rate≦150.
number
[14] 14. The separator for an electricity storage device according to any one of items 1 to 13, wherein, when a thermal response index when the separator for an electricity storage device after immersion in an electrolyte is heated to 150° C. at 2° C. / min is fitted to equation (1) using a least squares approximation method, the range of T0 is 110≦T0≦150 and the range of max is 0.1≦max≦30.
[15] A separator for an electricity storage device comprising a polyolefin microporous membrane as a substrate and a surface layer formed on at least one surface of the polyolefin microporous membrane, The polyolefin contained in the polyolefin microporous membrane has one or more functional groups, and A separator for an electricity storage device, characterized in that after being stored in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure.
[16] A separator for an electricity storage device comprising a polyolefin microporous membrane as a substrate and a thermoplastic polymer-containing layer formed on at least one surface of the polyolefin microporous membrane, The polyolefin contained in the polyolefin microporous membrane has one or more functional groups, and Item 16. The separator for an electricity storage device according to item 15, characterized in that after being housed in an electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure.
[17] Item 17. The separator for an electricity storage device according to item 16, wherein the coverage area ratio of the thermoplastic polymer-containing layer to the substrate is 5% to 90%.
[18] Item 16. The separator for an electricity storage device according to item 15, wherein the thermoplastic polymer contained in the thermoplastic polymer-containing layer contains a polymerization unit of a (meth)acrylic acid ester or (meth)acrylic acid.
[19] 19. The separator for an electricity storage device according to any one of items 16 to 18, wherein the thermoplastic polymer contained in the thermoplastic polymer-containing layer has a glass transition temperature of -40°C to 105°C.
[20] A separator for an electricity storage device comprising a polyolefin microporous membrane as a substrate and an active layer disposed on at least one surface of the polyolefin microporous membrane, The polyolefin contained in the polyolefin microporous membrane has one or more functional groups, and Item 16. The separator for an electricity storage device according to item 15, characterized in that after being housed in an electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure. [twenty one] 21. The separator for an electric storage device according to item 20, wherein the active layer contains at least one fluorine atom-containing vinyl compound selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), and inorganic particles. [twenty two] 22. The separator for a power storage device according to item 20 or 21, wherein a mass ratio of the fluorine atom-containing vinyl compound to the inorganic particles in the active layer (fluorine atom-containing vinyl compound / inorganic particles) is 5 / 95 to 80 / 20. [twenty three] The weight average molecular weight of the fluorine atom-containing vinyl compound is 0.6×10 6 ~2.5×10 6 23. The separator for an electricity storage device according to any one of items 20 to 22, [twenty four] A polyolefin microporous membrane as a substrate; a heat-resistant porous layer containing a heat-resistant resin laminated on at least one surface of the polyolefin microporous membrane; A separator for an electricity storage device comprising: The polyolefin contained in the polyolefin microporous membrane has one or more functional groups, and Item 16. The separator for an electricity storage device according to item 15, characterized in that after being housed in an electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure. [twenty five] Item 25. The separator for a power storage device according to item 24, wherein the heat-resistant porous layer contains 30% by mass to 90% by mass of an inorganic filler having an average particle size of 0.2 μm to 0.9 μm.
[26] Item 26. The separator for an electricity storage device according to item 24 or 25, wherein the heat-resistant resin comprises at least one selected from the group consisting of wholly aromatic polyamide, polyimide, polyamideimide, polysulfone, polyketone, polyether, polyetherketone, polyetherimide, and cellulose.
[27] 27. The separator for an electricity storage device according to any one of items 24 to 26, wherein the heat-resistant resin contains a para-type aromatic polyamide and / or a meta-type aromatic polyamide.
[28] 28. The separator for an electricity storage device according to any one of items 16 to 27, wherein the chemical substance is any one of an electrolyte, an electrolytic solution, an electrode active material, an additive, or a decomposition product thereof contained in the polyolefin microporous membrane.
[29] 29. The power storage device separator according to any one of items 16 to 28, wherein the crosslinked structure is an amorphous part crosslinked structure in which an amorphous part of the polyolefin is crosslinked.
[30] Item 29. The power storage device separator according to item 28, wherein the amorphous portion is selectively crosslinked.
[31] 31. The separator for an electricity storage device according to any one of items 16 to 30, wherein the polyolefin is a functional group-modified polyolefin or a polyolefin copolymerized with a monomer having a functional group.
[32] 32. The separator for an electricity storage device according to any one of items 16 to 31, wherein the crosslinked structure is formed by a reaction via any one of a covalent bond, a hydrogen bond, or a coordinate bond.
[33] The reaction via the covalent bond is represented by the following reactions (I) to (IV): (I) Condensation reactions of multiple identical functional groups; (II) Reactions between multiple heterogeneous functional groups; (III) chain condensation reaction of functional groups with the electrolyte; and (IV) reaction of functional groups with additives; Item 33. The separator for an electricity storage device according to item 32, wherein the separator is at least one selected from the group consisting of:
[34] The reaction via the coordinate bond is represented by the following reaction (V): (V) A reaction in which multiple identical functional groups crosslink through coordinate bonds with metal ions; Item 34. The separator for an electricity storage device according to Item 33,
[35] Item 34. The separator for an electrical storage device according to item 33, wherein the reaction (I) and / or (II) is catalytically promoted by a chemical substance inside the electrical storage device.
[36] Item 34. The separator for use in an electricity storage device according to item 33, wherein the reaction (I) is a condensation reaction of a plurality of silanol groups.
[37] Item 34. The separator for an electricity storage device according to Item 33, wherein the reaction (IV) is a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction between a compound Rx constituting the electricity storage device separator and a compound Ry constituting the additive, wherein the compound Rx has a functional group x, and the compound Ry has a linking reaction unit y1.
[38] The reaction (IV) is a nucleophilic substitution reaction, The functional group x of the compound Rx is at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH; The linking reaction unit y1 of the compound Ry is CH3SO2-, CF3SO2-, ArSO2-, CH3SO3-, CF3SO3-, ArSO3-, and the following formulae (y1-1) to (y1-6): [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} Item 38. The separator for an electricity storage device according to item 37, wherein the molar ratio is at least two selected from the group consisting of monovalent groups represented by the following formula:
[39] The reaction (IV) is a nucleophilic substitution reaction, The compound Ry has a chain unit y2 in addition to the linking reaction unit y1; and The chain unit y2 is represented by the following formulae (y2-1) to (y2-6): [ka] {In the formula, m is an integer of 0 to 20, and n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} Item 39. The separator for an electricity storage device according to item 37 or 38, wherein the R 1 -R 2 -R 3 -R 4 -R 5 -R 6 -R 7 -R 8 -R 9 -R 10 -R 11 -R 12 -R 13 -
[40] The reaction (IV) is a nucleophilic addition reaction, The functional group x of the compound Rx is at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH; The linking reaction unit y1 of the compound Ry is represented by the following formulae (Ay1-1) to (Ay1-6): [ka] [ka] [ka] [ka] {In the formula, R is a hydrogen atom or a monovalent organic group.} [ka] [ka] Item 38. The separator for an electricity storage device according to item 37, wherein the at least one group is selected from the group consisting of groups represented by the following formula:
[41] The reaction (IV) is a ring-opening reaction, The functional group x of the compound Rx is at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH; The linking reaction unit y1 of the compound Ry is represented by the following formula (ROy1-1): [ka] In the formula, each of the multiple Xs is independently a hydrogen atom or a monovalent substituent. Item 38. The separator for an electricity storage device according to Item 37, wherein the at least two groups are represented by the following formula:
[42] In the above reaction (V), the metal ion is Zn 2+ , Mn 2+ , Co 3+ , Ni 2+ and Li + Item 35. The separator for an electricity storage device according to item 34, wherein the separator is at least one selected from the group consisting of:
[43] 43. The power storage device separator according to any one of items 1 to 42, wherein the polyolefin having the functional group is not a masterbatch resin containing a dehydration condensation catalyst that forms a crosslinked structure of the functional group.
[44] (A) an exterior body housing a laminate or a wound body of an electrode and the separator for an electricity storage device according to any one of items 1 to 43; and (B) a container containing a nonaqueous electrolyte; An electricity storage device assembly kit comprising:
[45] 44. An electricity storage device comprising: a positive electrode; a negative electrode; the separator for an electricity storage device according to any one of items 1 to 43; and a non-aqueous electrolyte solution.
[46] 44. An electricity storage device comprising a positive electrode, a negative electrode, the separator for an electricity storage device according to any one of items 1 to 43, and a non-aqueous electrolyte, wherein the positive electrode is at least one selected from the group consisting of a nickel-manganese-cobalt (NMC)-based lithium-containing positive electrode, an olivine-type lithium iron phosphate (LFP)-based positive electrode, a lithium cobalt oxide (LCO)-based positive electrode, a nickel-cobalt aluminum (NCA)-based lithium-containing positive electrode, and a lithium manganese oxide (LMO)-based positive electrode. Effect of the Invention
[0033] According to the present disclosure, it is possible to provide a separator for an electricity storage device with higher safety, and an electricity storage device using the same.
[0034] In a first embodiment, the present disclosure can provide a separator for an electricity storage device that is safer and has a reduced possibility of thermal runaway due to a local short circuit, and an electricity storage device using the same.
[0035] In a second embodiment, the present disclosure can provide a separator for an electricity storage device that can improve at least one of the safety of the electricity storage device, for example, safety in a nail penetration test, heat shrinkability and hot box test properties, and high-temperature bar impact destruction test properties, and an electricity storage device using the same. [Brief description of the drawings]
[0036] [Figure 1] Fig. 1(A) is a schematic diagram showing the behavior of an electricity storage device separator having a non-crosslinked polyolefin substrate layer and an inorganic particle layer when it is heat-shrunk with both ends open, and Fig. 1(B) is a schematic diagram showing the behavior of an electricity storage device separator having a non-crosslinked polyolefin substrate layer and an inorganic particle layer when it is heat-shrunk with both ends fixed. [Diagram 2] FIG. 2 is a schematic diagram showing the behavior of an electricity storage device separator having a non-crosslinked polyolefin substrate layer and an inorganic particle layer when it is thermally shrunk with both ends open. [Diagram 3] Fig. 3(A) is a schematic diagram showing the behavior of an electricity storage device separator having a crosslinked polyolefin substrate layer and an inorganic particle layer when it is heat-shrunk with both ends open, and Fig. 3(B) is a schematic diagram showing the behavior of an electricity storage device separator having a crosslinked polyolefin substrate layer and an inorganic particle layer when it is heat-shrunk with both ends fixed. [Figure 4] FIG. 4 is a schematic diagram showing the behavior when a local short circuit occurs in an electricity storage device including an electricity storage device separator having a crosslinked polyolefin substrate layer, an inorganic particle layer, and a thermoplastic polymer layer. [Diagram 5] FIG. 5 is a schematic diagram showing the behavior when a local short circuit occurs in an electricity storage device including an electricity storage device separator having a non-crosslinked polyolefin substrate layer, an inorganic particle layer, and a thermoplastic polymer layer. [Figure 6] FIG. 6 is a schematic diagram showing the behavior when a local short circuit occurs in an electricity storage device including an electricity storage device separator having a non-crosslinked polyolefin substrate layer and a thermoplastic polymer layer. [Figure 7] FIG. 7 is a schematic diagram showing the behavior when a local short circuit occurs in an electricity storage device including an electricity storage device separator having a crosslinked polyolefin substrate layer and an inorganic particle layer. [Figure 8] FIG. 8 is a schematic diagram showing the behavior when a local short circuit occurs in an electricity storage device including an electricity storage device separator having a non-crosslinked polyolefin substrate layer and an inorganic particle layer. [Figure 9] FIG. 9 is a schematic diagram of an island structure containing an alkali metal and / or an alkaline earth metal in a TOF-SIMS measurement. [Figure 10] FIG. 10 is a schematic diagram for explaining a crystalline polymer having a higher-order structure divided into lamellae (crystalline portions), amorphous portions, and intermediate layers between them. [Figure 11] FIG. 11 is a schematic diagram for explaining the crystal growth of polyolefin molecules. [Figure 12] FIG. 12 is a schematic diagram of a high-temperature bar impact fracture test (shock test). DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0037] <Separator for power storage device> A separator for an electricity storage device (hereinafter, also simply referred to as "separator") is required to have insulating properties and lithium ion permeability, and is therefore generally formed from an insulating material having a porous structure, such as paper, a polyolefin nonwoven fabric, or a resin microporous film. In particular, for lithium ion batteries, a polyolefin microporous film is an excellent separator substrate because it is resistant to oxidation-reduction deterioration of the separator and can form a dense and uniform porous structure.
[0038] In a first embodiment, the separator for an electricity storage device includes at least one each of an A layer containing a polyolefin, a B layer containing inorganic particles, and a C layer containing a thermoplastic polymer. The polyolefin contained in the A layer has one or more types of functional groups. The functional groups include functional groups that undergo a condensation reaction with each other within the electricity storage device to form a crosslinked structure by siloxane bonds.
[0039] In a second embodiment, a separator for an electricity storage device comprises a polyolefin microporous membrane as a substrate and a surface layer formed on at least one side thereof, and the polyolefin contained in the polyolefin microporous membrane has one or more types of functional groups. After the separator is housed in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure.
[0040] In the second embodiment, the separator for an electricity storage device preferably comprises a polyolefin microporous membrane as a substrate and a thermoplastic polymer-containing layer formed on at least one side thereof. The polyolefin contained in the polyolefin microporous membrane has one or more types of functional groups, and after the separator is housed in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure.
[0041] In the second embodiment, the separator for the electric storage device preferably comprises a polyolefin microporous film as a substrate and an active layer disposed on at least one side thereof. The polyolefin contained in the polyolefin microporous film has one or more functional groups, and after the separator is housed in the electric storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electric storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure. By combining a chemically crosslinkable separator substrate capable of forming a crosslinked structure by any one of the reactions (1) to (3) after the separator is housed in the electric storage device with an active layer such as a PVDF-based resin-containing layer or a layer containing a PVDF-based resin and inorganic particles, in addition to the crosslinking gelation of the substrate, the adhesion of the electrode material and the active layer in the electric storage device can synergistically improve the heat shrinkability at high temperatures (e.g., 200°C or higher) and hot box testability.
[0042] In the second embodiment, the separator for the power storage device preferably comprises a polyolefin microporous film as a substrate and a heat-resistant porous layer containing a heat-resistant resin laminated on at least one side of the polyolefin microporous film. The polyolefin contained in the polyolefin microporous film has one or more functional groups, and after the separator is housed in the power storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the power storage device, or (3) the functional groups react with other types of functional groups to form a crosslinked structure. Up until now, many studies have focused on the mechanical strength of separator films in impact tests that simulate the destruction of a battery structure due to external forces: bar impact tests, and it has been found that separators with high tensile strength can suppress short circuits without breaking even when subjected to external forces. However, at high temperatures such as 150°C, the polyethylene (PE) microporous film melts and cannot suppress short circuits. On the other hand, even if a heat-resistant resin such as aramid resin is composited with a microporous membrane, only the aramid resin remains in a thin film, and the thin film structure of the aramid resin may be destroyed by gas generation due to electrode decomposition or other chemical reactions inside the battery, leading to a short circuit between the electrodes. By combining a chemically crosslinked separator substrate that can form a crosslinked structure by any of the above reactions (1) to (3) after being stored in an electricity storage device with a heat-resistant porous layer containing a heat-resistant resin, the bar impact destruction testability at high temperatures (for example, 150°C or higher) can be synergistically improved by the crosslinked gelation of the substrate and the heat resistance of the porous layer laminated on the substrate. By providing a crosslinked structure in the crystalline PE microporous membrane, the fluidity is low, and the substrate cannot be compatible with or mixed with the molten or softened state of the aramid resin, so that contact between the electrodes can be suppressed. Such a low fluidity resin layer at high temperatures can suppress short circuits, ignition, and explosions even in the unlikely event of decomposition and generation of O2 from the positive electrode. In addition, heat-resistant resins such as aramid resin contain many polar functional groups and show high affinity with electrolyte. It was experimentally demonstrated that by applying heat-resistant resin to a substrate with a cross-linked structure in an electricity storage device, electrolyte can be uniformly supplied from the heat-resistant resin layer to the substrate after incorporation and injection into the electricity storage device, and the substrate can form a uniform cross-linked structure.
[0043] The separator for an electricity storage device has a total thickness of preferably 2 μm or more, more preferably 4 μm or more, from the viewpoint of ensuring insulation. The separator for an electricity storage device has a total thickness of preferably 40 μm or less, more preferably 20 μm or less, from the viewpoint of increasing ion permeability and the energy density of the electricity storage device.
[0044] I. Separator for power storage device according to the first embodiment
[0045] <Polyolefin Base Layer> In the present specification, the A layer containing polyolefin is also simply referred to as a "polyolefin substrate layer". The polyolefin substrate layer is preferably a single-layer structure. The single structure is a layer composed of a single material, and as long as it is composed of a single material, it may include a coarse structure layer with a large pore size and a dense structure layer with a small pore size.
[0046] The polyolefin substrate layer is typically a microporous film containing polyolefin as a main component, and is preferably a polyolefin microporous film. "Containing as a main component" means that the target component is contained in an amount of 50% by mass or more based on the total mass. The polyolefin contained in the polyolefin substrate layer may be, for example, 50% by mass or more, 60% by mass or more, 70% by mass or more, 80% by mass or more, 90% by mass or more, 99% by mass or more, or 100% by mass based on the total mass of the resin components constituting the microporous film.
[0047] The polyolefin is not particularly limited, but may be a polyolefin containing an olefin having 3 to 10 carbon atoms as a monomer unit. Examples of such polyolefins include homopolymers of ethylene or propylene, and copolymers formed from at least two olefin monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene, and are preferably polyethylene, polypropylene, or a combination thereof.
[0048] Among polyethylenes, low density polyethylene (LDPE), medium density polyethylene (MDPE), high density polyethylene (HDPE), and ultra-high molecular weight polyethylene (UHMWPE) can be mentioned, and high density polyethylene (HDPE) and ultra-high molecular weight polyethylene (UHMWPE) are preferred from the viewpoint that heat setting (sometimes abbreviated as "HS") can be performed at higher temperatures without blocking micropores. Generally, low density polyethylene (LDPE) is a polyethylene having a density of 0.925 g / cm 3 Medium density polyethylene (MDPE) has a density of 0.925 g / cm 3 More than 0.942g / cm 3 High density polyethylene (HDPE) has a density of 0.942 g / cm 3 More than 0.970g / cm 3 Ultra-high molecular weight polyethylene (UHMWPE) has a density of less than 0.970 g / cm 3 The above refers to polyethylene with a weight average molecular weight (Mw) of 1,000,000 or more. The density of polyethylene can be measured according to "D) Density gradient tube method" described in JIS K7112 (1999).
[0049] Examples of polypropylene include isotactic polypropylene, syndiotactic polypropylene, atactic polypropylene, etc. Examples of copolymers of ethylene and propylene include ethylene-propylene random copolymers, ethylene-propylene rubber, etc.
[0050] The polyolefin contained in the polyolefin substrate layer includes a polyolefin having one or more types of functional groups that undergo a condensation reaction with each other within the energy storage device to form a cross-linked structure via siloxane bonds (hereinafter also referred to as "cross-linkable functional groups" in this specification).
[0051] The crosslinkable functional group is preferably grafted to the main chain of the polyolefin. The crosslinkable functional group is a crosslinkable silane group, for example, a trialkoxysilyl group (-Si(OR)3) and / or a dialkoxysilyl group (-Si(OR)2), in which R is, for example, methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, tert-butyl, or a combination thereof, preferably methyl, ethyl, n-propyl, or a combination thereof. The crosslinkable silane group is more preferably a methoxysilyl group and an ethoxysilyl group, more preferably a trimethoxysilyl group (-Si(OMe)3). The alkoxysilyl group is converted to a silanol group through a hydrolysis reaction with water, and a condensation reaction occurs, so that a siloxane bond can be formed in the battery. The following formula shows an example of a crosslinking reaction when R is methyl. The ratio of the change from the T0 structure to the T1 structure, the T2 structure, or the T3 structure is arbitrary.
[0052] [ka]
[0053] In the silane-modified polyolefin (hereinafter also referred to as "resin a"), the main chain and the graft are connected by a covalent bond. The structure forming the covalent bond is not particularly limited, but examples thereof include alkyl, ether, glycol, and ester.
[0054] From the viewpoint of uniform arrangement of Si-containing molecular structures and the life of the equilibrium state of the Li-ion coordination intermediate, it is preferable that resin a contains 0.03 to 1.0 mol% of silanol units, that is, the silanol unit modification rate is 0.03 to 1.0 mol%, before the crosslinking reaction of resin a. The silanol unit modification rate is more preferably 0.05 to 0.35 mol%, further preferably 0.07 to 0.32 mol%, particularly preferably 0.08 to 0.30 mol%, and most preferably 0.12 to 0.28 mol%. The inventors of the present application have found that resin a tends to have a molecular structure that is easy to construct a crosslinking reaction when the silanol unit modification amount is as above, focusing on the fact that the silane-modified units are mainly present in the non-crystalline part of the separator, more preferably only in the non-crystalline part, the distance between the silane-modified units, and the thermal vibration motion at -10°C to 80°C, and the like. The above T0, T1, T2 and T3 structures can all form coordination intermediates with Li ions. However, it is believed that Li ions coordinate between Si atoms in the non-crystalline portion, and that decoordination and recoordination proceed randomly. Therefore, by adjusting the amount of modified silanol units in resin a to within the above range, a more significant effect can be obtained.
[0055] From the viewpoint of uniform arrangement of Si-containing molecular structures and the life of the equilibrium state of the Li-ion coordination intermediate, it is preferable that the resin a is modified with 0.01 to 2.0 mol % of propylene (C3) units, 0.01 to 2.0 mol % of butene (C4) units, or 0.01 to 2.0 mol % in total of C3 units and C4 units. In this case, the number of carbon atoms is determined by taking into account both the R group and the linking group in the above formula.
[0056] From the same viewpoint, the C3 unit modification rate of resin a is more preferably 0.01 to 1.2 mol%, further preferably 0.01 to 0.75 mol%, particularly preferably 0.02 to 0.60 mol%, and most preferably 0.05 to 0.30 mol%.
[0057] From the viewpoint of uniform arrangement of Si-containing molecular structures and the life of the equilibrium state of the Li-ion coordination intermediate, the C4 unit modification rate of resin a is more preferably 0.01 to 1.0 mol%, further preferably 0.30 to 0.70 mol%, and particularly preferably 0.48 to 0.65 mol% before the crosslinking reaction of resin a. On the other hand, in the heat setting (HS) step in the formation of the separator film, the C4 unit modification rate of resin a is preferably 0.43 mol% or less, more preferably 0.40 mol% or less, and further preferably 0.1 mol% or less.
[0058] From the viewpoint of uniform arrangement of Si-containing molecular structures and the lifespan of the equilibrium state of the Li ion coordination intermediate, the total modification rate of the C3 units and the C4 units of resin a is more preferably 1.5 mol % or less, even more preferably 1.0 mol % or less, particularly preferably 0.6 mol % or less, and most preferably 0.3 mol % or less.
[0059] From the viewpoint of cycle characteristics and safety of the electricity storage device, the number average molecular weight (Mn) of resin a is preferably 10,000 to 20,000, more preferably 16,000 or less, and even more preferably 15,000 or less. From the same viewpoint, the weight average molecular weight (Mw) of resin a is preferably 45,000 to 200,000, more preferably 140,000 or less, even more preferably 129,000 or less, particularly preferably 100,000 or less, and most preferably 72,000 or less. From the same viewpoint, the Mw / Mn of resin a is preferably 3.0 to 12, more preferably 4.0 to 9.0, and even more preferably 4.1 to 8.0.
[0060] The resin a is not limited, but its viscosity average molecular weight (Mv) may be, for example, 20,000 to 150,000, and its density may be, for example, 0.90 to 0.97 g / cm 3 The melt mass flow rate (MFR) at 190° C. may be, for example, 0.1 to 15 g / min.
[0061] The polyethylene constituting the silane-grafted modified polyethylene may be composed of one type of ethylene alone, or may be composed of two or more types of ethylene. Two or more types of silane-grafted modified polyethylene composed of different ethylenes may be used in combination.
[0062] The crosslinking reaction may occur spontaneously in the environment within the energy storage device, or may be triggered by an external stimulus. Examples of external stimuli include heat and light, such as ultraviolet light. The crosslinking reaction is preferably promoted as a catalytic reaction under acidic or alkaline conditions, or in the presence of a base with low nucleophilicity. The siloxane bond formed by condensation has high thermodynamic stability. The bond energy of C-C is 86 kcal mol -1 , the bond energy of C-Si is 74 kcal mol -1 whereas the Si-O bond energy is 128 kcal mol -1 This suggests the thermodynamic stability of the siloxane bond (Non-Patent Documents 1, 2). Therefore, for example, the presence of a certain concentration of hydrogen fluoride (HF) or H2SO4 in the reaction system can promote the crosslinking reaction of the silane-modified polyolefin in the polymer structure of the separator with the siloxane bond at a high yield, thereby building a highly heat-resistant structure in the separator.
[0063] In addition, silicon-containing compounds are highly reactive with F anions, so the cross-linking points formed by siloxane bonds may be decomposed by high concentrations of F anions. The bond energy of Si-F is 160 kcal / mol -1Since the thermal stability of the Si-F bond is very high, it is considered that in the equilibrium reaction, F anions continue to be consumed until the concentration in the system falls to a certain level (Non-Patent Documents 1, 2). The decomposition reaction of the crosslinking point by F anions is presumed to be a cleavage reaction of the C-Si bond or Si-OSi bond of the siloxane bond. In an experiment to estimate the bond dissociation energy of Si-X using the compound Me3Si-X, it has been reported in the past that the bond dissociation energy D of Si-X is D=394±8 kJ / mol when X=Me, D=513±11 kJ / mol when X=OMe, and D=638±5 kJ / mol when X=F (Non-Patent Document 7). In addition, under acidic conditions, considering the stability of the product after the cleavage of the C-Si bond or Si-OSi bond of the siloxane bond, it is presumed that the Si-OSi bond is easily cleaved to become Si-F and HO-Si. Therefore, when the F anion concentration in the reaction system exceeds a certain level, the siloxane bonds at the crosslinking points are broken down, which may result in a decrease in the heat resistance of the separator.
[0064] In this disclosure, it has been found that the concentration of HF can be controlled by utilizing the fact that PF5 and HF exist in equilibrium due to the Jahn-Teller effect of PF6, which promotes the crosslinking reaction of siloxane bonds and enables the control of the crosslinking reaction in the battery of a separator with high heat resistance. In addition, since PF5 and HF exist in equilibrium, the crosslinking reaction of siloxane bonds can be caused long-term and continuously, and the probability of the crosslinking reaction can be significantly improved. The amorphous structure of polyethylene is a highly entangled structure, and even if only a part of the crosslinked structure is formed, its entropy elasticity increases significantly. Therefore, the molecular mobility of the amorphous part decreases, making it difficult to form siloxane bonds for all silanol units. In this disclosure, the addition under multiple conditions was considered, and the problem was fundamentally solved.
[0065] By including a polyolefin substrate layer having a crosslinkable functional group as described above together with a layer B containing inorganic particles and a layer C containing a thermoplastic polymer, as described below, it is possible to provide a separator for an electricity storage device having a higher safety by reducing the possibility of thermal runaway due to a local short circuit, as described below. The reason for this is not limited to theory or the aspects of the drawings, but will be described below with reference to the drawings.
[0066] FIG. 1(A) is a schematic diagram showing the behavior of an electricity storage device separator (10) having a non-crosslinked polyolefin substrate layer (1a) and an inorganic particle layer (2) when it is heat-shrunk with both ends open. With both ends open, the substrate layer that has shrunk due to the stress (4) caused by heat shrinkage lifts the inorganic particle layer, causing buckling failure (5) of the inorganic particle layer, and the substrate layer pulled by the protruding inorganic particle layer causes tensile failure (6). FIG. 2 illustrates this behavior in stages. When an electricity storage device separator having a non-crosslinked polyolefin substrate layer (1a) and an inorganic particle layer (2) is heat-shrunk with both ends open, the substrate layer has areas where the vectors of the stress (4) caused by heat shrinkage are concentrated and areas where they are sparse, causing the electricity storage device separator to deform into a corrugated shape. At this time, buckling failure (cracks) occurs at the apexes of the corrugated inorganic particle layer (5), and the substrate layer is pulled by the inorganic particle layer (6). As the deformation progresses further, multiple cracks protrude, causing the base layer to undergo tensile fracture (6) and creating voids. Returning to FIG. 1, FIG. 1(B) is a schematic diagram showing the behavior of an electricity storage device separator (10) having a non-crosslinked polyolefin base layer (1a) and an inorganic particle layer (2) when it is thermally shrunk with both ends fixed. The state in which both ends are fixed mimics the state in which the electricity storage device separator is stored in an electricity storage device. With both ends fixed, the polyolefin base layer breaks between the fixing jigs (20) due to stress (4) caused by thermal shrinkage, and the gaps widen as the thermal shrinkage progresses. As a result, the inorganic particle layer deforms so as to fall into the gaps in the polyolefin base layer.
[0067] FIG. 3(A) is a schematic diagram showing the behavior of a separator (10) for an electric storage device having a crosslinked polyolefin substrate layer (1b) and an inorganic particle layer (2) when both ends are opened and the separator is thermally shrunk. In the case of a crosslinked polyolefin substrate layer, when both ends are opened, the stress (4) caused by thermal shrinkage causes buckling failure (5) of the inorganic particle layer and tensile failure (6) of the substrate layer, as in FIG. 1(A) and FIG. 2. However, when both ends are fixed as shown in FIG. 3(B), the crosslinked polyolefin substrate layer (1b) tends to be stretched between the fixing jigs (20) without breaking. The high safety of the separator for an electric storage device is realized by combining the inorganic particle layer and the thermoplastic polymer layer described later, on the premise of the difference in behavior during thermal shrinkage between the non-crosslinked polyolefin substrate layer and the crosslinked polyolefin substrate layer when both ends are fixed.
[0068] More specifically, FIG. 4 is a schematic diagram showing the behavior when a local short circuit (7) occurs in an electricity storage device (100) including an electricity storage device separator (10) having a crosslinked polyolefin substrate layer (1b), an inorganic particle layer (2), and a thermoplastic polymer layer (3). In the case of a lithium ion secondary battery, a local short circuit may be caused by lithium dendrites that grow from the negative electrode active material layer by repeating charge / discharge cycles at low temperatures. As shown in FIG. 4, when pressure (8) is applied to an electricity storage device after a low-temperature charge / discharge cycle, a local short circuit (7) is likely to occur. When a local short circuit occurs, the short circuited portion generates heat, and the surrounding crosslinked polyolefin substrate layer tries to thermally shrink. However, as explained in FIG. 3, the crosslinked polyolefin substrate layer is unlikely to break, and the inorganic particle layer is fixed to the positive electrode by the thermoplastic polymer layer, so that the inorganic particle layer is unlikely to deform. Therefore, the stress (4) due to thermal shrinkage is concentrated at the interface between the polyolefin substrate layer and the inorganic particle layer, and the local short circuit is broken, and as a result, thermal runaway is prevented.
[0069] Fig. 5 is a schematic diagram showing behavior when a local short circuit (7) occurs in an electricity storage device (100) subjected to low-temperature charge / discharge cycles and pressure in the same manner as in Fig. 4, except that a non-crosslinked polyolefin substrate layer (1a) is used. Since the polyolefin substrate layer is non-crosslinked, the non-crosslinked polyolefin substrate layer breaks and a void is formed around the local short circuit, as described in Figs. 1 and 2. Therefore, the stress (4) due to thermal contraction does not concentrate at the interface between the polyolefin substrate layer and the inorganic particle layer, and the local short circuit is difficult to break.
[0070] Fig. 6 is a schematic diagram showing behavior when a local short circuit (7) occurs in an electricity storage device (100) similar to Fig. 5 except that it does not have an inorganic particle layer, by subjecting it to low-temperature charge / discharge cycles and pressure. As in Fig. 5, the non-crosslinked polyolefin substrate layer breaks, and a void is formed around the local short circuit. In addition, as the non-crosslinked polyolefin substrate layer deforms, the thermoplastic polymer layer (3) is pulled toward the periphery, and the void becomes larger. Therefore, stress (4) due to thermal contraction does not concentrate, and the local short circuit is less likely to break.
[0071] Fig. 7 is a schematic diagram showing behavior when a local short circuit (7) occurs in an electricity storage device (100) by subjecting it to a low-temperature charge / discharge cycle and pressure in the same manner as in Fig. 4 except that it does not have a thermoplastic polymer layer. Since it does not have a thermoplastic polymer layer, the inorganic particle layer is easily deformed, and compared to the case of Fig. 4, part of the stress due to thermal contraction is absorbed by the deformation of the inorganic particle layer. Therefore, the stress due to thermal contraction is less likely to concentrate at the interface between the polyolefin substrate layer and the inorganic particle layer, and the local short circuit is less likely to break.
[0072] 8 is a schematic diagram showing behavior when a local short circuit (7) occurs in an electricity storage device (100) subjected to low-temperature charge / discharge cycles and pressure in the same manner as in FIG. 7, except that a non-crosslinked polyolefin substrate layer (1a) is used. Since there is no thermoplastic polymer layer, the inorganic particle layer is easily deformed, and part of the stress (4) due to thermal contraction is absorbed by the deformation of the inorganic particle layer, and further, the non-crosslinked polyolefin substrate layer breaks, forming a void around the local short circuit. Therefore, the stress (4) due to thermal contraction does not concentrate at the interface between the polyolefin substrate layer and the inorganic particle layer, and the local short circuit is difficult to break.
[0073] In order to obtain resistance to oxidation-reduction degradation and a dense and uniform porous structure, the polyolefin substrate layer preferably contains both a silane-modified polyolefin and a polyolefin other than the silane-modified polyolefin (hereinafter also referred to as "silane-unmodified polyolefin"). The silane-unmodified polyolefin to be combined with the silane-modified polyolefin (hereinafter abbreviated as "resin a") is preferably a polyolefin having a viscosity average molecular weight (Mv) of 2,000,000 or more (hereinafter abbreviated as "resin b"), a polyolefin having an Mv of less than 2,000,000 (hereinafter abbreviated as "resin c"), or a combination thereof. By combining the resin a with two types of silane-unmodified polyolefins having molecular weights in a specific range, it is possible to obtain an electricity storage device that is more likely to break a local short circuit due to stress concentration and is safer. The resin b is more preferably a polyethylene having a viscosity average molecular weight (Mv) of 2,000,000 or more, and the resin c is more preferably a polyethylene having an Mv of less than 2,000,000.
[0074] From the viewpoint of cycle characteristics and safety of the electricity storage device, the number average molecular weight (Mn) of resin b is preferably 200,000 to 1,400,000, more preferably 210,000 to 1,200,000, and even more preferably 250,000 to 1,000,000. From the same viewpoint, the weight average molecular weight (Mw) of resin b is preferably 1,760,000 to 8,800,000, more preferably 1,900,000 to 7,100,000, and even more preferably 2,000,000 to 6,200,000. From the same viewpoint, Mw / Mn of resin b is preferably 3.0 to 12, more preferably 4.0 to 9.0, and even more preferably 6.0 to 8.8. From the same viewpoint, Mv of resin b is preferably 2,000,000 to 10,000,000, more preferably 2,100,000 to 8,500,000, even more preferably 3,000,000 to 7,800,000, and still more preferably 3,300,000 to 6,500,000.
[0075] From the viewpoint of cycle characteristics and safety of the electricity storage device, the number average molecular weight (Mn) of the resin c is preferably 20,000 to 250,000, more preferably 30,000 to 200,000, even more preferably 32,000 to 150,000, and even more preferably 40,000 to 110,000. From the same viewpoint, the weight average molecular weight (Mw) of the resin c is preferably 230,000 to 2,000,000, more preferably 280,000 to 1,600,000, even more preferably 320,000 to 1,200,000, and even more preferably 400,000 to 1,000,000. From the same viewpoint, the Mw / Mn of the resin c is preferably 3.0 to 12, more preferably 4.0 to 9.0, and even more preferably 6.0 to 8.8. From the same viewpoint, the Mv of resin c is preferably 250,000 to 2,500,000, more preferably 300,000 to 1,600,000, even more preferably 320,000 to 1,100,000, and still more preferably 450,000 to 800,000.
[0076] From the viewpoint of safety of the electricity storage device, the content of resin a in the polyolefin substrate layer is preferably 3% by mass to 70% by mass, more preferably 5% by mass to 60% by mass, and even more preferably 10% by mass to 50% by mass, based on the total mass of the solid content of the polyolefin raw material. From the viewpoint of high ion permeability and high safety, the total content of silane unmodified polyolefin in the polyolefin substrate layer is preferably 40% by mass to 95% by mass, more preferably 50% by mass to 90% by mass, and even more preferably 60% by mass to 80% by mass, based on the total mass of the solid content of the polyolefin raw material.
[0077] From a similar viewpoint, the content of resin b in the polyolefin raw material is preferably 3 mass% to 70 mass%, more preferably 5 mass% to 60 mass%, and even more preferably 5 mass% to 40 mass%, based on the total mass of the solid content of the polyolefin raw material.
[0078] From a similar viewpoint, the content of resin c in the polyolefin raw material is preferably 1 mass% to 90 mass%, more preferably 5 mass% to 60 mass%, and even more preferably 5 mass% to 50 mass%, based on the total mass of the solid content of the polyolefin raw material.
[0079] From the same viewpoint, the mass ratio of resin a to resin b in the polyolefin raw material (mass of resin a / mass of resin b) is preferably 0.07 to 12.00, more preferably 0.10 to 11.00, and further preferably 0.50 to 10.00.
[0080] From the same viewpoint, the mass ratio of resin a to resin c in the polyolefin raw material (mass of resin a / mass of resin c) is preferably 0.07 to 12.00, more preferably 0.10 to 11.00, and further preferably 0.20 to 10.00.
[0081] From the same viewpoint, the mass ratio of resin b to resin c in the polyolefin raw material (mass of resin b / mass of resin c) is preferably 0.06 to 7.00, more preferably 0.10 to 7.00, and further preferably 0.12 to 6.90.
[0082] The thickness of the polyolefin substrate layer is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 3.0 μm or more. When the thickness of the polyolefin substrate layer is 1.0 μm or more, the membrane strength tends to be further improved. The thickness of the polyolefin substrate layer is preferably 100 μm or less, more preferably 50 μm or less, and even more preferably 30 μm or less. When the thickness of the polyolefin substrate layer is 100 μm or less, the ion permeability tends to be further improved.
[0083] The 150°C heat shrinkage rate of the polyolefin base layer is preferably 10% or more, more preferably 15% or more, and even more preferably 20% or more. When the 150°C heat shrinkage rate is 10% or more, the stress applied during heat shrinkage becomes large, making it easier to break local short circuits and more effectively preventing thermal runaway.
[0084] <Inorganic particle layer> The electricity storage device separator further includes a layer B containing inorganic particles (hereinafter also referred to as "inorganic particle layer" in this specification).
[0085] The inorganic particles are preferably at least one selected from the group consisting of alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, iron oxide, silicon nitride, titanium nitride, boron nitride, silicon carbide, aluminum oxide hydroxide, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, diatomaceous earth, silica sand, and glass fiber. Examples of alumina include alumina such as α-alumina, β-alumina, and γ-alumina, and alumina hydrate such as boehmite. α-alumina or boehmite is preferable because of its high stability against the electrolyte used in lithium ion batteries.
[0086] The content of inorganic particles contained in the inorganic particle layer is preferably 5% by mass to 99% by mass, more preferably 10% by mass to 99% by mass, even more preferably 50% by mass to 98% by mass, and even more preferably 90% by mass to 97% by mass, based on the total mass of the inorganic particle layer. When the content of inorganic particles is 5% by mass or more, the elastic modulus of the separator can be increased, and a separator with higher heat resistance can be obtained. When the content of inorganic particles is 99% by mass or less, powder falling from the separator can be prevented.
[0087] The inorganic particle layer is preferably an inorganic porous layer further containing a resin binder in addition to inorganic particles. As the resin binder, a resin material such as a styrene-butadiene resin, an acrylic acid ester resin, a methacrylic acid ester resin, or a fluororesin such as polyvinylidene fluoride can be used. The content of the resin binder contained in the inorganic particle layer is preferably 1% by mass to 50% by mass, more preferably 3% by mass to 10% by mass, based on the total mass of the inorganic particle layer. When the resin binder is 1% by mass or more, powder falling from the separator can be prevented. When the content of the inorganic particles is 50% by mass or less, the elastic modulus of the separator can be increased, and a separator with higher heat resistance can be obtained.
[0088] The glass transition temperature (Tg) of the resin binder is preferably −50° C. to 90° C., and more preferably −30° C. to −10° C. When the glass transition temperature (Tg) of the resin binder is −50° C. or higher, the adhesiveness tends to be excellent, and when it is 90° C. or lower, the ion permeability tends to be excellent.
[0089] The thickness of the inorganic particle layer is preferably 0.5 μm or more, more preferably 1.0 μm or more, and even more preferably 2.0 μm or more. By making the thickness of the inorganic particle layer 0.5 μm or more, a separator with higher heat resistance can be obtained. The thickness of the inorganic particle layer is preferably 20 μm or less, more preferably 10 μm or less, and even more preferably 6 μm or less. By making the thickness of the inorganic particle layer 20 μm or less, ion permeability tends to be further improved.
[0090] The elastic modulus of the inorganic particle layer is preferably 0.05 GPa or more, more preferably 0.1 GPa or more. When the elastic modulus of the inorganic particle layer is 0.05 GPa or more, stress concentration is likely to occur at the interface between the inorganic particle layer and the polyolefin substrate layer when a local short circuit occurs, and thermal runaway can be more effectively prevented. The elastic modulus of the inorganic particle layer is preferably 10 GPa or less, more preferably 5 GPa or less, and even more preferably 2 GPa or less. When the elastic modulus of the inorganic particle layer is 10 GPa or less, the handleability of the separator is improved.
[0091] <Thermoplastic polymer layer> The separator for an electricity storage device further includes a layer C (hereinafter also referred to as a "thermoplastic polymer layer" in the present specification) containing a thermoplastic polymer. The thermoplastic polymer layer is preferably laminated on the surface of the inorganic particle layer that is not in contact with the polyolefin substrate layer.
[0092] Examples of thermoplastic polymers include polyolefin resins such as polyethylene, polypropylene, and α-polyolefin; fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene, or copolymers containing these; diene-based polymers containing conjugated dienes such as butadiene and isoprene as monomer units, or copolymers containing these, or hydrogenated versions of these; acrylic polymers containing (meth)acrylate, (meth)acrylic acid, or the like as monomer units and not having a polyalkylene glycol unit, and copolymers containing (meth)acrylate, (meth)acrylic acid, or the like as monomer units. and one or two polyalkylene glycol units, or copolymers containing these, or hydrogenated products thereof; rubbers such as ethylene propylene rubber, polyvinyl alcohol, polyvinyl acetate, etc.; polyalkylene glycols having no polymerizable functional group, such as polyethylene glycol, polypropylene glycol, etc.; resins such as polyphenylene ether, polyphenylene sulfide, polyester, etc.; copolymers having an ethylenically unsaturated monomer with 3 or more repeating alkylene glycol units as a copolymerization unit; and combinations thereof. From the viewpoint of improving the safety of the electricity storage device, the thermoplastic polymer is preferably an acrylic polymer, and more preferably a polymer containing a polymerization unit of a (meth)acrylic acid ester or (meth)acrylic acid as a polymerization unit.
[0093] From the viewpoint of improving the safety of the electricity storage device, it is also preferable that the thermoplastic polymer contains at least one fluorine atom-containing vinyl compound selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE).
[0094] The glass transition temperature (Tg) of the thermoplastic polymer is preferably −50° C. to 150° C. When the glass transition temperature (Tg) of the thermoplastic polymer is −50° C. or higher, the adhesiveness tends to be excellent, and when it is 150° C. or lower, the ion permeability tends to be excellent.
[0095] The area ratio of the thermoplastic polymer layer covering the surface of the inorganic particle layer is preferably 5% or more, more preferably 20% or more, and even more preferably 50% or more. When the area ratio of the thermoplastic polymer layer is 5% or more, the adhesion to the electrode can be improved. The area ratio of the thermoplastic polymer layer covering the surface of the inorganic particle layer is preferably 98% or less. This can suppress pore closure in the polyolefin substrate layer and maintain high air permeability.
[0096] The peel strength (180° peel strength) when the thermoplastic polymer layer is peeled from the inorganic particle layer at an angle of 180° is preferably 0.01 N / m or more, more preferably 0.5 N / m or more. When the 180° peel strength of the thermoplastic polymer layer is 0.01 N / m or more, it is possible to obtain a separator for an electricity storage device that has excellent adhesive strength, thus suppressing deformation of the inorganic particle layer and having excellent safety. From the viewpoint of handling, the 180° peel strength of the thermoplastic polymer layer is preferably 30 N / m or less, more preferably 10 N / m or less.
[0097] The thickness of the thermoplastic polymer layer is preferably 0.1 μm or more, more preferably 0.5 μm or more. When the thickness of the thermoplastic polymer layer is 0.1 μm or more, the adhesive strength is excellent, and therefore deformation of the inorganic particle layer is suppressed, and a separator for an electricity storage device with excellent safety can be obtained. The thickness of the thermoplastic polymer layer is preferably 3 μm or less, more preferably 1 μm or less, from the viewpoint of increasing ion permeability.
[0098] <Island structure> When TOF-SIMS measurement is performed on a 100 μm square area of the A layer, it is preferable that at least one island structure containing an alkali metal and / or an alkaline earth metal is detected. 2 ~245μm 2 , more preferably 10 μm 2 ~230μm 2 , more preferably 11 μm 2 ~214μm 2It is more preferable that, when TOF-SIMS measurement is performed on a 100 μm square area of the separator for an electricity storage device, two or more island structures containing calcium are detected. In this case, the distance between the center points of gravity of the island structures is preferably 6 μm to 135 μm, more preferably 8 μm to 130 μm, and even more preferably 10 μm to 125 μm. FIG. 9 is a schematic diagram of an island structure containing an alkali metal and / or an alkaline earth metal in TOF-SIMS measurement. As shown in FIG. 10, the island structures (9) and the distance (d) between the island structures can be measured in a 100 μm square area. Methods for controlling the size of the island structures and the distance between the center points of gravity include adjusting the rotation speed of the extruder, the molecular weight of the polyolefin resin raw material, etc.
[0099] When manufacturing an electric storage device using an electrolyte solution containing LiFSO3, due to variations in the amount of moisture brought in by each component, the alkali metal and / or alkaline earth metal can be unevenly distributed in an island structure aggregated in the polyolefin substrate layer, thereby trapping HF as a salt with the alkali metal and / or alkaline earth metal. The alkali metal and / or alkaline earth metal is gradually consumed from the surface of the island structure, so the trapping effect can be maintained for a long period of time. This is preferable because it can suppress battery deterioration for a long period of time. If excess HF is present after crosslinking, the siloxane crosslinked separator may catalyze an open bond reaction, which is the reverse reaction of the crosslinking reaction. Therefore, it is speculated that by continuously trapping HF with unevenly distributed alkali metal and / or alkaline earth metal, the open bond reaction can be suppressed and the long-term stability of the crosslinked structure of the silane crosslinked separator can be improved.
[0100] Examples of the alkali metal include lithium, sodium, and potassium, and examples of the alkaline earth metal include magnesium, calcium, and strontium. The island structure preferably includes an alkaline earth metal, and the alkaline earth metal is preferably calcium. By distributing calcium unevenly in the polyolefin substrate layer in the form of an island structure, calcium consumes HF in the system as CaF2, and the HF concentration can be controlled more efficiently. Since calcium is gradually consumed from the surface of the island structure, it is presumed that the trapping effect can be maintained for a long period of time without being completely consumed in a short period of time. This is preferable because it can suppress battery deterioration for a long period of time. If excess HF is present after crosslinking, a siloxane-crosslinked separator may catalyze an open bond reaction, which is a reverse reaction of the crosslinking reaction. Therefore, it is presumed that by continuously trapping HF with unevenly distributed calcium, the open bond reaction can be suppressed and the long-term stability of the crosslinked structure of the silane-crosslinked separator can be improved. When the electrolyte contains LiPF6, it is also possible that an excess amount of F anions is generated due to variations in the amount of water. It was experimentally demonstrated that the creation of an island structure containing calcium within the polyolefin substrate layer traps F anions, thereby ensuring the stability of the siloxane bonds and allowing the cross-linked structure of the separator to be maintained for a long period of time.
[0101] <Characteristics of separators for power storage devices> The porosity of the separator for an electricity storage device is preferably 20% or more, more preferably 30% or more, and even more preferably 40% or more. When the porosity of the separator is 20% or more, the ability to follow the rapid movement of ions tends to be improved. On the other hand, the porosity of the separator is preferably 80% or less, more preferably 70% or less, and even more preferably 60% or less. When the porosity of the separator is 80% or less, the membrane strength tends to be improved and self-discharge tends to be suppressed.
[0102] The air permeability of the separator for power storage devices is 3The separator has an air permeability of preferably 50 seconds or more, more preferably 60 seconds or more, and even more preferably 70 seconds or more, per 100 cm of membrane volume. When the separator has an air permeability of 50 seconds or more, the balance between the membrane thickness, the porosity, and the average pore size tends to be improved. The air permeability of the separator is determined by the air permeability per 100 cm of membrane volume. 3 The air permeability of the separator is preferably 400 seconds or less, more preferably 300 seconds or less, even more preferably 250 seconds or less, and still more preferably 200 seconds or less. When the air permeability of the separator is 400 seconds or less, the ion permeability tends to be further improved.
[0103] The separator for an electricity storage device has a thickness of preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 3.0 μm or more. When the separator has a thickness of 1.0 μm or more, the membrane strength tends to be further improved. The separator has a thickness of preferably 100 μm or less, more preferably 60 μm or less, and even more preferably 50 μm or less. When the separator has a thickness of 100 μm or less, the ion permeability tends to be further improved.
[0104] The 150°C heat shrinkage of the separator for the power storage device and the 150°C heat shrinkage in the electrolyte are preferably 50% or less, more preferably 30% or less, and even more preferably 10% or less. By making the separator's 150°C heat shrinkage and the 150°C heat shrinkage in the electrolyte 50% or less, the battery safety during local short circuit can be further improved. The 150°C heat shrinkage of the separator for the power storage device and the 150°C heat shrinkage in the electrolyte are preferably 0.1% or more, more preferably 0.2% or more, and even more preferably 0.3% or less. By making the separator's 150°C heat shrinkage and the 150°C heat shrinkage in the electrolyte 0.1% or more, the balance between porosity and puncture strength tends to be further improved.
[0105] When a battery generates abnormal heat due to an internal short circuit or other reasons, the separator may become deformed due to the high temperature. In this specification, this phenomenon is called "thermal response", and the area change rate of the separator due to the thermal response is called "thermal response index". It has been reported that the deformation of crystalline polymers due to heat is caused by the non-orientation of the amorphous part and the lamellar structure of the fiber structure of the crystalline part, and the thermal response index of the separator can be considered to be related to the number of molecular chains in the polymer resin constituting the polyolefin base layer that exceed the activation energy for the crystalline and amorphous parts to cause the above-mentioned changes. Meanwhile, the molecular motion of polymers is determined by the flexibility of the main chain (intramolecular interaction) and the intermolecular interaction. In particular, in the case of polymer solids, the latter plays an important role, and when the temperature of the polymer is raised, the intermolecular interaction weakens, and the micro-Brownian motion and macro-Brownian motion become active, causing changes in the crystalline and amorphous parts. Therefore, it can be considered that the activation energy for the transition of the polymer chains in the crystalline part to a lamellar structure and the non-orientation of the polymer chains in the amorphous part depends on the intermolecular interaction. In addition, the intermolecular interaction depends on the molecular weight of the polymer. The molecular weight distribution of a polymer varies depending on the manufacturing method, but is often approximated by a distribution function such as Zimm type distribution or Wesslau type distribution (log normal distribution). Therefore, the distribution of the above-mentioned activation energy for each molecular chain in the polymer can be considered to follow these distribution functions. If the thermal response index of the separator is considered to be the cumulative number of molecular chains that exceed the above-mentioned activation energy, it is expected that the thermal response can be approximated by a cumulative distribution function, for example, a sigmoid function. In fact, the inventors used the least squares method to calculate the relationship between the thermal response index and temperature when heating a separator for an electricity storage device to 150°C at 2°C / min, and expressed it as follows:
number
[0106] In the above formula (1), the value of T0 is preferably 110≦T0≦150, more preferably 115≦T0≦140, and even more preferably 120≦T0≦135. The value of T0 is related to the temperature at which a thermal response occurs. When the range of T0 is within the above range, the separator is prevented from thermally responding in the normal temperature range of the battery, and the lithium dendrite can be folded accurately when a local short circuit occurs, thereby stopping the local short circuit. In the above formula (1), the range of max is preferably 0.1≦max≦30, more preferably 0.2≦max≦20, and even more preferably 0.5≦max≦10. The value of max is related to the convergence value of the thermal response index. When the range of max is within the above range, the occurrence of an internal short circuit due to the thermal response of the separator during a local short circuit can be prevented.
[0107] In view of the above, as a method for controlling the values of rate, T0, and max in the above formula (1), a method for adjusting the molecular weight distribution of the polyolefin substrate and a method for controlling the mechanical strength of the inorganic coating layer having the effect of suppressing thermal deformation are considered. For example, it is preferable to use a total of three types of polyolefin raw materials, namely, polyolefin (raw material b) with Mv=2 million to 9 million, polyolefin (raw material c) with Mv=500,000 to 2 million, and silane-modified polyolefin (raw material a) with Mv=20,000 to 150,000 as a silane-modified polyolefin raw material. More preferably, the content ratio is adjusted according to each molecular weight. More preferably, the common logarithm of the ratio between the basis weight converted pin puncture strength of the polyolefin substrate layer and the basis weight of the inorganic coating layer, calculated by the following formula (2), is used to easily keep the values of rate, T0, and max within the above range. In the above raw material composition, the ratio of raw material a to the total mass of the polyolefin substrate layer is preferably 3% by mass to 70% by mass, and the ratio of raw materials b and c contained therein (mass of resin b / mass of resin c) is preferably 0.06 to 7.00. The common logarithm is preferably 0.1 to 3.
number
[0108] II. Separator for power storage device according to the second embodiment
[0109] <Polyolefin Base Layer> It is believed that the functional groups contained in the polyolefin that constitutes the separator substrate are not incorporated into the crystalline portion of the polyolefin, but are crosslinked in the amorphous portion. Therefore, after being housed in an electricity storage device, the separator of the second embodiment forms a crosslinked structure by utilizing chemicals in the surrounding environment or inside the electricity storage device, thereby suppressing an increase in internal stress or deformation of the produced electricity storage device, and improving at least one of safety during nail penetration testing, heat shrinkage properties, hot box test properties, and high-temperature bar impact destruction test properties.
[0110] (1) The condensation reaction between functional groups of a polyolefin can be, for example, a reaction via a covalent bond between two or more functional groups A contained in the polyolefin. (3) The reaction between a functional group of a polyolefin and another type of functional group can be, for example, a reaction via a covalent bond between a functional group A and a functional group B contained in the polyolefin.
[0111] In addition, in the reaction between the functional group of the polyolefin and the chemical substance inside the electric storage device (2), for example, the functional group A contained in the polyolefin can form a covalent bond or a coordinate bond with any of the electrolyte, electrolytic solution, electrode active material, additives, or decomposition products thereof contained in the electric storage device, or with any of the electrolyte, electrolytic solution, electrode active material, additives, or decomposition products thereof contained in the polyolefin microporous membrane as the substrate. The timing of the incorporation of the electrolyte, electrolytic solution, electrode active material, additives, or decomposition products thereof into the polyolefin microporous membrane does not matter, and may be before, during, or after the separator is housed in the electric storage device. In addition, according to the reaction (2), a crosslinked structure is formed not only inside the separator, but also between the separator and the electrode or between the separator and the solid electrolyte interface (SEI), thereby improving the strength between the multiple members of the electric storage device.
[0112] The crosslinked structure formed by any one of the reactions (1) to (3) is preferably an amorphous crosslinked structure in which the amorphous part of the polyolefin is crosslinked. Since the functional group contained in the polyolefin constituting the separator substrate is not incorporated into the crystalline part of the polyolefin but is considered to be crosslinked in the amorphous part, it is possible to suppress the increase in internal stress or the deformation of the produced electricity storage device while simultaneously achieving a shutdown function and high-temperature membrane rupture resistance, as compared with a conventional crosslinked separator in which the crystalline part and its periphery are easily crosslinked, and thus it is possible to ensure at least one of the safety during nail penetration test of the electricity storage device, heat shrinkage and hot box testability, and high-temperature bar impact fracture testability. From the same viewpoint, the amorphous part of the polyolefin is more preferably selectively crosslinked, and more preferably is significantly crosslinked than the crystalline part. The gelation degree of the polyolefin microporous membrane having an amorphous part crosslinked structure such as a silane crosslinked structure is preferably 30% or more, more preferably 70% or more.
[0113] Although the above crosslinking reaction mechanism and crosslinked structure are not clear, the present inventors consider it as follows.
[0114] (1) Crystal structure in microporous high-density polyethylene membrane As shown in Figure 10, polyolefin resins such as high density polyethylene are generally crystalline polymers, and have a higher-order structure divided into lamellae (crystalline parts) of the crystal structure, amorphous parts, and intermediate layers between them. In the crystalline parts and the intermediate layers between the crystalline and amorphous parts, the mobility of the polymer chains is low and they cannot be separated, but relaxation phenomena can be observed in the 0 to 120°C range in solid viscoelasticity measurements. On the other hand, the mobility of the polymer chains in the amorphous parts is very high, and they are observed in the -150 to -100°C range in solid viscoelasticity measurements. This is closely related to the relaxation of radicals, radical migration reactions, crosslinking reactions, etc., which will be described later.
[0115] Furthermore, the polyolefin molecules that make up the crystals are not single; as shown in Figure 11, multiple polymer chains form small lamellae, which then aggregate to form crystals. This phenomenon is difficult to observe directly. In recent years, academic research has progressed through simulations and the phenomenon has become clearer. Note that here, a crystal is the smallest crystal unit that can be measured by X-ray structural analysis, and is the unit that can be calculated as the crystallite size. In this way, even in the crystalline portion (inside the lamella), it is predicted that there are some parts that are not constrained within the crystal and have a somewhat high degree of mobility.
[0116] (2) Crosslinking reaction mechanism by electron beam Next, the reaction mechanism of electron beam crosslinking (hereafter abbreviated to EB crosslinking) to polymers is as follows: (i) irradiation of an electron beam of tens to hundreds of kGy, (ii) penetration of the electron beam into the reaction target (polymer) and generation of secondary electrons, (iii) hydrogen abstraction reaction in the polymer chain by the secondary electrons and generation of radicals, (iv) adjacent hydrogen abstraction by radicals and movement of active sites, (v) crosslinking reaction or polyene formation by recombination of radicals. Here, the radicals generated in the crystal part have poor motion, so they exist for a long time, and impurities cannot enter the crystal, so the probability of reaction and quenching is low. Such radical species are called stable radicals, and remain for a long period of several months, and their lifespan was clarified by ESR measurement. As a result, it is considered that crosslinking reactions in the crystal are poor. However, in the unconstrained molecular chains that exist in small amounts inside the crystal or in the surrounding crystal-amorphous intermediate layer, the generated radicals have a somewhat long lifespan. Such radical species are called persistent radicals, and in a mobile environment, it is believed that cross-linking reactions between molecular chains will proceed with a high probability. On the other hand, since the mobility of the non-crystalline portion is very high, the generated radical species have a short life span, and it is believed that not only cross-linking reactions between molecular chains but also polyene reactions within a single molecular chain will proceed with a high probability. As described above, in a microscopic view at the crystal level, it can be assumed that the crosslinking reaction due to EB crosslinking is localized inside the crystal or its periphery.
[0117] (3) Crosslinking reaction mechanism by chemical reaction It is preferable to react a functional group in the polyolefin resin with a chemical substance contained in the electricity storage device or the polyolefin microporous membrane, or to use a chemical substance contained in the electricity storage device or the polyolefin microporous membrane as a catalyst. As mentioned above, polyolefin resins have crystalline and amorphous parts. However, the functional groups mentioned above are not present inside the crystals due to steric hindrance, but are localized in the amorphous parts. This is generally known, and although units such as methyl groups contained in small amounts in the polyethylene chain may be incorporated into the crystals, grafts that are bulkier than ethyl groups are not incorporated (Non-Patent Document 2). For this reason, crosslinking points resulting from reactions other than electron beam crosslinking are localized only in the amorphous parts.
[0118] (4) Relationship between differences in cross-linking structure and effects In the crosslinking reaction caused by a chemical reaction inside a battery, the morphology of the reaction product is different. In the research leading up to the present disclosure, the phenomenon was elucidated by the following experiments in order to clarify the crosslinking structure and the changes in the physical properties of the microporous membrane that accompany the structural change. First, the mechanical properties of the membrane were investigated by tensile rupture tests. In addition to the tensile rupture tests, the crystal structure changes were analyzed by in-situ X-ray structural analysis using synchrotron radiation. The results showed that, compared to membranes that had not been EB crosslinked or chemically crosslinked (before), the EB crosslinked membrane suppressed the subdivision of the crystal parts as the strain increased. This is because the inside or periphery of the crystal parts was selectively crosslinked. Accordingly, the Young's modulus and rupture strength improved significantly, and high mechanical strength was achieved. On the other hand, the chemically crosslinked membrane showed no difference in the subdivision of the crystals before and after the crosslinking reaction, suggesting that the non-crystalline parts were selectively crosslinked. Furthermore, there was no change in mechanical strength before and after the crosslinking reaction. Next, the behavior of both films during crystal melting was examined by fuse / meltdown characteristic tests. As a result, the fuse temperature of the EB crosslinked film was significantly higher, with the meltdown temperature rising to 200°C or higher. On the other hand, the fuse temperature of the chemically crosslinked film remained unchanged before and after crosslinking, and it was confirmed that the meltdown temperature rose to 200°C or higher. From this, it is considered that the fuse characteristics caused by crystal melting in the EB crosslinked film were caused by crosslinking around the crystal parts, which resulted in an increase in melting temperature and a decrease in melting speed. On the other hand, it was concluded that the chemically crosslinked film did not affect the fuse characteristics because it did not have a crosslinked structure in the crystal parts. In addition, in the high temperature range of around 200°C, both films have a crosslinked structure after crystal melting, so the entire resin can be stabilized in a gel state, resulting in good meltdown characteristics.
[0119] The above findings are summarized in the table below. [Table 1]
[0120] The components of the separator according to the second embodiment will be described below.
[0121] The polyolefin microporous membrane as the substrate described above can be a monolayer membrane consisting of a single polyolefin-containing microporous layer, a multilayer membrane consisting of a plurality of polyolefin-containing microporous layers, or a multilayer membrane consisting of a polyolefin resin layer and a layer containing another resin as a main component.
[0122] In the case of a bilayer membrane formed from two polyolefin-containing microporous layers, the polyolefin composition of the two layers can be different, and in the case of a multilayer membrane formed from three or more polyolefin-containing microporous layers, the polyolefin composition of the outermost and innermost layers can be different, for example, a three-layer membrane.
[0123] The multilayer film as the substrate preferably has a two or more layer laminate structure having at least one A layer containing polyolefin and one B layer containing polyolefin, and more preferably has a three or more layer laminate structure having one B layer on each side (both sides) of the A layer. The laminate structure is not limited to a two-layer structure of "A layer-B layer" or a three-layer structure of "B layer-A layer-B layer" as long as it has one each of the A layer and B layer. For example, the polyolefin microporous film may have one or more additional layers formed on either or both B layers or between the A layer and the B layer.
[0124] The layers A and B contain polyolefin, and are preferably made of polyolefin. The form of the polyolefin in the layers A and B may be a microporous polyolefin body, for example, a woven fabric of polyolefin-based fibers, a nonwoven fabric of polyolefin-based fibers, or the like.
[0125] <Polyolefin> The polyolefin is not particularly limited, and examples thereof include homopolymers of ethylene or propylene, and copolymers formed from at least two monomers selected from the group consisting of ethylene, propylene, 1-butene, 4-methyl-1-pentene, 1-hexene, 1-octene, and norbornene. Among these, high density polyethylene, low density polyethylene, and ultra-high molecular weight polyethylene (UHMWPE) are preferred, and high density polyethylene or UHMWPE is more preferred, from the viewpoint that the pores are not blocked and heat setting (sometimes abbreviated as "HS") can be performed at a higher temperature. In general, it is known that the weight average molecular weight of UHMWPE is 1,000,000 or more. The polyolefin may be used alone or in combination of two or more kinds.
[0126] In addition, the polyolefin microporous membrane preferably contains a polyolefin with a weight average molecular weight (Mw) of less than 2,000,000, and more preferably contains 40% by mass or more, more preferably 80% by mass or more, of the polyolefin with Mw of less than 2,000,000 relative to the total polyolefin. By using a polyolefin with Mw of less than 2,000,000, the polymer shrinkage is relaxed early in the heating test of the electric storage device, and safety tends to be easily maintained, especially in the heating safety test. In addition, when using a polyolefin with Mw of less than 2,000,000, the elastic modulus in the thickness direction of the obtained microporous membrane tends to be smaller than when using a polyolefin with Mw of 1,000,000 or more, and therefore a microporous membrane that is relatively easy to transfer the unevenness of the core is obtained. The weight average molecular weight of the entire polyolefin microporous film constituting the separator is preferably 100,000 or more and 2,000,000 or less, and more preferably 150,000 or more and 1,500,000 or less.
[0127] <Polyolefin having one or more functional groups> From the viewpoints of forming a crosslinked structure, resistance to oxidation-reduction degradation, and dense and uniform porous structure, the polyolefin microporous membrane preferably contains a functional group-modified polyolefin or a polyolefin copolymerized with a monomer having a functional group as a polyolefin having one or more functional groups. In this specification, functional group-modified polyolefin refers to a polyolefin to which a functional group is bonded after production. The functional group is bonded to the polyolefin skeleton or can be introduced into a comonomer, and is preferably involved in selective crosslinking of the amorphous part of the polyolefin, and can be at least one selected from the group consisting of a carboxyl group, a hydroxyl group, a carbonyl group, a polymerizable unsaturated hydrocarbon group, an isocyanate group, an epoxy group, an alkoxysilyl group, a hydrazide group, a carbodiimide group, an oxazoline group, an acetoacetyl group, an aziridine group, an ester group, an active ester group, a carbonate group, an azide group, a linear or cyclic heteroatom-containing hydrocarbon group, an amino group, a sulfhydryl group, a metal chelate group, and a halogen-containing group.
[0128] From the viewpoints of the separator's strength, ion permeability, resistance to oxidation-reduction deterioration, and dense and uniform porous structure, it is preferable that the separator contains both polyolefin having one or more functional groups and UHMWPE. When polyolefin having one or more functional groups and UHMWPE are used in combination, the mass ratio of polyolefin having one or more functional groups to UHMWPE in the separator (mass of polyolefin having one or more functional groups / mass of ultra-high molecular weight polyethylene) is preferably 0.05 / 0.95 to 0.80 / 0.20.
[0129] <Crosslinked structure> The crosslinked structure of the polyolefin contained in the polyolefin microporous membrane contributes to at least one of the safety in a nail penetration test, the heat shrinkage property, the hot box test property, and the high temperature bar impact fracture test property of an electricity storage device, and is preferably formed in the amorphous part of the polyolefin. The crosslinked structure can be formed, for example, by a reaction via any one of a covalent bond, a hydrogen bond, or a coordinate bond. Among them, the reaction via a covalent bond is the following reactions (I) to (IV): (I) Condensation reaction of multiple identical functional groups (II) Reactions between multiple different functional groups (III) Chain condensation reaction of functional groups with electrolytes (IV) Chain condensation reaction of functional groups with additives It is preferable that the at least one selected from the group consisting of: The reaction via a coordinate bond is shown in the following reaction (V): (V) A reaction in which multiple identical functional groups crosslink through coordinate bonds with eluted metal ions It is preferable that:
[0130] Reaction (I) A schematic scheme and specific examples of reaction (I) are shown below, where the first functional group of the separator is A. [ka] {In the formula, R is an alkyl group or heteroalkyl group having 1 to 20 carbon atoms which may have a substituent.}
[0131] When the functional group A for the reaction (I) is a silanol group, the polyolefin is preferably silane-graft modified. The silane-graft modified polyolefin has a structure in which the main chain is a polyolefin and the main chain has an alkoxysilyl as a graft. Examples of the alkoxide substituted with the alkoxysilyl include methoxide, ethoxide, and butoxide. For example, in the above formula, R can be methyl, ethyl, n-propyl, isopropyl, n-butyl, sec-butyl, isobutyl, and tert-butyl. The main chain and the graft are connected by a covalent bond, and examples of the structure include alkyl, ether, glycol, and ester. Considering the manufacturing process of the separator, the silane-graft modified polyolefin preferably has a silicon to carbon ratio (Si / C) of 0.2 to 1.8%, more preferably 0.5 to 1.7%, before the crosslinking treatment step.
[0132] The preferred silane-grafted polyolefin has a density of 0.90 to 0.96 g / cm 3 and the melt flow rate (MFR) at 190°C is 0.2 to 5 g / min. From the viewpoint of suppressing the generation of resin aggregates in the separator manufacturing process and maintaining silane crosslinking until contact with the electrolyte, it is preferable that the silane-grafted modified polyolefin is not a masterbatch resin containing a dehydration condensation catalyst. It is known that the dehydration condensation catalyst also functions as a catalyst for the siloxane bond formation reaction of an alkoxysilyl group-containing resin. In this specification, a compound obtained by adding a dehydration condensation catalyst (e.g., an organometallic catalyst) to an alkoxysilyl group-containing resin or other kneaded resin in advance during a continuous process of resin kneading using an extruder and compounding the resulting material is called a masterbatch resin.
[0133] Reaction (II) A schematic scheme and a specific example of reaction (II) in which the first functional group of the separator is A and the second functional group is B are shown below. [ka] [ka] [ka] [ka]
[0134] Reactions (I) and (II) can be catalyzed, for example, catalytically promoted, by chemicals within the electrical storage device in which the separator is incorporated. The chemicals can be, for example, any of the electrolytes, electrolytic solutions, electrode active materials, additives, or decomposition products thereof contained in the electrical storage device.
[0135] Reaction (III) A schematic scheme and a specific example of reaction (III) are shown below, where the first functional group of the separator is A and the electrolyte is Sol. [ka] [ka] [ka] [ka]
[0136] Reaction (IV) A schematic scheme of reaction (IV) is shown below, where the first functional group of the separator is A, the second functional group that is optionally incorporated is B, and the additive is Add. [ka]
[0137] From the viewpoint of forming a covalent bond represented by a dotted line in the above scheme, the reaction (IV) is preferably a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction between a compound Rx constituting the separator and a compound Ry constituting the additive (Add). The compound Rx may be a polyolefin, such as polyethylene or polypropylene, contained in the separator, and preferably the polyolefin is modified with a functional group x, such as at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH, and -SH.
[0138] Since the multiple compounds Rx are crosslinked via the compound Ry as an additive, it is preferred that the compound Ry has two or more linking reaction units y1. The multiple linking reaction units y1 may be any structure or group, may be substituted or unsubstituted, may contain heteroatoms or inorganic substances, and may be the same or different from each other, as long as they can undergo a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction with the functional group x of the compound Rx. In addition, when the compound Ry has a chain structure, the multiple linking reaction units y1 can each independently be a terminal group, be incorporated into the main chain, or be a side chain or pendant.
[0139] When reaction (IV) is a nucleophilic substitution reaction, the following description will be given by regarding the functional group x of compound Rx as a nucleophilic group and the linking reaction unit y1 of compound Ry as a leaving group, but both the functional group x and the linking reaction unit y1 can be a leaving group depending on their nucleophilicity.
[0140] From the viewpoint of the nucleophilic agent, the functional group x of the compound Rx is preferably an oxygen-based nucleophilic group, a nitrogen-based nucleophilic group, or a sulfur-based nucleophilic group. Examples of the oxygen-based nucleophilic group include a hydroxyl group, an alkoxy group, an ether group, and a carboxyl group, among which -OH and -COOH are preferred. Examples of the nitrogen-based nucleophilic group include an ammonium group, a primary amino group, and a secondary amino group, among which -NH2 and -NH- are preferred. Examples of the sulfur-based nucleophilic group include, for example, -SH and a thioether group, among which -SH is preferred.
[0141] When the reaction (IV) is a nucleophilic substitution reaction, the linking reaction unit y1 of the compound Ry from the viewpoint of the leaving group may be an alkylsulfonyl group such as CH3SO2- or CH3CH2SO2-; an arylsulfonyl group (-ArSO2-); a haloalkylsulfonyl group such as CF3SO2- or CCl3SO2-; - -, CH3CH2SO3 - -; arylsulfonate groups (ArSO3 - -);CF3SO3 - -, CCl3SO3 - - and other haloalkylsulfonate groups; and heterocyclic groups are preferred, and these can be used alone or in combination of two or more. Examples of heteroatoms contained in the heterocycle include nitrogen atoms, oxygen atoms, and sulfur atoms, and among these, nitrogen atoms are preferred from the viewpoint of leaving properties. Examples of leaving groups containing a nitrogen atom in the heterocycle include the following formulas (y1-1) to (y1-6): [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} [ka] {In the formula, X is a hydrogen atom or a monovalent substituent.} A monovalent group represented by the following formula is preferred.
[0142] In the formulae (y1-1) to (y1-6), X is a hydrogen atom or a monovalent substituent. Examples of the monovalent substituent include an alkyl group, a haloalkyl group, an alkoxyl group, and a halogen atom.
[0143] When the reaction (IV) is a nucleophilic substitution reaction and the compound Ry has a chain structure, the compound Ry has, in addition to the linking reaction unit y1, the following formulae (y2-1) to (y2-6) as the chain unit y2: [ka] {In the formula, m is an integer of 0 to 20, and n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} [ka] {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} In addition, when the compound Ry contains a plurality of chain units y2, they may be the same or different, and their arrangement may be block or random.
[0144] In formula (y2-1), m is an integer of 0 to 20, and from the viewpoint of the crosslinked network, preferably 1 to 18. In formulae (y2-1) to (y2-6), n is an integer of 1 to 20, and from the viewpoint of the crosslinked network, preferably 2 to 19 or 3 to 16. In formulae (y2-5) to (y2-6), X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and from the viewpoint of the stability of the chain structure, preferably a methylene group, an ethylene group, an n-propylene group, an n-butylene group, an n-hexylene group, an n-heptylene group, an n-octylene group, an n-dodecylene group, an o-phenylene group, an m-phenylene group, or a p-phenylene group.
[0145] When the reaction (IV) is a nucleophilic substitution reaction, preferred combinations of the functional group x of the compound Rx and the linking reaction unit y1 and chain unit y2 of the compound Ry are shown in Tables 2 to 4 below.
[0146] [Table 2]
[0147] [Table 3]
[0148] [Table 4]
[0149] As a specific example 1 of the nucleophilic substitution reaction, the functional group x of the polyolefin is -NH2, the linking reaction unit y1 of the additive (compound Ry) is a skeleton derived from succinimide, and the chain unit y2 is -(O-C2H5) n The reaction scheme for the case where - is shown below. [ka]
[0150] As specific example 2 of a nucleophilic substitution reaction, the reaction scheme is shown below in which the functional groups x of the polyolefin are -SH and -NH2, the linking reaction unit y1 of the additive (compound Ry) is a nitrogen-containing cyclic skeleton, and the chain unit y2 is o-phenylene. [ka]
[0151] When the reaction (IV) is a nucleophilic addition reaction, the functional group x of the compound Rx and the linking reaction unit y1 of the compound Ry can undergo an addition reaction. In the nucleophilic addition reaction, the functional group x of the compound Rx is preferably an oxygen-based nucleophilic group, a nitrogen-based nucleophilic group, or a sulfur-based nucleophilic group. Examples of the oxygen-based nucleophilic group include a hydroxyl group, an alkoxy group, an ether group, and a carboxyl group, among which -OH and -COOH are preferred. Examples of the nitrogen-based nucleophilic group include an ammonium group, a primary amino group, and a secondary amino group, among which -NH2 and -NH- are preferred. Examples of the sulfur-based nucleophilic group include, for example, -SH and a thioether group, among which -SH is preferred.
[0152] In the nucleophilic addition reaction, the linking reaction unit y1 of the compound Ry is represented by the following formulae (Ay1-1) to (Ay1-6): [ka] [ka] [ka] [ka] {In the formula, R is a hydrogen atom or a monovalent organic group.} [ka] [ka] It is preferable that the alkyl group is at least one selected from the group consisting of groups represented by the following formula:
[0153] In formula (Ay1-4), R is a hydrogen atom or a monovalent organic group, and preferably a hydrogen atom, C 1~20 It is an alkyl group, an alicyclic group, or an aromatic group, and more preferably a hydrogen atom, a methyl group, an ethyl group, a cyclohexyl group, or a phenyl group.
[0154] When reaction (IV) is a nucleophilic addition reaction, preferred combinations of the functional group x of compound Rx and the linking reaction unit y1 of compound Ry are shown in Tables 5 and 6 below.
[0155] [Table 5]
[0156] [Table 6]
[0157] As a specific example of a nucleophilic addition reaction, the reaction scheme in the case where the functional group x of the separator is -OH and the linking reaction unit y1 of the additive (compound Ry) is -NCO is shown below. [ka]
[0158] When reaction (IV) is a ring-opening reaction, the functional group x of compound Rx and the linking reaction unit y1 of compound Ry can undergo a ring-opening reaction, and from the viewpoint of availability of raw materials, it is preferable that the cyclic structure on the linking reaction unit y1 side opens. From the same viewpoint, it is more preferable that the linking reaction unit y1 is an epoxy group, it is even more preferable that compound Ry has at least two epoxy groups, and it is even more preferable that it is a diepoxy compound.
[0159] When the reaction (IV) is a ring-opening reaction, the functional group x of the compound Rx is preferably at least one selected from the group consisting of -OH, -NH2, -NH-, -COOH and -SH, and / or the linking reaction unit y1 of the compound Ry is preferably represented by the following formula (ROy1-1): [ka] In the formula, each of the multiple Xs is independently a hydrogen atom or a monovalent substituent. In formula (ROy1-1), each of the multiple Xs independently represents a hydrogen atom or a monovalent substituent, and preferably represents a hydrogen atom, C 1~20 The functional group x of the compound Rx and the linking reaction unit y1 of the compound Ry for the epoxy ring-opening reaction are preferably combined as shown in Table 7 below.
[0160] [Table 7]
[0161] Reaction (V) The first functional group of the separator is A and the metal ion is M. n+ A schematic scheme of reaction (V) and an example of the functional group A are shown below. [ka]
[0162] In the above scheme, metal ion M n+ is preferably eluted from the electricity storage device (hereinafter, also referred to as eluted metal ion), for example, Zn 2+ , Mn 2+ , Co 3+ , Ni 2+ and Li + The functional group A may be at least one selected from the group consisting of -COO - The coordinate bond in the above case is exemplified below. [ka]
[0163] Functional group A is -COOH and the eluted metal ion is Zn 2+ A specific scheme of reaction (V) in the case of is shown below. [ka]
[0164] In the above scheme, hydrofluoric acid (HF) can be derived from, for example, the electrolyte, electrolytic solution, electrode active material, additive, or decomposition product or water absorption product thereof contained in the electricity storage device, depending on the charge / discharge cycle of the electricity storage device.
[0165] <Other Ingredients> The polyolefin microporous membrane may contain, in addition to the polyolefin, known additives such as a dehydration condensation catalyst, a metal soap such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, a coloring pigment, an inorganic filler, or inorganic particles, if desired.
[0166] Characteristics of microporous membranes The following microporous membrane properties are for flat or single-layer membranes. When the microporous membrane is in the form of a laminate membrane, the following properties can be measured after removing layers other than the polyolefin microporous membrane from the laminate membrane.
[0167] The porosity of the polyolefin microporous film is preferably 20% or more, more preferably 30% or more, and even more preferably 32% or more or 35% or more. When the porosity of the microporous film is 20% or more, the followability to the rapid movement of lithium ions tends to be improved. On the other hand, the porosity of the microporous film is preferably 90% or less, more preferably 80% or less, and even more preferably 50% or less. When the porosity of the microporous film is 90% or less, the film strength tends to be improved and self-discharge tends to be suppressed. The porosity of the microporous film can be measured by the method described in the Examples.
[0168] The air permeability of a microporous polyolefin membrane is 3 The air permeability of the microporous membrane is preferably 1 second or more, more preferably 50 seconds or more, even more preferably 55 seconds or more, and even more preferably 70 seconds or more, 90 seconds or more, or 110 seconds or more per second. When the air permeability of the microporous membrane is 1 second or more, the balance between the membrane thickness, the porosity, and the average pore size tends to be improved. In addition, the air permeability of the microporous membrane is preferably 400 seconds or less, more preferably 300 seconds or less, and even more preferably 270 seconds or less. When the air permeability of the microporous membrane is 400 seconds or less, the ion permeability tends to be improved. The air permeability of the microporous membrane can be measured by the method described in the Examples.
[0169] The tensile strength of the polyolefin microporous membrane is preferably 1000 kgf / cm in both MD and TD (direction perpendicular to MD, membrane width direction). 2 More preferably, it is 1050 kgf / cm 2 More preferably, it is 1100 kgf / cm 2 The tensile strength is 1000kgf / cm 2 By being equal to or greater than this, breakage during slitting or winding of the electricity storage device tends to be further suppressed, or a short circuit due to a foreign object or the like in the electricity storage device tends to be further suppressed. On the other hand, the tensile strength of the microporous membrane is preferably 5000 kgf / cm 2 More preferably, it is 4500 kgf / cm or less. 2More preferably, it is 4000 kgf / cm or less. 2 The tensile strength of the microporous membrane is 5000 kgf / cm or less. 2 By satisfying this condition, the microporous membrane will relax early during the heat test, weakening the contractile force, and as a result, safety tends to be improved.
[0170] The tensile modulus of the polyolefin microporous membrane is preferably 120 N / cm or less, more preferably 100 N / cm or less, and even more preferably 90 N / cm or less in both MD and TD. A tensile modulus of 120 N / cm or less indicates that the separator for a lithium ion secondary battery is not extremely oriented, and in a heating test or the like, when a blocking agent such as polyethylene melts and shrinks, the polyethylene etc. causes stress relaxation early, which suppresses the shrinkage of the separator in the battery and tends to easily prevent short circuits between electrodes. That is, the safety of the separator during heating can be further improved. Such a microporous membrane with a low tensile modulus can be easily achieved by including polyethylene having a weight average molecular weight of 500,000 or less in the polyolefin forming the microporous membrane. On the other hand, the lower limit of the tensile modulus of the microporous membrane is not particularly limited, but is preferably 10 N / cm or more, more preferably 30 N / cm or more, and even more preferably 50 N / cm or more. The ratio of the tensile modulus in the MD and TD directions of the polyolefin microporous membrane (tensile modulus in the MD direction / tensile modulus in the TD direction) is preferably 0.2 to 3.0, more preferably 0.5 to 2.0, and even more preferably 0.8 to 1.2. When the ratio of the tensile modulus in the MD and TD directions of the polyolefin microporous membrane is within such a range, the shrinkage force in the MD and TD directions becomes uniform when a blocking agent such as polyethylene melts and shrinks. As a result, when the separator is thermally shrunk in the battery, the shear stress applied to the electrode adjacent to the separator also becomes uniform in the MD and TD directions, which tends to prevent the destruction of the laminate of the electrode and the separator. That is, the safety of the separator during heating can be further improved. The tensile modulus of the microporous membrane can be appropriately adjusted by adjusting the degree of stretching, or by relaxing after stretching as necessary.
[0171] The thickness of the polyolefin microporous membrane is preferably 1.0 μm or more, more preferably 2.0 μm or more, and even more preferably 3.0 μm or more, 4.0 μm or more, or 5.5 μm or more. When the thickness of the microporous membrane is 1.0 μm or more, the membrane strength tends to be further improved. In addition, the thickness of the microporous membrane is preferably 500 μm or less, more preferably 100 μm or less, and even more preferably 80 μm or less, 22 μm or less, or 19 μm or less. When the thickness of the microporous membrane is 500 μm or less, the ion permeability tends to be further improved. The thickness of the microporous membrane can be measured by the method described in the Examples.
[0172] In the case of separators used in recent relatively high-capacity lithium-ion secondary batteries, the thickness of the polyolefin microporous membrane is preferably 25 μm or less, more preferably 22 μm or less or 20 μm or less, even more preferably 18 μm or less, and particularly preferably 16 μm or less. In this case, the permeability tends to be further improved by having the membrane thickness of the microporous membrane be 25 μm or less. In this case, the lower limit of the membrane thickness may be 1.0 μm or more, 3.0 μm or more, 4.0 μm or more, or 5.5 μm or more.
[0173] <Surface layer> The surface layer is formed on at least one side of the polyolefin microporous membrane as the substrate. The surface layer may be disposed on one or both sides of the substrate, and is preferably disposed so that at least a part of the substrate is exposed. The surface layer is preferably at least one layer selected from the group consisting of a thermoplastic polymer-containing layer, an active layer, and a heat-resistant porous layer.
[0174] (Thermoplastic polymer-containing layer) The thermoplastic polymer-containing layer is formed on at least one side of the polyolefin microporous membrane as the substrate. The thermoplastic polymer-containing layer may be disposed on one or both sides of the substrate, and is preferably disposed so that at least a part of the substrate is exposed.
[0175] The area ratio (coverage area ratio) of the thermoplastic polymer-containing layer to the total area of the surface of the substrate on which the thermoplastic polymer-containing layer can be arranged is preferably 5% to 90%. Setting the coverage area ratio to 90% or less is preferable from the viewpoint of further suppressing clogging of the pores of the substrate by the thermoplastic polymer and further improving the permeability of the separator. On the other hand, setting the coverage area ratio to 5% or more is preferable from the viewpoint of further improving the adhesion to the electrode. From this viewpoint, the upper limit of the coverage area ratio is more preferably 80% or less, 75% or less, or 70%, and the lower limit of this area ratio is more preferably 10% or more, or 15% or more. This coverage area ratio is measured by observing the surface of the separator on which the thermoplastic polymer-containing layer is formed with an SEM. In addition, when the thermoplastic polymer-containing layer is a layer in which inorganic particles are mixed, the area of the thermoplastic polymer is calculated by taking the total area of the thermoplastic polymer and the inorganic particles as 100%.
[0176] When the thermoplastic polymer-containing layer is disposed on only a part of the surface of the separator substrate, the arrangement pattern of the thermoplastic polymer layer may be, for example, a dotted, striped, lattice, striped, tortoiseshell, random, etc., or a combination thereof. The thickness of the thermoplastic polymer-containing layer disposed on the substrate is preferably 0.01 μm to 5 μm, more preferably 0.1 μm to 3 μm, and even more preferably 0.1 to 1 μm, per one surface of the substrate.
[0177] The thermoplastic polymer-containing layer contains a thermoplastic polymer. The thermoplastic polymer-containing layer may contain, based on the total amount of the layer, preferably 60% by mass or more, more preferably 90% by mass or more, even more preferably 95% by mass or more, and particularly preferably 98% by mass or more of the thermoplastic polymer. The thermoplastic polymer layer may contain other components in addition to the thermoplastic polymer.
[0178] Thermoplastic polymers include, for example, the following: Polyolefin resins such as polyethylene, polypropylene, and α-polyolefin; Fluorine-based polymers such as polyvinylidene fluoride and polytetrafluoroethylene, or copolymers containing these; Diene-based polymers containing conjugated dienes such as butadiene and isoprene as monomer units, copolymers containing these, or hydrogenated products thereof; An acrylic polymer containing a (meth)acrylate, (meth)acrylic acid, or the like as a monomer unit and having no polyalkylene glycol unit, an acrylic polymer containing a (meth)acrylate, (meth)acrylic acid, or the like as a monomer unit and having one or two polyalkylene glycol units, or a copolymer containing these, or a hydrogenated product thereof; Rubbers such as ethylene propylene rubber, polyvinyl alcohol, and polyvinyl acetate; Cellulose derivatives such as ethyl cellulose, methyl cellulose, hydroxyethyl cellulose, and carboxymethyl cellulose; Polyalkylene glycols having no polymerizable functional groups, such as polyethylene glycol and polypropylene glycol; Resins such as polyphenylene ether, polysulfone, polyethersulfone, polyphenylene sulfide, polyetherimide, polyamideimide, polyamide, and polyester; A copolymer having, as a copolymerization unit, an ethylenically unsaturated monomer having 3 or more repeating alkylene glycol units; and Combinations of these; Examples include: Among these, from the viewpoint of improving safety in a puncture test of an electricity storage device including a separator, it is preferable that the thermoplastic polymer contains a polymerized unit of a (meth)acrylic acid ester or (meth)acrylic acid.
[0179] In nail penetration tests, experiments suggest that the generation of heat can be suppressed by minimizing the short circuit area around the device where the nail penetrates. Meanwhile, the part closest to the nail is at a very high temperature, and the polyethylene microporous membrane is in a molten state. It has been experimentally observed that the force of the molten resin trying to minimize its specific surface area causes a hole to expand concentrically from the nail and shrink toward the unmelted part. The hole formed at this time becomes the short circuit area, and is thought to control the speed of internal heat generation and whether or not the battery will ultimately ignite or explode.
[0180] On the other hand, when manufacturing a storage device such as a battery, it is inevitable that a bent (R) part may occur in the wound kit, and the clearance between the positive and negative electrodes may not be uniform over the entire area (region). Although the heat resistance of uncoated chemically crosslinked substrates of thermoplastic polymers such as acrylic resins has been improved, it is presumed that the thinner parts of the uneven clearance between the positive and negative electrodes shrink more during nail penetration tests, resulting in a wide short circuit area. In addition, due to the expansion and contraction deformation of the electrodes during the cycle of the storage device, the uncoated separator of thermoplastic polymers may have a shift over the entire surface, resulting in uneven clearance between the positive and negative electrodes. It is presumed that the parts closer to the electrodes shrink more during nail penetration tests, resulting in a wide short circuit area.
[0181] In contrast, the chemically crosslinked substrate membrane coated with a thermoplastic polymer such as acrylic resin has a thermoplastic polymer layer that exhibits adhesion between the separator and the electrode, and can maintain a more uniform clearance between the positive and negative electrodes over the entire area. In addition, it can follow the electrode expansion and contraction deformation during the cycle of the energy storage device, and can ensure a uniform clearance even after long-term use. In addition to ensuring a uniform clearance in this way, the thermoplastic polymer layer with an adjusted coating area can swell with the electrolyte, and the electrolyte can be supplied (exuded) from the thermoplastic polymer layer to the chemically crosslinked substrate, allowing the crosslinking reaction to proceed evenly over the entire area of the chemically crosslinked substrate within the energy storage device, thereby obtaining good nail penetration test results.
[0182] From the viewpoint of improving safety in a puncture test of an electricity storage device including a separator, the glass transition temperature (Tg) of the thermoplastic polymer is preferably within the range of -40°C to 105°C, and more preferably within the range of -38°C to 100°C.
[0183] From the viewpoints of wettability to the polyolefin multilayer microporous membrane, binding between the polyolefin multilayer microporous membrane and the thermoplastic polymer layer, and adhesion to the electrode, it is preferable that the thermoplastic polymer layer is blended with a polymer having a glass transition temperature of less than 20°C, and from the viewpoints of blocking resistance and ion permeability, it is preferable that the thermoplastic polymer layer is also blended with a polymer having a glass transition temperature of 20°C or higher.
[0184] The fact that a thermoplastic polymer has at least two glass transition temperatures can be achieved by, but is not limited to, a method of blending two or more types of thermoplastic polymers, a method of using a thermoplastic polymer having a core-shell structure, and the like. The core-shell structure is a polymer having a double structure in which the polymer belonging to the central portion and the polymer belonging to the outer shell portion have different compositions. In particular, in polymer blends and core-shell structures, the glass transition temperature of the entire thermoplastic polymer can be controlled by combining a polymer with a high glass transition temperature with a polymer with a low glass transition temperature, and multiple functions can be imparted to the entire thermoplastic polymer.
[0185] From the viewpoint of blocking inhibition and ion permeability of the separator, the thermoplastic copolymer is preferably in a particulate form when the glass transition temperature is, for example, 20° C. or higher, 25° C. or higher, or 30° C. or higher. By including the particulate thermoplastic copolymer in the thermoplastic polymer layer, it is possible to ensure the porosity of the thermoplastic polymer layer disposed on the substrate and the blocking resistance of the separator.
[0186] The average particle size of the particulate thermoplastic copolymer is preferably 10 nm to 2,000 nm, more preferably 50 nm to 1,500 nm, even more preferably 100 nm to 1,000 nm, particularly preferably 130 nm to 800 nm, particularly preferably 150 to 800 nm, and most preferably 200 to 750 nm. The average particle size of 10 nm or more means that when the particulate thermoplastic polymer is applied to a substrate including at least a porous membrane, the dimensions of the particulate thermoplastic polymer are secured to such an extent that it does not enter the pores of the substrate. Therefore, in this case, it is preferable from the viewpoint of improving the adhesion between the electrode and the separator and the cycle characteristics of the electric storage device. In addition, the average particle size of 2,000 nm or less is preferable from the viewpoint of applying a necessary amount of the particulate thermoplastic polymer to the substrate in order to achieve both the adhesion between the electrode and the separator and the cycle characteristics of the electric storage device.
[0187] The particulate thermoplastic polymer described above can be produced by a known polymerization method using the corresponding monomer or comonomer. As the polymerization method, for example, a suitable method such as solution polymerization, emulsion polymerization, bulk polymerization, etc. can be adopted.
[0188] Since the thermoplastic polymer layer can be easily formed by coating, it is preferred to form a particulate thermoplastic polymer by emulsion polymerization and use the resulting thermoplastic polymer emulsion as the water-based latex.
[0189] The thermoplastic polymer-containing layer may contain only a thermoplastic polymer, or may contain, in addition to the thermoplastic polymer, other optional components, such as the known additives described above for the polyolefin microporous membrane.
[0190] (active layer) The active layer is disposed on at least one side of the polyolefin microporous membrane as the substrate. By disposing the active layer on the polyolefin microporous membrane, which is the chemically crosslinkable substrate described above, the heat shrinkability and / or hot box testability tend to be superior compared to conventional resin coating on substrates that do not have such chemical crosslinkability. In addition, the separator obtained by bonding the active layer to the substrate through a process of coating the substrate with the active layer tends to provide a power storage device with high output characteristics that is less likely to decrease in ion permeability. Furthermore, even when the temperature rises rapidly during abnormal heat generation, the separator tends to exhibit smooth shutdown characteristics and to easily obtain high safety. From this viewpoint, the active layer may be disposed on one or both sides of the substrate, and it is also preferable that the active layer is disposed so that at least a part of the substrate is exposed.
[0191] From the viewpoint of heat shrinkability and / or hot box testability, the active layer preferably contains a fluorine atom-containing vinyl compound, and more preferably contains a fluorine atom-containing vinyl compound and inorganic particles.
[0192] As the fluorine atom-containing vinyl compound, for example, compounds known as fluorine-based resins or binders can be used.
[0193] The weight average molecular weight (Mw) of the fluorine-containing vinyl compound is 0.6×10 6 ~2.5×10 6 It is preferable that the Mw of the fluorine atom-containing vinyl compound is within this range, since the heat shrinkability and hot box testability tend to be good. From the same viewpoint, the molecular weight of the fluorine atom-containing vinyl compound is preferably within the range of 270 kDa to 600 kDa, and it is also preferable to use a fluorine atom-containing vinyl compound having a molecular weight of 270 kDa to 310 kDa in combination with a fluorine atom-containing vinyl compound having a molecular weight of 570 kDa to 600 kDa.
[0194] From the viewpoints of heat shrinkability and hot box testability, the melting point of the fluorine atom-containing vinyl compound is preferably within the range of 130° C. to 171° C. From the same viewpoint, at least one may be selected from the group consisting of fluorine atom-containing vinyl compounds having a melting point of 130° C. to 136° C., fluorine atom-containing vinyl compounds having a melting point of 167° C. to 171° C., and fluorine atom-containing vinyl compounds having a melting point of 150° C.±1° C.
[0195] Among compounds known as fluorine-based resins or binders, at least one selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (polymer PVDF-HFP), polyvinylidene fluoride-chlorotrifluoroethylene (polymer PVDF-CTFE), PVDF homopolymer, a mixture of PVDF and tetrafluoroethylene-ethylene copolymer (ETFE), or vinylidene fluoride-tetrafluoroethylene-ethylene terpolymer is preferred, and at least one selected from the group consisting of polymer PVDF-HFP and polymer PVDF-CTFE is more preferred. By copolymerizing HFP or CTFE with vinylidene fluoride, the crystallinity of the fluorine-based resin can be controlled within an appropriate range, so that the flow of the active layer can be suppressed during adhesion treatment with the electrode. Furthermore, since the adhesive strength is improved during adhesion treatment with the electrode, no interface slippage occurs when used as a separator for a secondary battery, and therefore the heat shrinkability and / or hot box testability are improved. Note that fluorine-based resins are usually obtained by emulsion polymerization or suspension polymerization.
[0196] Specific examples of PVDF include the Kynar Flex (registered trademark) series of Arkema, such as LBG, LBG8200, and the like; and the Solef (registered trademark) series of SOLVAY, such as grades 1015 and 6020, and the like.
[0197] Specific examples of polymeric PVDF-HFP include the Solef® series from SOLVAY, such as grades 21216 and 21510 (both of which are soluble in acetone), etc. Specific examples of polymeric PVDF-CTFE include the Solef® series from SOLVAY, such as grade 31508 (which is soluble in acetone), etc.
[0198] Of the above fluororesins, the proportion of structural units derived from HFP or CTFE in polymer PVDF-HFP and polymer PVDF-CTFE is preferably 2.0% by mass to 20.0% by mass. When the HFP or CTFE content is 2.0% by mass or more, the crystallization of the fluororesin is suppressed from proceeding to a high degree, and when the HFP or CTFE content is 20.0% by mass or less, the crystallization of the fluororesin is moderately expressed. From the same viewpoint, the proportion of structural units derived from HFP or CTFE in polymer PVDF-HFP and polymer PVDF-CTFE is more preferably 2.25% by mass or more, even more preferably 2.5% by mass or more, more preferably 18% by mass or less, and even more preferably 15% by mass or less.
[0199] In the Hot Box test, it is important that the separator made of polyolefin such as polyethylene at 150℃ provides an isolation layer between the positive and negative electrodes after crystal melting. When manufacturing a storage device such as a battery, it is inevitable that a bent (R) part may occur in the wound kit, and the clearance of the positive and negative electrodes over the entire area (region) may not be uniform. Although the heat resistance of the uncoated chemically crosslinked substrate made of fluororesin such as PVDF has been improved, it is presumed that the short circuit prevention in the thinner part is insufficient in the uneven clearance of the positive and negative electrodes. In addition, during the cycle of the storage device, the uncoated separator made of fluororesin such as PVDF may shift over the entire surface due to the expansion and contraction deformation of the electrodes, which may cause the clearance between the positive and negative electrodes to become uneven, which may make it easier for a short circuit to occur in the part closer to the electrodes. Furthermore, when partial thermal decomposition of the positive electrode such as the NMC positive electrode occurs, it is expected that compressive strain will occur in the vicinity of the electrode due to local expansion caused by O2 release. In other words, the higher the nickel content in the NMC positive electrode, the more difficult it becomes to ensure isolation between the positive and negative electrodes when using a positive electrode that generates O2 at a lower temperature range. In a similar manner, there is a problem of crystal instability (thermal decomposition) in the constituent positive electrodes of LAC positive electrodes and other electrodes other than NMC. Under the most severe conditions such as NMC positive electrodes, assuming crystal decomposition from 150℃, this problem can be solved, and the heat shrinkability and hot box testability can be improved.
[0200] On the other hand, in the case of a chemically crosslinked substrate membrane coated with a fluororesin such as PVDF, the fluororesin layer exhibits adhesion between the separator and the electrode, and a more uniform clearance can be maintained between the positive and negative electrodes over the entire area. In addition, when a separator including an active layer is impregnated with an electrolyte, even if there is electrode expansion and contraction deformation during the cycle of a battery or other storage device, or even if O2 is generated during thermal decomposition of the positive electrode, the separator can follow the deformation and ensure a uniform clearance even after long-term use. In addition to the uniform clearance being ensured in this way, the adjusted PVDF-based resin can swell with the electrolyte and can uniformly supply (permeate) the electrolyte to the chemically crosslinked substrate, thereby allowing a uniform crosslinking reaction to proceed in the battery of the chemically crosslinked substrate. Therefore, in order to ensure the expression of good heat resistance over the entire area of the separator and obtain good HotBox test results, it is preferable to select the above-mentioned fluororesin.
[0201] It is more preferable that the active layer contains one or more polar groups selected from the group consisting of hydroxyl group (-OH), carboxyl group (-COOH), maleic anhydride group (-COOOC-), sulfonic acid group (-SO3H), and pyrrolidone group (-NCO-), or a polymer having two or more of these polar groups, because the cycle characteristics of the separator at low temperatures (e.g., less than 90°C, less than 50°C, less than 25°C, less than 10°C, less than 5°C, 0°C or less, etc.) are improved. Examples of such polymers include at least one polymer selected from cyanoethyl pullulan, cyanoethyl polyvinyl alcohol, cyanoethyl cellulose, and cyanoethyl sucrose. It is presumed that the reason why the cycle characteristics of the separator at low temperatures are improved by containing a polymer having such a polar group in the active layer is that the resistance of the separator is reduced even at low temperatures due to the high dielectric constant of these polymers. The relative dielectric constant of the polymer having a polar group can be from 1 to 100 (measurement frequency = 1 kHz), and is preferably 10 or more.
[0202] The active layer may contain a resin other than the above resins (other resins). Examples of the other resins include, but are not limited to, polyvinylidene fluoride-trichloroethylene, polymethyl methacrylate, polyacrylonitrile, polyvinyl acetate, ethylene-vinyl acetate copolymer, polyimide, polyethylene oxide, etc., which may be used alone or in combination of two or more of them.
[0203] The inorganic particles used in the active layer are not particularly limited, but preferably have a melting point of 200° C. or higher, high electrical insulation properties, and are electrochemically stable within the range of use of lithium ion secondary batteries.
[0204] The inorganic particles are not particularly limited, but examples thereof include oxide ceramics such as alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, aluminum hydroxide, aluminum oxide hydroxide, potassium titanate, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These may be used alone or in combination.
[0205] Among these, from the viewpoint of improving the electrochemical stability and heat resistance of the separator, aluminum oxide compounds such as alumina and aluminum oxide hydroxide; and aluminum silicate compounds having no ion exchange capacity, such as kaolinite, dickite, nacrite, halloysite, and pyrophyllite, are preferred.
[0206] Alumina has many crystal forms, such as α-alumina, β-alumina, γ-alumina, and θ-alumina, and any of these can be suitably used. Among these, α-alumina is preferred because it is thermally and chemically stable.
[0207] As the aluminum oxide compound, aluminum oxide hydroxide (AlO(OH)) is particularly preferred. As the aluminum oxide hydroxide, boehmite is more preferred from the viewpoint of preventing internal short circuits caused by the generation of lithium dendrites. By employing particles mainly composed of boehmite as the inorganic particles constituting the active layer, a very lightweight porous layer can be realized while maintaining high permeability, and even in a thinner porous layer, the thermal shrinkage of the porous film at high temperatures is suppressed, tending to exhibit excellent heat resistance. Synthetic boehmite is more preferred, which can reduce ionic impurities that adversely affect the characteristics of electrochemical devices.
[0208] As the aluminum silicate compound having no ion exchange capacity, kaolin, which is mainly composed of kaolin mineral, is more preferable because it is inexpensive and easily available. Kaolin includes wet kaolin and calcined kaolin obtained by calcining wet kaolin. Calcined kaolin is particularly preferable. Calcined kaolin is particularly preferable from the viewpoint of electrochemical stability because water of crystallization is released during the calcination process and impurities are also removed.
[0209] Average particle size of inorganic particles (D 50 ) is preferably 0.2 μm or more and 2.0 μm or less, and more preferably more than 0.2 μm and 2.0 μm or less. 50 Adjusting to within the above range is preferable from the viewpoint of suppressing thermal shrinkage at high temperatures (e.g., 200° C. or higher) even when the thickness of the active layer is thin (e.g., 5 μm or less). Examples of methods for adjusting the particle size and distribution of the inorganic particles include a method of reducing the particle size by pulverizing the inorganic particles using an appropriate pulverizing device such as a ball mill, a bead mill, or a jet mill.
[0210] Examples of the shape of the inorganic particles include plate-like, scaly, needle-like, columnar, spherical, polyhedral, block-like, etc. A combination of inorganic fillers having these shapes may be used.
[0211] The mass ratio of the fluorine atom-containing vinyl compound to the inorganic particles in the active layer (fluorine atom-containing vinyl compound / inorganic particles) is preferably 5 / 95 to 80 / 20, more preferably 7 / 93 to 65 / 35, even more preferably 9 / 91 to 50 / 50, and even more preferably 10 / 90 to 40 / 60. When the mass ratio of the fluorine atom-containing vinyl compound to the inorganic particles is within such a range, not only the heat shrinkability and / or hot box testability but also the battery winding property tend to be good, which is preferable. For example, when the above-mentioned PVDF-HFP or the like is used as the fluorine atom-containing vinyl compound, the resin dissolves on the film surface due to the tribomaterial effect specific to this resin, so that the battery winding property tends to be improved.
[0212] The thickness of the active layer is preferably 5 μm or less, more preferably 2 μmm or less, from the viewpoint of improving heat shrinkability and / or hot box testability, and is preferably 0.5 μm or more, from the viewpoint of improving heat resistance and insulation properties.
[0213] The layer density of the active layer is 0.5 g / cm 3 ~3.0g / cm 3 and preferably 0.7 g / cm 3 ~2.0g / cm 3 It is more preferable that the layer density of the active layer is 0.5 g / cm 3 When the heat shrinkage rate is 3.0 g / cm or more, the heat shrinkage rate at high temperatures tends to be good. 3 When it is equal to or less than this, the air permeability tends to be good.
[0214] The active layer may contain optional components other than the fluorine atom-containing vinyl compound and inorganic particles. The optional components may include, for example, the known additives (except inorganic particles) described above for the polyolefin microporous membrane. In addition, the type, quality, and grade of the fluorine atom-containing vinyl compound, inorganic particles, and optional components used may be adjusted according to the properties to be imparted to the active layer and the desired thickness of the active layer.
[0215] (Heat-resistant porous layer) The heat-resistant porous layer contains a heat-resistant resin and has a large number of micropores therein. In the heat-resistant porous layer, these micropores may have a structure in which they are interconnected, allowing gas or liquid to pass from one surface to the other.
[0216] The heat-resistant porous layer is laminated on at least one side of the polyolefin microporous membrane as the substrate. By disposing the heat-resistant porous layer on the polyolefin microporous membrane, which is the chemically crosslinkable substrate described above, the high-temperature bar impact fracture test tends to be superior compared to conventional heat-resistant resin coating on a substrate not having such chemical crosslinking. In addition, the separator obtained by bonding the heat-resistant porous layer to the substrate through the process of laminating the heat-resistant porous layer on the substrate tends to provide a power storage device with high output characteristics that is less likely to decrease in ion permeability. Furthermore, even when the temperature rises rapidly during abnormal heat generation, the separator tends to exhibit smooth shutdown characteristics and to easily obtain high safety. From this viewpoint, the heat-resistant porous layer may be disposed on one or both sides of the substrate, and it is also preferable that the heat-resistant porous layer is disposed so that at least a part of the substrate is exposed.
[0217] From the viewpoint of improving the high-temperature bar impact fracture test properties, the heat-resistant porous layer preferably contains a heat-resistant resin and an inorganic filler.
[0218] As the heat-resistant resin, it is preferable to use a resin having a melting point of more than 150°C, a melting point of 250°C or more, or, for a resin that does not substantially have a melting point, a resin having a thermal decomposition temperature of 250°C or more. Examples of such heat-resistant resins include wholly aromatic polyamides, polyimides, polyamideimides, polysulfones, polyketones, polyethers, polyetherketones, polyetherimides, cellulose, and the like. Among them, wholly aromatic polyamides are preferred from the viewpoint of durability, and para-type aromatic polyamides and / or meta-type aromatic polyamides are more preferred. In addition, meta-type aromatic polyamides are preferred from the viewpoint of the formability of the porous layer and the oxidation-reduction resistance.
[0219] The heat-resistant resin has a molecular weight distribution Mw / Mn of 5≦Mw / Mn≦100 and / or a weight average molecular weight Mw of 8.0×10 3 Above 1.0×10 6 It is preferable that the molecular weight is less than 1000 nm. When a heat-resistant resin characterized by these molecular weights is used, a better heat-resistant porous layer can be formed when a heat-resistant porous layer is formed on a polyolefin microporous membrane by a wet coating method. This is because a heat-resistant resin having a wide molecular weight distribution as described above also contains a large amount of low molecular weight substances, and the processability of the coating liquid in which the resin is dissolved is improved. Therefore, a heat-resistant porous layer with few defects and a uniform thickness is easily formed. In addition, since it becomes possible to perform coating well without applying a strong coating pressure, the occurrence of clogging of the pores on the surface of the polyolefin microporous membrane is suppressed, and the decrease in air permeability at the interface between the heat-resistant porous layer and the polyolefin microporous membrane is prevented. In addition, when the coating liquid is applied to the polyolefin microporous membrane and immersed in a coagulation liquid, the resin in the coating film becomes easy to move, and good pore formation is possible. Furthermore, the low molecular weight substances contained in the resin are compatible with the inorganic filler, and the drop-off of the inorganic filler that contributes to pore formation can be prevented. As a result, a heat-resistant porous layer having uniform fine pores can be easily formed, and therefore a separator having excellent ion permeability and good contact with the electrodes can be obtained.
[0220] The heat-resistant resin preferably contains 1% by weight to 15% by weight, more preferably 3% by weight to 10% by weight, of a low-molecular-weight polymer having a molecular weight of 8,000 or less. In this case, a good heat-resistant porous layer can be formed in the same manner as described above.
[0221] Furthermore, when aromatic polyamide is used as the heat-resistant resin, it is preferable that the terminal group concentration ratio of the aromatic polyamide is [COOX {wherein X represents hydrogen, an alkali metal or an alkaline earth metal}] / [NH2]≧1. For example, terminal carboxyl groups such as COONa have the effect of removing undesirable films formed on the negative electrode side of a battery. Therefore, when an aromatic polyamide having more terminal carboxyl groups than terminal amine groups is used, a nonaqueous electrolyte secondary battery with a stable discharge capacity over a long period of time tends to be obtained. For example, a battery having a good discharge capacity may be obtained even after 100 or 1000 charge / discharge cycles.
[0222] The inorganic filler used in the heat-resistant porous layer is not particularly limited, but is preferably one that has a melting point of 200° C. or higher, has high electrical insulation properties, and is electrochemically stable within the range of use of lithium ion secondary batteries.
[0223] Examples of the shape of the inorganic filler include granular, plate-like, scaly, needle-like, columnar, spherical, polyhedral, blocky, etc. A combination of inorganic fillers having these shapes may be used.
[0224] Average particle size of inorganic filler (D 50 ) is preferably 0.2 μm or more and 0.9 μm or less, and more preferably more than 0.2 μm and 0.9 μm or less. 50 Adjusting to within the above range is preferable from the viewpoint of suppressing thermal shrinkage at high temperatures (e.g., 150° C. or higher, 200° C. or higher, or 200° C. or higher) or improving bar impact fracture test properties at high temperatures, even when the heat-resistant porous layer has a thin thickness (e.g., 5 μm or less, or 4 μm or less). Examples of a method for adjusting the particle size and distribution of the inorganic filler include a method of reducing the particle size by pulverizing the inorganic filler using an appropriate pulverizing device such as a ball mill, a bead mill, or a jet mill.
[0225] In addition to the heat-resistant resin, the heat-resistant porous layer preferably contains 25% by mass to 95% by mass of an inorganic filler based on the mass of the heat-resistant porous layer. An inorganic filler content of 25% by mass or more is preferable for dimensional stability and heat resistance at high temperatures, while an inorganic filler content of 95% by mass or less is preferable for strength, handling properties, or moldability.
[0226] From the viewpoint of improving the bar impact fracture test properties at high temperatures, the heat-resistant porous layer preferably contains 30 mass % to 90 mass % and more preferably 32 mass % to 85 mass % of inorganic filler having an average particle size in the range of 0.2 μm to 0.9 μm, based on the mass of the heat-resistant porous layer.
[0227] The inorganic filler is not particularly limited, but examples thereof include oxide ceramics such as alumina, silica, titania, zirconia, magnesia, ceria, yttria, zinc oxide, and iron oxide; nitride ceramics such as silicon nitride, titanium nitride, and boron nitride; ceramics such as silicon carbide, calcium carbonate, magnesium sulfate, aluminum sulfate, aluminum hydroxide, aluminum oxide hydroxide, potassium titanate, talc, kaolinite, dickite, nacrite, halloysite, pyrophyllite, montmorillonite, sericite, mica, amesite, bentonite, asbestos, zeolite, calcium silicate, magnesium silicate, diatomaceous earth, and silica sand; and glass fibers. These may be used alone or in combination.
[0228] Among these, from the viewpoint of improving the electrochemical stability and heat resistance of the separator, aluminum oxide compounds such as alumina and aluminum oxide hydroxide; and aluminum silicate compounds having no ion exchange capacity, such as kaolinite, dickite, nacrite, halloysite, and pyrophyllite, are preferred.
[0229] Alumina has many crystal forms, such as α-alumina, β-alumina, γ-alumina, and θ-alumina, and any of these can be suitably used. Among these, α-alumina is preferred because it is thermally and chemically stable.
[0230] As the aluminum oxide compound, aluminum oxide hydroxide (AlO(OH)) is particularly preferred. As the aluminum oxide hydroxide, boehmite is more preferred from the viewpoint of preventing internal short circuits caused by the generation of lithium dendrites. By employing particles mainly composed of boehmite as the inorganic filler constituting the heat-resistant porous layer, a very lightweight porous layer can be realized while maintaining high permeability, and even in a thinner porous layer, the thermal shrinkage of the microporous film at high temperatures is suppressed, tending to exhibit excellent heat resistance. Synthetic boehmite is even more preferred, which can reduce ionic impurities that adversely affect the characteristics of electrochemical devices.
[0231] As the aluminum silicate compound having no ion exchange capacity, kaolin, which is mainly composed of kaolin mineral, is more preferable because it is inexpensive and easily available. Kaolin includes wet kaolin and calcined kaolin obtained by calcining wet kaolin. Calcined kaolin is particularly preferable. Calcined kaolin is particularly preferable from the viewpoint of electrochemical stability because water of crystallization is released during the calcination process and impurities are also removed.
[0232] The porosity of the heat-resistant porous layer is preferably in the range of 60% to 90%. When the porosity of the heat-resistant porous layer is 90% or less, it is preferable from the viewpoint of heat resistance. Also, when the porosity of the heat-resistant porous layer is 60% or more, it is preferable from the viewpoint of cycle characteristics or storage characteristics and discharge characteristics of the battery. From the same viewpoint, the coating amount (basis weight) of the heat-resistant porous layer is 2 g / m 2 ~10g / m 2 It is preferable that:
[0233] The thickness of the heat-resistant resin layer is preferably 8 μm or less, more preferably 4 μm or less or 3.5 μm or less, per side of the polyolefin microporous membrane as the substrate from the viewpoint of high-temperature bar impact breaking test properties. The thickness of the heat-resistant resin layer can be 0.5 μm or more from the viewpoint of improving heat resistance and insulation properties.
[0234] The heat-resistant resin layer may contain optional components other than the heat-resistant resin and inorganic particles. Examples of the optional components include the known additives (excluding inorganic particles) described above for the polyolefin microporous membrane, resins other than the heat-resistant resin, and the like.
[0235] <<Method for producing separator for power storage device>> The method for producing a separator for an electricity storage device according to the present disclosure includes producing a substrate layer containing a polyolefin, and then forming or arranging a desired layer on the substrate layer. In the first embodiment, the desired layer is a layer containing inorganic particles (layer B) and a layer containing a thermoplastic polymer (layer C), and in the second embodiment, the surface layer (i.e., at least one of a thermoplastic polymer-containing layer, an active layer, and a heat-resistant porous layer).
[0236] I. Method for producing separator for power storage device according to first embodiment
[0237] <Method for producing polyolefin substrate layer> A method for producing a polyolefin substrate layer may, for example, include the following steps: (1) Sheet forming process; (2) Stretching process; (3) a porous body forming step; and (4) Heat treatment process; The method for producing the polyolefin substrate layer may further include, if desired, a kneading step before the sheet forming step (1) and / or a winding and slitting step after the heat treatment step (3).
[0238] The kneading step is a step of kneading the raw material resin of the polyolefin substrate layer with, if desired, a plasticizer and / or an inorganic filler to obtain a kneaded product. The raw material resin of the polyolefin substrate layer can be the polyolefin resin described above. Kneading can be performed using a kneader. From the viewpoint of suppressing the generation of resin aggregates in the subsequent manufacturing process, it is preferable not to add a master batch resin containing a dehydration condensation catalyst to the kneaded product. As the plasticizer, for example, an organic compound that can form a uniform solution with polyolefin at a temperature below the boiling point can be used. More specifically, decalin, xylene, dioctyl phthalate, dibutyl phthalate, stearyl alcohol, oleyl alcohol, decyl alcohol, nonyl alcohol, diphenyl ether, n-decane, n-dodecane, and paraffin oil can be mentioned. Among these, paraffin oil and dioctyl phthalate are preferable. The plasticizer may be used alone or in combination of two or more kinds. The ratio of the plasticizer to the total mass of the polyolefin resin used is preferably 20% by mass or more from the viewpoint of the porosity of the resulting microporous film, and is preferably 90% by mass or less from the viewpoint of the viscosity during melt kneading.
[0239] The sheet forming process is a process in which the obtained kneaded product or a mixture of a polyolefin resin raw material and an optional plasticizer and / or inorganic filler is extruded, cooled and solidified, and molded into a sheet to obtain a sheet. The method of forming the sheet is not particularly limited, but for example, a method of compressing and cooling the molten product extruded after melt kneading to solidify it is included. The cooling method includes a method of directly contacting the product with a cooling medium such as cold air or cooling water, a method of contacting the product with a roll and / or a press machine cooled with a refrigerant, etc., and the method of contacting the product with a roll and / or a press machine cooled with a refrigerant is preferred in terms of excellent film thickness controllability.
[0240] From the viewpoint of suppressing the generation of resin aggregates in the polyolefin substrate layer, the mass ratio of the silane-modified polyolefin to the silane-unmodified polyolefin in the sheet forming step (mass of the silane-modified polyolefin / mass of the silane-unmodified polyolefin) is preferably 0.05 / 0.95 to 0.4 / 0.6, more preferably 0.06 / 0.94 to 0.38 / 0.62. The silane-unmodified polyolefin is preferably ultra-high molecular weight polyethylene (UHMWPE).
[0241] The stretching step is a step of stretching the obtained sheet in at least one direction to obtain a stretched product. If necessary, a plasticizer and / or an inorganic filler may be extracted from the sheet before stretching. Examples of the sheet stretching method include MD uniaxial stretching by a roll stretching machine, TD uniaxial stretching by a tenter, sequential biaxial stretching by a combination of a roll stretching machine and a tenter, or a combination of a tenter and a tenter, and simultaneous biaxial stretching by a simultaneous biaxial tenter or inflation molding. From the viewpoint of obtaining a more uniform film, simultaneous biaxial stretching is preferable. The areal magnification is preferably 8 times or more, more preferably 15 times or more, and even more preferably 20 times or more or 30 times or more, from the viewpoint of the uniformity of the film thickness, and the balance between the tensile elongation, the porosity, and the average pore size. By having an areal magnification of 8 times or more, it tends to be easy to obtain a film with high strength and good thickness distribution. The areal magnification may be 250 times or less from the viewpoint of preventing breakage.
[0242] The porous body forming step is a step of extracting the plasticizer and / or inorganic filler from the stretched product after the stretching step to make the stretched product porous and obtain a microporous membrane. Examples of the method of extracting the plasticizer include a method of immersing the stretched product in an extraction solvent and a method of showering the extraction solvent on the stretched product. The extraction solvent is not particularly limited, but is preferably a solvent that is a poor solvent for polyolefin and a good solvent for plasticizer and / or inorganic filler and has a boiling point lower than the melting point of polyolefin. Examples of such extraction solvents include hydrocarbons such as n-hexane and cyclohexane; halogenated hydrocarbons such as methylene chloride, 1,1,1-trichloroethane, and fluorocarbons; alcohols such as ethanol and isopropanol; ketones such as acetone and 2-butanone; and alkaline water. The extraction solvent may be used alone or in combination of two or more.
[0243] The heat treatment step is a step of heat treating the microporous membrane after the stretching step. If necessary, a plasticizer may be further extracted from the microporous membrane before the heat treatment. The heat treatment method is not particularly limited, but may be, for example, a heat setting method in which stretching and relaxation operations are performed using a tenter and / or a roll stretching machine. The relaxation operation refers to a reduction operation performed at a predetermined temperature and relaxation rate in the machine direction (MD) and / or transverse direction (TD) of the membrane. The relaxation rate refers to the value obtained by dividing the MD dimension of the membrane after the relaxation operation by the MD dimension of the membrane before the operation, or the value obtained by dividing the TD dimension of the membrane after the relaxation operation by the TD dimension of the membrane before the operation, or when both MD and TD are relaxed, the value obtained by multiplying the relaxation rate of MD and the relaxation rate of TD.
[0244] The winding and slitting step is a step in which the obtained microporous membrane is slit, if necessary, and wound around a predetermined core for ease of handling in the subsequent steps.
[0245] From the viewpoint of maintaining the crosslinking property until the polyolefin substrate layer comes into contact with the electrolyte, it is preferable that the manufacturing process of the polyolefin substrate layer does not include a crosslinking process. That is, the crosslinking process is preferably performed in the electricity storage device after the separator having the polyolefin substrate layer is incorporated into the electricity storage device. The crosslinking process is generally a process in which an object to be treated containing silane-modified polyolefin is brought into contact with a mixture of an organometallic catalyst and water, or is immersed in a base solution or an acid solution, and a silane dehydration condensation reaction is carried out to form an oligosiloxane bond. Examples of organometallic catalysts include di-butyltin-di-laurate, di-butyltin-di-acetate, and di-butyltin-di-octoate. The base solution means an alkaline solution having a pH of more than 7 and containing, for example, alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkali metal phosphates, ammonia, and amine compounds. The acid solution means an acidic solution having a pH of less than 7 and containing inorganic acids and / or organic acids.
[0246] Method for forming island structure In the manufacturing process of the polyolefin substrate layer, when the raw material is fed into the extruder in the sheet forming process, a certain concentration of alkali metal and / or alkaline earth metal compound is mixed into the raw material, so that an island structure of alkali metal and / or alkaline earth metal can be formed in the separator. However, when raw materials with significantly different molecular weights are used, it is difficult to uniformly disperse the alkali metal and / or alkaline earth metal compound in the resin raw material due to the difference in melt viscosity between the raw materials. Furthermore, in the case of melt mixing containing silane-modified polyolefin, dispersion is even more difficult due to the presence of units having heterofunctional groups. In such a complex mixed resin, the uniformity of the dispersion of the alkali metal and / or alkaline earth metal compound is improved by shear stirring using an extruder at a high rotation speed, but there is a problem that the F anion in the electrolyte is consumed more than necessary because the island structure is dispersed adjacently in fine particles. In addition, shear stirring using an extruder at a high rotation speed causes the molecular weight of the polyolefin to deteriorate, significantly impairing the mechanical strength and openability of the separator.
[0247] In order to control the construction of island structures without impairing mechanical strength and pore opening, it is preferable to use three kinds of polyolefin raw materials in total, namely, polyolefin raw materials with Mv=2 million to 9 million (raw material b) and Mv=500,000 to 2 million (raw material c), and silane-modified polyolefin raw material with Mv=20,000 to 150,000 (raw material a). More preferably, the content ratio is adjusted according to the molecular weight of each. This makes it possible to control the construction of island structures containing alkali metal and / or alkaline earth metal compounds with limited size and dispersity.
[0248] In the above raw material composition, it is preferable that the ratio of raw material a to the whole is 3 mass% to 70 mass%, and the ratio of raw materials b and c contained therein (mass of resin b / mass of resin c) is 0.06 mass% to 7.00 mass%.
[0249] Surface Treatment of Polyolefin Substrate Layer The microporous membrane obtained by the method including the various steps described above can be used as a polyolefin substrate layer of a separator for an electric storage device. It is preferable to subject the surface of the polyolefin substrate layer to a surface treatment, since it makes it easier to apply a coating liquid thereafter and improves the adhesion between the substrate layer and the coating layer. Examples of the surface treatment method include a corona discharge treatment method, a plasma treatment method, a mechanical roughening method, a solvent treatment method, an acid treatment method, and an ultraviolet oxidation method.
[0250] <Method of Forming Inorganic Particle Layer> The inorganic particle layer can be formed by applying a coating liquid containing inorganic particles and an optional resin binder in a solvent to a polyolefin substrate layer, and then removing the solvent. The solvent preferably includes a poor solvent such as water or a mixed solvent of water and a water-soluble organic medium (e.g., methanol or ethanol).
[0251] The coating method may be any method that can realize the desired coating pattern, coating thickness, and coating area, and examples thereof include die coating, curtain coating, impregnation coating, blade coating, rod coating, and gravure coating.
[0252] The method for removing the solvent from the coating film after coating may be any method that does not adversely affect the polyolefin substrate layer and the inorganic particle layer, such as a method of drying by heating at a temperature below the melting point of the substrate while fixing the substrate, or a method of drying under reduced pressure at a low temperature.
[0253] Method for forming thermoplastic polymer layer The thermoplastic polymer layer can be formed by applying a coating liquid containing a thermoplastic polymer in a solvent to the inorganic particle layer. When manufacturing a separator for an electricity storage device that does not have an inorganic particle layer, the coating liquid for the thermoplastic polymer layer may be directly applied onto the polyolefin substrate layer. The coating liquid may be prepared by synthesizing a thermoplastic polymer by emulsion polymerization, and the resulting emulsion may be used as it is as the coating liquid. The coating liquid preferably contains a poor solvent such as water or a mixed solvent of water and a water-soluble organic medium (e.g., methanol or ethanol).
[0254] The coating method may be any method that can realize the desired coating pattern, coating thickness, and coating area, and examples thereof include die coating, curtain coating, impregnation coating, blade coating, rod coating, and gravure coating.
[0255] The method for removing the solvent from the coating film after coating may be any method that does not adversely affect the polyolefin substrate layer, the inorganic particle layer, and the thermoplastic polymer layer, such as a method of drying by heating at a temperature below the melting point of the substrate while fixing the substrate, or a method of drying under reduced pressure at a low temperature.
[0256] II. Method for producing separator for power storage device according to second embodiment
[0257] <Method for producing a polyolefin microporous membrane as a substrate> As a method for producing a separator according to the second embodiment, the case where the polyolefin microporous membrane is a single-layer membrane (flat membrane) as a substrate will be described below, but it is not intended to exclude forms other than the flat membrane. The method for producing a microporous membrane includes the following steps: (1) Sheet forming process; (2) Stretching process; (3) a porous body forming step; and (4) Heat treatment process; The method for producing a microporous membrane may optionally include a resin modification step or a kneading step before the sheet forming step (1), and / or a winding and slitting step after the heat treatment step (3), but from the viewpoint of maintaining the crosslinking property of the microporous membrane until it is installed in an electricity storage device, it preferably does not include a crosslinked structure formation step or a contact step with a crosslinking-promoting catalyst.
[0258] The crosslinked structure forming step includes (1) a sub-step of condensing multiple functional groups contained in the microporous membrane, (2) a sub-step of reacting the functional groups contained in the microporous membrane with chemicals in the electricity storage device, or (3) a sub-step of reacting the functional groups contained in the microporous membrane with other functional groups. The crosslinking-promoting catalyst is any catalyst capable of promoting a crosslinking reaction, such as the above-described (I) condensation reaction of multiple identical functional groups, (II) reaction between multiple different functional groups, (III) chain condensation reaction between functional groups and an electrolyte, and (IV) chain condensation reaction between functional groups and an additive.
[0259] In the kneading step, for example, a polyolefin, and optionally other resins, and a plasticizer or inorganic material can be kneaded using a kneader. From the viewpoint of suppressing the generation of resin aggregates in the production process and maintaining the crosslinking property of the microporous membrane until it is housed in the electricity storage device, it is preferable not to add a masterbatch resin containing a crosslinking-promoting catalyst to the kneaded mixture.
[0260] The polyolefin subjected to the kneading step or the sheet forming step is not limited to an olefin homopolymer, but may be a polyolefin copolymerized with a monomer having a functional group, or a functional group-modified polyolefin. The functional group is a functional group capable of participating in the formation of a crosslinked structure, and may be, for example, the functional groups A and / or B in the reactions (I) to (V) described above. By preparing a polyolefin raw material containing a monomer unit having the functional groups A and / or B in advance, the resin modification step can be omitted.
[0261] On the other hand, if the polyolefin raw material does not have a functional group capable of participating in the formation of a crosslinked structure or the molar fraction of such a functional group is less than a predetermined ratio, the polyolefin raw material can be subjected to a resin modification process to incorporate a functional group into the resin backbone or increase the molar fraction of the functional group to obtain a functional group-modified polyolefin. The resin modification process can be carried out by a known method. For example, the polyolefin raw material can be contacted with a reaction reagent by liquid spraying, gas spraying, dry mixing, immersion, coating, etc., so that the functional groups A and / or B can be introduced into the polyolefin backbone.
[0262] The plasticizer is not particularly limited, but examples thereof include organic compounds that can form a uniform solution with polyolefin at a temperature below the boiling point. More specifically, decalin, xylene, dioctyl phthalate, dibutyl phthalate, stearyl alcohol, oleyl alcohol, decyl alcohol, nonyl alcohol, diphenyl ether, n-decane, n-dodecane, paraffin oil, etc. are included. Among these, paraffin oil and dioctyl phthalate are preferred. The plasticizer may be used alone or in combination of two or more. The ratio of the plasticizer is not particularly limited, but from the viewpoint of the porosity of the obtained microporous film, the polyolefin and the silane-grafted modified polyolefin are preferably 20% by mass or more based on the total mass as necessary, and from the viewpoint of the viscosity during melt kneading, it is preferably 90% by mass or less.
[0263] The sheet forming process is a process of extruding the obtained kneaded product or a mixture of polyolefin and plasticizer, cooling and solidifying it, and forming and processing it into a sheet to obtain a sheet. The method of forming the sheet is not particularly limited, but for example, a method of compressing and cooling the molten product extruded by melt kneading to solidify it. The cooling method includes a method of directly contacting the product with a cooling medium such as cold air or cooling water, a method of contacting the product with a roll or press cooled by a refrigerant, etc., and the method of contacting the product with a roll or press cooled by a refrigerant is preferred in terms of excellent film thickness controllability.
[0264] When a polyolefin copolymerized with a monomer having a functional group or a functional group-modified polyolefin is used in combination with another polyolefin, from the viewpoint of resin aggregates or maximum internal heat generation rate in the separator, the mass ratio (polyolefin copolymerized with a monomer having a functional group or a functional group-modified polyolefin / other polyolefin) in the sheet molding step is preferably 0.05-0.4 / 0.6-0.95, and more preferably 0.06-0.38 / 0.62-0.94.
[0265] From the viewpoint of improving safety by suppressing thermal runaway when the power storage device is destroyed while having low-temperature shutdown properties of 150°C or less and resistance to membrane rupture at high temperatures of 180 to 220°C, it is preferable that in the sheet molding process, the polyolefin copolymerized with a monomer having a functional group or the functional group-modified polyolefin is not a masterbatch resin that contains a catalyst that promotes the crosslinking reaction of the functional group before the sheet molding process.
[0266] The stretching step is a step of extracting a plasticizer or inorganic material from the obtained sheet as necessary, and further stretching the sheet in one or more directions. Examples of the sheet stretching method include MD uniaxial stretching by a roll stretching machine, TD uniaxial stretching by a tenter, sequential biaxial stretching by a combination of a roll stretching machine and a tenter or a tenter and a tenter, and simultaneous biaxial stretching by a simultaneous biaxial tenter or inflation molding. From the viewpoint of obtaining a more uniform film, simultaneous biaxial stretching is preferable. The total areal magnification is preferably 8 times or more, more preferably 15 times or more, and even more preferably 20 times or more or 30 times or more, from the viewpoint of the uniformity of the film thickness, the balance between the tensile elongation, the porosity, and the average pore size. By having a total areal magnification of 8 times or more, it tends to be easy to obtain a film with high strength and good thickness distribution. In addition, from the viewpoint of preventing breakage, this areal magnification may be 250 times or less.
[0267] The porous body forming step is a step of extracting a plasticizer from the stretched product after the stretching step to make the stretched product porous. The method of extracting the plasticizer is not particularly limited, but examples thereof include a method of immersing the stretched product in an extraction solvent and a method of showering the stretched product with the extraction solvent. The extraction solvent is not particularly limited, but for example, it is preferably a poor solvent for polyolefin and a good solvent for plasticizers or inorganic materials, and has a boiling point lower than the melting point of polyolefin. Such an extraction solvent is not particularly limited, but examples thereof include hydrocarbons such as n-hexane or cyclohexane; halogenated hydrocarbons such as methylene chloride or 1,1,1-trichloroethane, and fluorocarbons; alcohols such as ethanol or isopropanol; ketones such as acetone or 2-butanone; and alkaline water. The extraction solvent may be used alone or in combination of two or more types.
[0268] The heat treatment step is a step of extracting a plasticizer from the sheet as necessary after the stretching step, and further performing heat treatment to obtain a microporous membrane. The heat treatment method is not particularly limited, but examples include a heat setting method in which stretching and relaxation operations are performed using a tenter or roll stretching machine. The relaxation operation refers to a reduction operation performed at a predetermined temperature and relaxation rate in the machine direction (MD) and / or transverse direction (TD) of the membrane. The relaxation rate refers to the value obtained by dividing the MD dimension of the membrane after the relaxation operation by the MD dimension of the membrane before the operation, or the value obtained by dividing the TD dimension of the membrane after the relaxation operation by the TD dimension of the membrane before the operation, or when both MD and TD are relaxed, the value obtained by multiplying the relaxation rate of MD and the relaxation rate of TD.
[0269] <Winding / Slitting process / Post-processing process> The winding step is a step in which the obtained microporous membrane is slit, if necessary, and wound around a predetermined core.
[0270] It is preferable to subject the obtained polyolefin microporous membrane to a surface treatment, since this makes it easier to apply a coating liquid thereafter and improves the adhesion between the polyolefin and the surface layer. Examples of the surface treatment method include corona discharge treatment, plasma treatment, mechanical roughening, solvent treatment, acid treatment, and ultraviolet oxidation.
[0271] <Multi-layered substrate> As an example of the method for producing a multi-layer microporous polyolefin film, the production of a multi-layer film having a first microporous layer, a second microporous layer, and a first microporous layer in this order is described below. As a method for laminating these porous layers, for example, the following three-layer simultaneous lamination method can be mentioned: The polyolefin resin composition and the plasticizer, which are the components of the first and second microporous layers, are melt-kneaded separately using a twin-screw extruder to form an olefin solution, and then each polyolefin solution is fed from each twin-screw extruder to a three-layer T-die, and the layer thickness ratio of each layer (first polyolefin solution layer / second polyolefin solution layer / first polyolefin solution layer) formed from each solution is adjusted to a desired range, and the layer is cooled while being taken up at a predetermined take-up speed to form a gel-like three-layer sheet. In the above, a three-layer T-die is used to simultaneously laminate and form three layers, but it is also possible to form each layer separately and then form the three layers.
[0272] <Method of forming surface layer> The surface layer can be formed, for example, by applying a coating liquid containing the material for the surface layer to a polyolefin microporous membrane as a substrate and drying it. Alternatively, the polyolefin microporous membrane as a substrate and the membrane for the surface layer may be produced separately and then laminated together.
[0273] (Method of forming thermoplastic polymer-containing layer) The thermoplastic polymer can be disposed on the substrate, for example, by applying a coating liquid containing the thermoplastic polymer to the substrate. The thermoplastic polymer may be synthesized by emulsion polymerization, and the resulting emulsion may be used as the coating liquid as is. The coating liquid preferably contains a poor solvent such as water or a mixed solvent of water and a water-soluble organic medium (e.g., methanol or ethanol).
[0274] The method of coating the coating liquid containing thermoplastic polymer on the substrate of polyolefin microporous film is not particularly limited as long as it can realize the desired coating pattern, coating film thickness and coating area.For example, the coating method described above for coating the coating liquid containing inorganic particles may be used.From the viewpoint of high degree of freedom of the coating shape of thermoplastic polymer and easy adjustment of the preferred coverage area ratio as described above, gravure coater method or spray coating method is preferred.
[0275] The method for removing the solvent from the coating film after coating is not particularly limited as long as it does not adversely affect the substrate and the thermoplastic polymer-containing layer. For example, a method of drying the substrate at a temperature below its melting point while fixing the substrate, a method of drying under reduced pressure at a low temperature, a method of immersing the substrate in a poor solvent for the thermoplastic polymer to solidify the thermoplastic polymer into particles and simultaneously extract the solvent, etc. can be mentioned.
[0276] (Method of forming active layer) As a method for disposing or forming an active layer on a substrate, for example, a method of applying a coating liquid containing a fluorine-containing vinyl compound and inorganic particles to at least one side of the substrate can be mentioned. In this case, the coating liquid may contain a solvent, a dispersant, etc., in order to improve dispersion stability and coatability. The coating liquid may contain an organic solvent such as cyanoethyl polyvinyl alcohol or acetone, or may contain water, a mixed solvent of water and a water-soluble organic medium (e.g., methanol or ethanol), etc.
[0277] The method of applying the coating liquid to the substrate is not particularly limited as long as the required layer thickness and coating area can be realized. For example, a particle raw material containing a resin binder and a polymer substrate raw material may be laminated and extruded by a co-extrusion method, or the substrate and the active layer film may be prepared separately and then bonded together.
[0278] The method for removing the solvent from the coating film after coating is not particularly limited as long as it does not adversely affect the polyolefin resin, the fluorine-containing vinyl compound, or the inorganic particles. For example, a method of drying the coating film at a temperature below the melting point of the polyolefin resin or the fluorine-containing vinyl compound while fixing the substrate, a method of drying under reduced pressure at a low temperature, etc. can be mentioned.
[0279] (Method of forming a heat-resistant resin layer on a substrate) A method for forming a heat-resistant resin layer on a substrate can include, for example, a method of applying a coating liquid containing a heat-resistant resin and an inorganic filler to at least one side of the substrate. In this case, the coating liquid may contain a solvent, a dispersant, etc., in order to improve dispersion stability and coatability. The coating liquid may contain an organic solvent such as NMP, IPA, cyanoethyl polyvinyl alcohol, acetone, or may contain water, a mixed solvent of water and a water-soluble organic medium (e.g., methanol or ethanol), or the like.
[0280] The method of applying the coating liquid to the substrate is not particularly limited as long as the required layer thickness and coating area can be achieved. For example, a particle raw material containing a resin binder and a polymer substrate raw material may be laminated and extruded by a co-extrusion method, or the substrate and the heat-resistant resin layer may be separately prepared and then bonded together.
[0281] The method for removing the solvent from the coating film after coating is not particularly limited as long as it does not adversely affect the polyolefin resin, the heat-resistant resin, or the inorganic filler. For example, a method of drying the coating film at a temperature below the melting point of the polyolefin resin or the heat-resistant resin while fixing the substrate, a method of drying under reduced pressure at a low temperature, etc. can be mentioned.
[0282] The separator obtained by the method including the various steps described above can be used in an electrical storage device, in particular in a lithium battery or a lithium ion secondary battery.
[0283] <Electricity storage device> The electricity storage device of the present disclosure includes a positive electrode, a negative electrode, an electricity storage device separator of the present disclosure, a non-aqueous electrolyte, and an additive, if desired. The electricity storage device includes at least one electricity storage element including a positive electrode, a negative electrode, and an electricity storage device separator disposed therebetween. Typically, a plurality of positive electrodes and a plurality of negative electrodes are alternately stacked with the electricity storage device separator of the present disclosure interposed therebetween to form a plurality of electricity storage elements. The electricity storage elements are typically housed in an exterior body in a state of being impregnated with a non-aqueous electrolyte.
[0284] When the separator for an electricity storage device according to the present disclosure is housed in a device exterior, the functionally modified polyethylene or functionally grafted polyethylene reacts with chemicals contained in the electrolyte or additives to form a crosslinked structure, and the produced electricity storage device has a crosslinked structure. The functionally modified polyethylene or functionally grafted polyethylene may be derived from, but is not limited to, the polyolefin raw material of the microporous membrane, or may be derived from a polyolefin modified during the manufacturing process of the microporous membrane.
[0285] Specific examples of the power storage device of the present disclosure include lithium batteries, lithium secondary batteries, lithium ion secondary batteries, sodium secondary batteries, sodium ion secondary batteries, magnesium secondary batteries, magnesium ion secondary batteries, calcium secondary batteries, calcium ion secondary batteries, aluminum secondary batteries, aluminum ion secondary batteries, nickel hydrogen batteries, nickel cadmium batteries, electric double layer capacitors, lithium ion capacitors, redox flow batteries, lithium sulfur batteries, lithium air batteries, zinc air batteries, etc. Among these, from the viewpoint of practicality, lithium batteries, lithium secondary batteries, lithium ion secondary batteries, nickel hydrogen batteries, or lithium ion capacitors are preferred, and lithium batteries or lithium ion secondary batteries are more preferred.
[0286] A lithium-ion secondary battery (LIB) is a storage battery that uses a lithium-containing positive electrode, a negative electrode, and an electrolyte solution that contains an organic solvent containing a lithium salt such as LiPF6. A known LIB positive electrode can be used as the positive electrode. When a lithium-ion secondary battery is charged and discharged, ionized lithium travels back and forth between the electrodes. In addition, since the ionized lithium needs to travel between the electrodes relatively quickly while suppressing contact between the electrodes, a separator is placed between the electrodes.
[0287] Although the following description will be given taking a lithium ion secondary battery as an example, the power storage device of the present disclosure is not limited to this.
[0288] <Positive electrode> The positive electrode typically has a positive electrode current collector and a positive electrode active material layer disposed on one or both sides of the positive electrode current collector. The positive electrode active material layer contains a positive electrode active material and, if necessary, further contains a conductive assistant and / or a binder.
[0289] The positive electrode current collector is made of, for example, a metal foil such as an aluminum foil, a nickel foil, a stainless steel foil, etc. The positive electrode current collector may have a carbon coating on the surface, and may be processed into a mesh shape.
[0290] The positive electrode active material preferably contains a material capable of absorbing and releasing lithium ions. More specifically, the positive electrode active material may be, for example, a positive electrode active material containing at least one transition metal element selected from the group consisting of Ni, Mn, and Co. A positive electrode that is easily thermally decomposed or releases O2 may also be used, and is preferably at least one selected from the group consisting of nickel-manganese-cobalt (NMC)-based lithium-containing positive electrodes, olivine-type lithium iron phosphate (LFP)-based positive electrodes, lithium cobalt oxide (LCO)-based positive electrodes, nickel-cobalt-aluminum (NCA)-based lithium-containing positive electrodes, and lithium manganese oxide (LMO)-based positive electrodes. Nickel-manganese-cobalt (NMC)-based lithium composite oxides are preferable because they are capable of reversibly and stably absorbing and releasing lithium ions and can achieve high energy density. In the case of an NMC-based lithium composite oxide, the molar ratio of the amount of nickel (Ni) to the total amount of nickel, manganese, and cobalt is preferably 4-9, 5-9, 6-9, 5-8, or 6-8.
[0291] The positive electrode active material may be an olivine-type lithium iron phosphate (LFP)-based positive electrode. Olivine-type lithium iron phosphate has an olivine structure and is excellent in thermal stability, so it is often used at relatively high temperatures such as 60°C. However, ordinary separators that do not have a cross-linked structure have problems with cycle characteristics because they undergo creep deformation (deformation of the microporous structure) at 60°C. The separator having the cross-linked structure of the present disclosure can suppress creep deformation, so by using it in combination with an olivine-type lithium iron phosphate (LFP)-based positive electrode, it can be used in a temperature range where cycle characteristics have previously been a problem. The positive electrode active material may be a lithium cobalt oxide (LCO)-based positive electrode. The lithium cobalt oxide (LCO)-based positive electrode has a high oxidation potential, so the operating voltage of the battery can be increased. However, lithium cobalt oxide has a high hardness and tends to be easily mixed with foreign matter due to metal wear during the molding process. If metal foreign matter is mixed in during battery assembly, it may cause an internal short circuit. The separator having the crosslinked structure of the present disclosure has excellent fuse / meltdown characteristics, so that it can safely stop the electrochemical reaction even when an internal short circuit occurs. By using a combination of a lithium cobalt oxide (LCO)-based positive electrode and the separator of the present disclosure, it is possible to achieve both the operating voltage of the battery and safety during an internal short circuit. The positive electrode active material may be a nickel-cobalt-aluminum (NCA)-based lithium-containing positive electrode. By using a nickel-cobalt-aluminum (NCA)-based lithium-containing positive electrode, a battery with excellent charge / discharge capacity can be manufactured at low cost. However, there is a tendency that a trace amount of moisture contained in the battery reacts with Li ions eluted from the positive electrode to generate a lithium compound, and the lithium compound reacts with the electrolyte to generate gas. The generation of gas may cause battery swelling. In addition, the charge / discharge capacity may decrease due to the consumption of lithium ions eluted from the positive electrode. When the separator having the crosslinked structure of the present disclosure has an island structure of alkali metal / alkaline earth metal, the alkali metal / alkaline earth metal in the island structure reacts with HF, making it possible to control the HF concentration.One of the reactions that occurs in a battery is a reaction in which moisture reacts with an electrolyte salt such as LiPF6 to generate HF. By controlling the HF concentration in the battery, the reaction between moisture and the electrolyte salt can be promoted, and moisture can be consumed efficiently. By using a nickel-cobalt-aluminum (NCA)-based lithium-containing positive electrode in combination with the separator of the present disclosure, the decrease in charge / discharge capacity can be suppressed. The positive electrode active material may be a lithium manganese oxide (LMO)-based positive electrode. Lithium manganese oxide has a spinel structure (cubic crystal), so the crystal structure is strong, and it is thermally stable and safe, so it is used at relatively high temperatures such as 60°C. However, normal separators that do not have a cross-linked structure have creep deformation (thermal shrinkage) at 60°C, which has led to problems with cycle characteristics. The separator with the cross-linked structure of the present disclosure can suppress creep deformation, so by using it in combination with a lithium manganese oxide (LMO)-based positive electrode, it can be used even in temperature ranges where cycle characteristics have been a problem until now.
[0292] The positive electrode active material may be an olivine-type lithium iron phosphate (LFP)-based positive electrode, which is low-cost, has a long life, and is also excellent in safety. The positive electrode active material may be a lithium cobalt oxide (LCO)-based positive electrode, which has a high operating voltage and can achieve an excellent cycle life. The positive electrode active material may be a nickel-cobalt-aluminum (NCA)-based lithium-containing positive electrode, which has a layered structure and is excellent in balance of capacity density, cost, and thermal stability. The positive electrode active material may be a lithium manganese oxide (LMO)-based positive electrode, which has a spinel structure (cubic crystal), has a strong crystal structure, is thermally stable, and is excellent in safety.
[0293] Examples of the conductive assistant in the positive electrode active material layer include carbon black such as graphite, acetylene black, and Ketjen black, and carbon fiber, etc. The content of the conductive assistant is preferably 10 parts by mass or less, more preferably 1 to 5 parts by mass, per 100 parts by mass of the positive electrode active material.
[0294] Examples of the binder for the positive electrode active material layer include polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid, styrene butadiene rubber, and fluororubber. The content of the binder is preferably 6 parts by mass or less, more preferably 0.5 to 4 parts by mass, per 100 parts by mass of the positive electrode active material.
[0295] <Negative electrode> The negative electrode typically has a negative electrode current collector and a negative electrode active material layer disposed on one or both sides of the negative electrode current collector. The negative electrode active material layer contains a negative electrode active material and, if necessary, further contains a conductive assistant and / or a binder.
[0296] The negative electrode current collector is made of a metal foil such as copper foil, nickel foil, stainless steel foil, etc. The surface of the negative electrode current collector may be carbon-coated or processed into a mesh shape. The thickness of the negative electrode current collector is preferably 5 to 40 μm, more preferably 6 to 35 μm, and further preferably 7 to 30 μm.
[0297] The negative electrode active material is lithium ion at 0.4V (vs. Li / Li + ) is preferably contained. More specifically, examples of the negative electrode active material include amorphous carbon (hard carbon), graphite (artificial graphite, natural graphite), pyrolytic carbon, coke, glassy carbon, baked body of organic polymer compound, mesocarbon microbeads, carbon fiber, activated carbon, carbon colloid, and carbon black, as well as metal lithium, metal oxides, metal nitrides, lithium alloys, tin alloys, Si materials, intermetallic compounds, organic compounds, inorganic compounds, metal complexes, organic polymer compounds, and the like. The negative electrode active material is used alone or in combination of two or more. Examples of the Si material include silicon, Si alloys, and Si oxides.
[0298] Examples of the conductive assistant in the negative electrode active material layer include carbon black such as graphite, acetylene black, and ketjen black, and carbon fiber. The content of the conductive assistant is preferably 20 parts by mass or less, more preferably 0.1 to 10 parts by mass, per 100 parts by mass of the negative electrode active material.
[0299] Examples of the binder for the negative electrode active material layer include carboxymethyl cellulose, polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), polyacrylic acid, and fluororubber. Also includes diene rubber, such as styrene butadiene rubber. The content of the binder is preferably 10 parts by mass or less, more preferably 0.5 to 6 parts by mass, per 100 parts by mass of the negative electrode active material.
[0300] <Separator for Electricity Storage Device> As the separator for an electricity storage device, the separator for an electricity storage device according to the present disclosure can be used.
[0301] <Electrolyte> The electrolyte in the battery may contain water, and the water contained in the system after the battery is produced may be water contained in the electrolyte, or water carried in from components such as electrodes or separators. The electrolyte may contain a non-aqueous solvent. Examples of the solvent contained in the non-aqueous solvent include alcohols such as methanol and ethanol; aprotic solvents, etc. Among them, aprotic solvents are preferred as the non-aqueous solvent.
[0302] Examples of aprotic solvents include cyclic carbonates, fluoroethylene carbonates, lactones, organic compounds having sulfur atoms, chain fluorinated carbonates, cyclic ethers, mononitriles, alkoxy group-substituted nitriles, dinitriles, cyclic nitriles, short-chain fatty acid esters, chain ethers, fluorinated ethers, ketones, and compounds in which some or all of the H atoms of the above aprotic solvents have been substituted with halogen atoms.
[0303] Examples of cyclic carbonates include ethylene carbonate, propylene carbonate, 1,2-butylene carbonate, trans-2,3-butylene carbonate, cis-2,3-butylene carbonate, 1,2-pentylene carbonate, trans-2,3-pentylene carbonate, cis-2,3-pentylene carbonate, vinylene carbonate, 4,5-dimethylvinylene carbonate, and vinylethylene carbonate.
[0304] Examples of fluoroethylene carbonate include 4-fluoro-1,3-dioxolan-2-one, 4,4-difluoro-1,3-dioxolan-2-one, cis-4,5-difluoro-1,3-dioxolan-2-one, trans-4,5-difluoro-1,3-dioxolan-2-one, 4,4,5-trifluoro-1,3-dioxolan-2-one, 4,4,5,5-tetrafluoro-1,3-dioxolan-2-one, and 4,4,5-trifluoro-5-methyl-1,3-dioxolan-2-one.
[0305] Examples of lactones include γ-butyrolactone, α-methyl-γ-butyrolactone, γ-valerolactone, γ-caprolactone, δ-valerolactone, δ-caprolactone, and ε-caprolactone.
[0306] Examples of organic compounds having a sulfur atom include ethylene sulfite, propylene sulfite, butylene sulfite, pentene sulfite, sulfolane, 3-sulfolene, 3-methylsulfolane, 1,3-propane sultone, 1,4-butane sultone, 1-propene 1,3-sultone, dimethyl sulfoxide, tetramethylene sulfoxide, and ethylene glycol sulfite.
[0307] Examples of the chain carbonate include ethyl methyl carbonate, dimethyl carbonate, diethyl carbonate, methyl propyl carbonate, methyl isopropyl carbonate, dipropyl carbonate, methyl butyl carbonate, dibutyl carbonate, and ethyl propyl carbonate.
[0308] Examples of cyclic ethers include tetrahydrofuran, 2-methyltetrahydrofuran, 1,4-dioxane, and 1,3-dioxane.
[0309] Examples of mononitriles include acetonitrile, propionitrile, butyronitrile, valeronitrile, benzonitrile, and acrylonitrile.
[0310] Examples of alkoxy-substituted nitriles include methoxyacetonitrile and 3-methoxypropionitrile.
[0311] Examples of dinitriles include malononitrile, succinonitrile, methylsuccinonitrile, glutaronitrile, 2-methylglutaronitrile, adiponitrile, 1,4-dicyanoheptane, 1,5-dicyanopentane, 1,6-dicyanohexane, 1,7-dicyanoheptane, 2,6-dicyanoheptane, 1,8-dicyanooctane, 2,7-dicyanooctane, 1,9-dicyanonane, 2,8-dicyanononane, 1,10-dicyanodecane, 1,6-dicyanodecane, 2,4-dimethylglutaronitrile, and ethylene glycol bis(propionitrile) ether.
[0312] Examples of cyclic nitriles include benzonitrile.
[0313] Examples of short-chain fatty acid esters include methyl acetate, methyl propionate, methyl isobutyrate, methyl butyrate, methyl isovalerate, methyl valerate, methyl pivalate, methyl hydroangelate, methyl caproate, ethyl acetate, ethyl propionate, ethyl isobutyrate, ethyl butyrate, ethyl isovalerate, ethyl valerate, ethyl pivalate, ethyl hydroangelate, ethyl caproate, propyl acetate, propyl propionate, propyl isobutyrate, propyl butyrate, propyl isovalerate, propyl valerate, propyl pivalate, propyl hydroangelate, propyl caproate, isopropyl acetate, isopropyl propionate, isopropyl isobutyrate, isopropyl butyrate, isopropyl isovalerate, isopropyl valerate, and isopropyl pivalate. , isopropyl hydroangelate, isopropyl caproate, butyl acetate, butyl propionate, butyl isobutyrate, butyl butyrate, butyl isovalerate, butyl valerate, butyl pivalate, butyl hydroangelate, butyl caproate, isobutyl acetate, isobutyl propionate, isobutyl isobutyrate, isobutyl butyrate, isobutyl isovalerate, isobutyl valerate, isobutyl pivalate, isobutyl hydroangelate, isobutyl caproate, tert-butyl acetate, tert-butyl propionate, tert-butyl isobutyrate, tert-butyl butyrate, tert-butyl isovalerate, tert-butyl valerate, tert-butyl pivalate, tert-butyl hydroangelate, and tert-butyl caproate.
[0314] Examples of the chain ether include dimethoxyethane, diethyl ether, 1,3-dioxolane, diglyme, triglyme, and tetraglyme. Examples of the fluorinated ether include those represented by the general formula Rf aa -OR bb (In the formula, Rf aa is an alkyl group containing a fluorine atom, and R bb is an organic group which may contain a fluorine atom). Examples of the ketone include acetone, methyl ethyl ketone, and methyl isobutyl ketone.
[0315] Examples of the above-mentioned aprotic solvent compounds in which some or all of the H atoms have been substituted with halogen atoms include compounds in which the halogen atoms are fluorine.
[0316] Here, examples of fluorinated chain carbonates include methyl trifluoroethyl carbonate, trifluorodimethyl carbonate, trifluorodiethyl carbonate, trifluoroethylmethyl carbonate, methyl 2,2-difluoroethyl carbonate, methyl 2,2,2-trifluoroethyl carbonate, and methyl 2,2,3,3-tetrafluoropropyl carbonate. The above-mentioned fluorinated chain carbonates are represented by the following general formula: R cc -OC(O)OR dd {where, R cc and R dd is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and the formula CH2Rf ee (In the formula, Rf ee is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom), and R cc and / or R dd contains at least one fluorine atom.}
[0317] Examples of fluorinated short-chain fatty acid esters include fluorinated short-chain fatty acid esters such as 2,2-difluoroethyl acetate, 2,2,2-trifluoroethyl acetate, and 2,2,3,3-tetrafluoropropyl acetate. Fluorinated short-chain fatty acid esters are represented by the following general formula: R ff -C(O)OR gg {where, R ff is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, CF3CF2H, CFH2, CF2H, CF2Rf hh , CFHRf hh , and CH2Rf iiand R is at least one selected from the group consisting of gg is CH3, CH2CH3, CH2CH2CH3, CH(CH3)2, and CH2Rf ii Rf is at least one selected from the group consisting of hh is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom may be substituted with at least one fluorine atom, and Rf ii is an alkyl group having 1 to 3 carbon atoms in which a hydrogen atom is substituted with at least one fluorine atom, and R ff and / or R gg contains at least one fluorine atom, and R ff If is CF2H, R gg can be expressed as {is not CH3}.
[0318] In the present specification, the non-aqueous electrolyte refers to an electrolyte solution containing an electrolyte in a non-aqueous solvent, and the amount of water is 1 mass% or less based on the total mass. The non-aqueous electrolyte solution preferably contains as little water as possible, but may contain a very small amount of water. The content of such water is preferably 300 mass ppm or less, more preferably 200 mass ppm or less, based on the total amount of the non-aqueous electrolyte solution.
[0319] Examples of non-aqueous solvents include alcohols such as methanol and ethanol, and aprotic solvents, and aprotic solvents are preferred. Examples of aprotic solvents include acetonitrile, mononitriles other than acetonitrile, alkoxy-substituted nitriles, dinitriles, cyclic nitriles, chain carbonates, cyclic carbonates, fluorinated carbonates, fluoroethylene carbonates, short-chain fatty acid esters, lactones, ketones, organic compounds having sulfur atoms, chain ethers, cyclic ethers, fluorinated ethers, and compounds in which some or all of the H atoms of these are substituted with halogen atoms.
[0320] The electrolyte is preferably a lithium salt, and from the viewpoint of promoting the silane crosslinking reaction, a fluorine-containing lithium salt that generates HF is more preferable. Examples of fluorine-containing lithium salts include lithium hexafluorophosphate (LiPF6), lithium fluorosulfonate (LiFSO3), lithium bis(trifluoromethanesulfonyl)imide (LiN(SO2CF3)2), lithium bis(fluorosulfonyl)imide (LiN(SO2F)2), lithium borofluoride (LiBF4), and lithium bisoxalate borate (LiBC4O8). Without being bound by theory, for example, when the electrolyte contains LiPF6, LiPF6 reacts with a small amount of moisture (moisture contained in components such as electrodes, separators, and electrolyte) contained in the power storage device to generate hydrogen fluoride (HF) or fluorine-containing organic substances derived from HF. It is believed that these HF or fluorine-containing organic substances derived from HF dissolve in the electrolyte and swell and diffuse into the amorphous part of the polyolefin having a crosslinkable silane group, thereby catalyzing the silane crosslinking reaction.
[0321] The non-aqueous electrolyte may contain, in addition to the above, an acid source such as an inorganic acid or an organic acid, and an alkali source as a substance that catalyzes the silane crosslinking reaction. Examples of the alkali source include alkali metal hydroxides, alkaline earth metal hydroxides, alkali metal carbonates, alkali metal phosphates, ammonia, and amine compounds. Among these, from the viewpoints of the safety of the power storage device and the silane crosslinking property, alkali metal hydroxides or alkaline earth metal hydroxides are preferred, alkali metal hydroxides are more preferred, and sodium hydroxide is even more preferred.
[0322] <Exterior body> The exterior body can be a known exterior body, for example, a battery can or a laminate film exterior body. As the battery can, for example, a metal can made of steel, stainless steel, aluminum, or a clad material can be used. The laminate film exterior body can be used as an exterior body by stacking two sheets with the heat-melting resin side facing inward, or by folding the laminate film exterior body so that the heat-melting resin side faces inward, and sealing the ends by heat sealing. When using a laminate film exterior body, a positive electrode lead body (or a lead tab connected to a positive electrode terminal and a positive electrode terminal) may be connected to a positive electrode current collector, and a negative electrode lead body (or a lead tab connected to a negative electrode terminal and a negative electrode terminal) may be connected to a negative electrode current collector. In this case, the laminate film exterior body may be sealed in a state in which the ends of the positive electrode lead body and the negative electrode lead body (or the lead tabs connected to the positive electrode terminal and the negative electrode terminal, respectively) are drawn out to the outside of the exterior body. More specifically, as the laminate film exterior body, for example, a laminate film having a three-layer structure of a heat-melting resin / metal film / resin can be used. The metal film is preferably an aluminum foil, and the resin material on both sides is preferably a polyolefin resin.
[0323] Additives When included, the additive may be, for example, at least one selected from the group consisting of a dehydration condensation catalyst, a metal soap such as calcium stearate or zinc stearate, an ultraviolet absorber, a light stabilizer, an antistatic agent, an antifogging agent, and a color pigment.
[0324] <Electricity storage device assembly kit> The electricity storage device assembly kit of the present disclosure includes (A) an exterior body housing a laminate or wound body of electrodes and an electricity storage device separator of the present disclosure; and (B) a container housing a non-aqueous electrolyte. The laminate or wound body includes at least one electricity storage element having a positive electrode, a negative electrode, and an electricity storage device separator disposed between them. Typically, multiple positive electrodes and multiple negative electrodes are alternately stacked with the electricity storage device separator of the present disclosure interposed therebetween to form multiple electricity storage elements. For details of each component, please refer to the "Electricity storage device" section above.
[0325] The separator for an electricity storage device can be assembled by removing the nonaqueous electrolyte from the container in which it is stored and injecting it into the exterior body. The form of the container in which the nonaqueous electrolyte is stored is not limited as long as the nonaqueous electrolyte can be stored until the separator for an electricity storage device is assembled. After the separator for an electricity storage device is assembled, the container in which the nonaqueous electrolyte was stored may be discarded or may be reused in the manufacture of another kit.
[0326] When using the electricity storage device assembly kit, a cross-linked structure is formed in the separator by contacting the separator in element (A) with the non-aqueous electrolyte in element (B) and contacting the electrolyte with the laminate or wound body within the exterior body, and / or by continuing the charge / discharge cycle of the assembled electricity storage device, thereby forming an electricity storage device that is both safe and has high output.
[0327] Without wishing to be bound by theory, it is believed that when the electrolyte or electrolyte solution comes into contact with the electrodes and / or when the power storage device is charged and discharged, a substance that catalyzes the crosslinking reaction or a substance having a functional group that becomes part of the crosslinked structure is present in the electrolyte solution, on the inner surface of the exterior body, or on the surface of the electrodes, and dissolves in the electrolyte solution and uniformly swells and diffuses into the amorphous part of the polyolefin, thereby uniformly promoting the crosslinking reaction of the separator-containing laminate or wound body. The substance that catalyzes the crosslinking reaction may be in the form of an acid solution or film, and when the electrolyte contains lithium hexafluorophosphate (LiPF6), it can be hydrogen fluoride (HF) or a fluorine-containing organic substance derived from hydrogen fluoride (HF). The substance having a functional group that becomes part of the crosslinked structure can be, for example, a compound having the functional groups A and / or B described above, the electrolyte solution itself, various additives, etc.
[0328] From the viewpoint of promoting the cross-linking reaction of the separator, the nonaqueous electrolyte stored in element (2) is preferably a fluorine (F)-containing lithium salt such as LiPF6 that generates HF, or an electrolyte having an unshared electron pair such as LiN(SO2CF3)2 or LiSO3CF3, or alternatively LiBF4, LiBC4O8 (LiBOB), etc.
[0329] In order to promote the crosslinking reaction of the separator, the electricity storage device assembly kit may include, as an accessory (or element (C)), a separate container for containing a catalyst for promoting the crosslinking reaction, such as a mixture of an organometallic catalyst and water, an acid solution, a base solution, or the like.
[0330] <<Method for manufacturing an electricity storage device>> In a first embodiment, a method for producing an electricity storage device according to the present disclosure includes, for example, the following steps: (i) a preparation step of preparing an exterior body housing a laminate or a wound body of electrodes and a separator for an electricity storage device according to the present disclosure, and a nonaqueous electrolyte; (ii) a step of pouring a non-aqueous electrolyte into the exterior body; (iii) optionally, a terminal connecting step of connecting a lead terminal to an electrode inside the exterior body or to an electrode exposed from the exterior body; (iv) optionally, a charge / discharge step of performing at least one charge / discharge cycle; The steps (i) to (iv) can be carried out by methods known in the art, except for using the separator for an electricity storage device of the present disclosure. In the steps (i) to (iv), the electrodes and nonaqueous electrolyte solution described in the section "Electricity storage device" can be used, and a positive electrode, a negative electrode, an electrolyte solution, an exterior body, and a charge / discharge device known in the art can also be used.
[0331] It is preferable to bring the separator into contact with the non-aqueous electrolyte in step (ii) to initiate the silane crosslinking reaction of the silane-modified polyolefin. From the viewpoint of ensuring the progress of the silane crosslinking reaction of the separator, it is preferable to carry out steps (iii) and (iv). Without being bound by theory, it is believed that a substance that catalyzes the silane crosslinking reaction is generated in the electrolyte or on the electrode surface by the charge-discharge cycle, which allows the silane crosslinking reaction to proceed more efficiently.
[0332] In the second embodiment, the method for producing an electricity storage device may include the following steps: (1) a crosslinking step in which functional groups are condensed with each other, (2) a functional group is reacted with a chemical substance inside the electricity storage device, or (3) a functional group of the polyolefin is reacted with another type of functional group to form a crosslinked structure, using a separator containing a polyolefin having one or more types of functional groups. The crosslinking step may be carried out in the same manner as the reaction for forming the crosslinked structure of the separator described above. In addition, the crosslinking step may be carried out by utilizing the compounds in the electricity storage device and the environment around the device, and therefore does not require excessive conditions such as electron beams or high temperatures of 100°C or higher, and may employ mild conditions such as a temperature of 5°C to 90°C and / or ambient atmosphere.
[0333] By carrying out a crosslinking step in the manufacturing process of an electricity storage device, it is possible to omit the formation of a crosslinked structure during or immediately after the separator film-forming process, and it is possible to alleviate or eliminate stress distortion after the production of an electricity storage device, and / or to impart a crosslinked structure to the separator without using relatively high energy such as light irradiation or heating, thereby reducing uneven crosslinking, the occurrence of unmelted resin aggregates, and the burden on the environment.
[0334] During the crosslinking process, (2) functional groups are reacted with chemicals inside the electricity storage device, or (3) functional groups of the polyolefin are reacted with other types of functional groups, thereby forming crosslinked structures not only inside the separator, but also between the separator and the electrodes or between the separator and the solid electrolyte interface (SEI), thereby improving the strength between multiple components of the electricity storage device.
[0335] In the method for producing an electricity storage device according to the present disclosure, the electricity storage device assembly kit described above can be used. In that case, the method for producing an electricity storage device according to the present disclosure includes the following steps: (i) preparing the above-described electricity storage device assembly kit; (ii) combining element (A) and element (B) of the electricity storage device assembly kit, (1) causing a condensation reaction between functional groups of the polyolefin contained in the separator, (2) causing the functional groups to react with chemicals inside the electricity storage device, or (3) causing the functional groups to react with other types of functional groups; (iii) optionally connecting lead terminals to the electrodes of element (A); (iv) optionally performing at least one charge / discharge cycle; Steps (i) to (iv) can be carried out by methods known in the art, except for using a separator for an electricity storage device, and steps (i) to (iv) can use a positive electrode, a negative electrode, an electrolyte, an exterior body, and a charge / discharge device known in the art.
[0336] From the viewpoint of reliably carrying out the crosslinking reaction of the separator during or after step (ii), it is preferable to carry out steps (iii) and (iv). It is considered that a substance that catalyzes the crosslinking reaction or a substance having a functional group that becomes part of the crosslinked structure is generated in the electrolyte, on the inner surface of the exterior body, or on the surface of the electrode by the charge-discharge cycle, thereby achieving the crosslinking reaction.
[0337] The separator for an electricity storage device according to the present disclosure forms a cross-linked structure when housed in an electricity storage device, and therefore can be adapted to a conventional electricity storage device manufacturing process while causing a cross-linking reaction after device manufacturing to improve the safety of the electricity storage device. Examples of safety include a reduction in the possibility of thermal runaway due to a local short circuit, improved safety in a nail penetration test, improved thermal shrinkage and hot box test properties, and improved high-temperature bar impact destruction test properties.
[0338] The electricity storage device, particularly the LIB, manufactured as described above includes the separator according to this embodiment, and therefore can have improved safety, such as reduced possibility of thermal runaway due to local short circuit, improved safety in nail penetration tests, improved thermal shrinkage and hot box test properties, and improved high-temperature bar impact destruction test properties. EXAMPLES
[0339] Measurement and evaluation methods Regarding the evaluation method of the separator described below, TOF-SIMS analysis and image processing, detection of silane-modified polyolefin contained in the separator, weight average molecular weight, viscosity average molecular weight, melt mass flow rate, basis weight of the polyolefin base layer, film thickness of the polyolefin base layer, puncture strength, basis weight equivalent puncture strength and porosity were measured by removing the coating film (inorganic particle layer and thermoplastic polymer layer) from each separator, immersing the separator in a non-aqueous electrolyte for one week, and washing the separator with methylene chloride before evaluation. Regarding the 150°C heat shrinkage rate, 150°C heat shrinkage rate in the electrolyte, thermal response index, film thickness, air permeability, powder falling property, FUSE temperature, and SHORT temperature, each separator was immersed in a non-aqueous electrolyte for one week, and the separator was washed with methylene chloride before evaluation. Regarding the electrode remaining rate, battery cycle test capacity retention rate, and battery crush test, a single-layer laminate type non-aqueous secondary battery was prepared using each separator and evaluated.
[0340] <Method for detecting silane-modified polyolefin contained in separator> In a crosslinked state, the silane-modified polyolefin contained in the separator is insoluble or has insufficient solubility in organic solvents, so that it may be difficult to measure the content of the silane-modified polyolefin directly from the separator. In such a case, the siloxane bond is decomposed to methoxysilanol using methyl orthoformate, which does not cause side reactions, as a pretreatment of the sample, and then the solution NMR measurement is performed to detect the silane-modified polyolefin contained in the separator or to perform GPC measurement. The pretreatment experiment can be performed with reference to Patent No. 3529854 and Patent No. 3529858. Specifically, the silane-modified polyolefin as a raw material used in the production of the separator can be measured by the following method. 1 H or 13 C-NMR identification can be used to detect the silane-modified polyolefin contained in the separator. 1 H and 13 An example of a C-NMR measurement technique is described below.
[0341] ( 1 H-NMR measurement) The sample was dissolved in o-dichlorobenzene-d4 at 140°C, and the proton resonance frequency was 600 MHz. 1 Obtain H-NMR spectra. 1 The H-NMR measurement conditions are as follows. Equipment: Bruker AVANCE NEO 600 Sample tube diameter: 5mmφ Solvent: o-dichlorobenzene-d4 Measurement temperature: 130℃ Pulse angle: 30° Pulse waiting time: 1sec Number of times: 1000 or more Sample concentration: 1 wt / vol%
[0342] ( 13 C NMR measurement) The sample was dissolved in o-dichlorobenzene-d4 at 140°C. 13 Obtain a C-NMR spectrum. 13 The measurement conditions for C-NMR are as follows: Equipment: Bruker AVANCE NEO 600 Sample tube diameter: 5mmφ Solvent: o-dichlorobenzene-d4 Measurement temperature: 130℃ Pulse angle: 30° Pulse waiting time: 5sec Accumulation count: 10,000 times or more Sample concentration: 10 wt / vol%
[0343] 1 H and / or 13 By C-NMR measurement, it is possible to confirm the amount of silane unit modification in the silane-modified polyolefin and the amount of alkyl group modification in the polyolefin in the polyolefin raw material, and to identify the content of silane-modified polyolefin in the separator (-CH2-Si: 1 H, 0.69 ppm, t; 13 C, 6.11 ppm, s) is possible.
[0344] <Weight average molecular weight (Mw)> A calibration curve was created by measuring standard polystyrene under the following conditions using a Waters ALC / GPC 150C (trademark). Chromatograms were also measured under the same conditions for each of the following polymers, and the weight-average molecular weight of each polymer was calculated based on the calibration curve by the following method. Column: Tosoh GMH6-HT (trademark) x 2 + GMH6-HTL (trademark) x 2 Mobile phase: o-dichlorobenzene Detector: Differential refractometer Flow rate: 1.0ml / min Column temperature: 140℃ Sample concentration: 0.1wt% (Weight average molecular weight (Mw) of polyethylene) Each molecular weight component in the obtained calibration curve was multiplied by 0.43 (Q factor of polyethylene / Q factor of polystyrene=17.7 / 41.3) to obtain a molecular weight distribution curve converted into polyethylene, and the weight average molecular weight was calculated. (Weight average molecular weight (Mw) of resin composition) The weight average molecular weight was calculated using the Q factor value of the polyolefin with the largest mass fraction, and otherwise in the same manner as in the case of polyethylene.
[0345] <Viscosity average molecular weight (Mv)> Based on ASTM-D4020, the intrinsic viscosity [η] in decalin solvent at 135°C was determined. The Mv of polyethylene was calculated using the following formula. [η]=6.77×10 -4 Mv 0.67
[0346] <Melt mass flow rate (MFR) (g / 10min)> Using a melt mass flow rate measuring instrument (Melt Indexer F-F01) manufactured by Toyo Seiki Seisakusho, the weight of the resin extruded in 10 minutes under conditions of 190° C. and a load of 2.16 kg was determined as the MFR value.
[0347] TOF-SIMS analysis and image processing A TOF-SIMS analysis was carried out on the separator for the power storage device. The TOF-SIMS mass spectrometer used was a nano-TOF (TRIFTV) manufactured by ULVAC-PHI, Inc. The analysis conditions were as follows, and calcium ions (corresponding to positive ions with m / z=40) were detected. [Image measurement conditions] Primary ion: Bismuth (Bi1 + ) Acceleration voltage: 30 kV Ion current: Approx. 0.5nA (as DC) Bunching present Analysis area: 100μm x 100μm Analysis time: 90 minutes Detected ion: positive ion (m / z=40) Neutralization: Electron gun + Ar monomer ion Vacuum degree: approx. 5.0×10 -5 Pa [Depth direction measurement conditions] Analysis conditions Primary ion: Bismuth (Bi1 +) Acceleration voltage: 30 kV Ion current: Approx. 1.2nA (as DC) Bunching present Analysis area: 100μm x 100μm Analysis time: 5 frames / cycle Detected ion: positive ion (m / z=40) Neutralization: Electron gun + Ar monomer ion Vacuum degree: approx. 5.0×10 -5 Pa Sputtering conditions Sputter ion: GCIB (Ar 2500 + ) Acceleration voltage: 20 kV Ion current: approx. 5nA Sputtering area: 400μm×400μm Sputtering time: 30 seconds / cycle Neutralization: Electron gun + Ar monomer ion
[0348] The TOF-SIMS spectrum image data obtained as described above was subjected to image processing according to the following procedure. (1) Create a filter that matches the beam shape (diameter 2 μm, pixel resolution 0.39 μm). The filter value is calculated using the fspecial function in the Image Processing Toolbox of the numerical calculation software MATLAB made by Mathworks. fspecial(``gaussian'',
[1313] ,1.69865) (2) Apply the created filter to the two-dimensional data. (3) Calculate the mean and standard deviation of the two-dimensional data after applying the filter. (4) Binarize using the mean + standard deviation × 3 as the threshold value. However, in the case of a normal distribution, 99.74% of the values fall within the range of mean + standard deviation × 3, so the intention is to extract numerically anomalous parts. (5) Dilation and contraction of 7 pixels are performed to connect adjacent extracted regions. (6) Remove small areas (less than 50 pixels). (7) Calculate the parameters of each remaining region. Extraction area (pixels), simple center of gravity position (x0, y0) The maximum value in the region, the average value in the region, and the weighted center of gravity (x m ,y m ) (8) Calculate the distance between each weighted center of gravity position. The calculation was performed using the WeightedCentroid option of the regionprops function in the Image Processing Toolbox of the numerical calculation software MATLAB manufactured by Mathworks. regionprops(cc,I,'WeightedCentroid') Here, cc is a variable indicating the extracted region, and I is a variable storing the two-dimensional data after the filter is applied. Through the above processing, the calcium ion island structures were identified, and the number, size, and distance between the weighted center of gravity positions were calculated.
[0349] <Heat shrinkage rate at 150℃ (%)> A sample piece of 100 mm TD x 100 mm MD taken from the separator for the power storage device was left in an oven at 150°C for 1 hour. The sample piece was sandwiched between two pieces of paper so that the hot air would not directly hit the sample piece. The sample piece was removed from the oven and cooled, after which the area of the sample piece was measured and the 150°C heat shrinkage rate was calculated using the following formula. 150℃ heat shrinkage rate (%) = {(10,000(mm 2 )-Area of the sample piece after heating (mm 2 )) / 10,000(mm 2 )}×100
[0350] <Preparation of non-aqueous electrolyte> A nonaqueous electrolyte solution was prepared by adding 0.3 mol / L lithium hexafluorophosphate (LiPF6), 1 mol / L lithium bis(fluorosulfonyl)imide (LiN(SO2F)2), and 20 mass ppm lithium fluorosulfonate (LiFSO3) as electrolytes to a mixed solution of 5 vol% acetonitrile, 62.5 vol% ethyl methyl carbonate, 30 vol% ethylene carbonate, and 2.5 vol% vinylene carbonate.
[0351] <Heat shrinkage rate at 150℃ in electrolyte (%)> A sample piece of 100 mm TD×100 mm MD taken from the separator for an electricity storage device was placed in an aluminum pack, and the nonaqueous electrolyte was poured into the pack until the sample piece was completely immersed, and the pack was left standing for one week. The pack was then left standing for one hour in an oven at 150° C. The sample piece was removed from the oven and cooled, after which the area of the sample piece was measured, and the 150° C. heat shrinkage in the electrolyte was calculated using the following formula. Thermal shrinkage rate at 150°C in electrolyte (%) = {(10,000(mm 2 )-Area of the sample piece after heating (mm 2 )) / 10,000(mm 2 )}×100
[0352] <Film thickness (μm)> The thickness of the separator for the electric storage device was measured at room temperature of 23±2°C and relative humidity of 60% using a micro thickness gauge, KBM (trademark) manufactured by Toyo Seiki. Specifically, the thickness was measured at five points at approximately equal intervals over the entire width in the TD direction, and the average value was obtained. The thickness of the polyolefin substrate layer (in the table, "substrate layer thickness") was measured by removing the coating film (inorganic particle layer and thermoplastic polymer layer) from the separator for the electric storage device. The thickness of the inorganic particle layer was calculated by removing the thermoplastic polymer layer from the separator for the electric storage device, measuring the thickness (thickness of the polyolefin substrate layer and inorganic coating layer), and further subtracting the thickness of the polyolefin substrate layer from the thickness of the polyolefin substrate layer and the inorganic coating layer. The thickness of the thermoplastic polymer layer was calculated by subtracting the thickness of the polyolefin substrate layer and the inorganic coating layer from the thickness of the separator for the electric storage device.
[0353] <Air permeability (sec / 100cm 3 )〉 In accordance with JIS P-8117 (2009), the volume of the separator for the power storage device was measured using a Gurley-type air permeability meter, G-B2 (trademark) manufactured by Toyo Seiki Co., Ltd. 3 The air permeability was measured.
[0354] <Porosity (%)> A sample measuring 10 cm x 10 cm was cut from the separator for the power storage device after removing the coating film. The volume of the sample (cm 3 ) and mass (g), and then calculate the density (g / cm 3 ) and the porosity was calculated using the following formula: The density of the mixed composition was determined by calculation using the density of each of the raw materials used and the mixing ratio. Porosity (%) = (volume-mass / density of mixed composition) / volume x 100
[0355] <Piercing strength (gf) and area weight conversion piercing strength (gf / (g / m 2 ))〉 Using a handy compression tester "KES-G5 (trademark)" manufactured by Kato Tech, the separator for the power storage device from which the coating film had been removed was fixed with a sample holder with an opening diameter of 11.3 mm. Next, a puncture test was performed on the center of the fixed separator for the power storage device in an atmosphere at a temperature of 23°C and a humidity of 40% with a needle tip curvature radius of 0.5 mm and a puncture speed of 2 mm / sec, to obtain the raw puncture strength (gf) as the maximum puncture load. The value (gf / (g / m2)) obtained by converting the puncture strength (gf) into basis weight (in the table, puncture strength converted into basis weight) was also calculated.
[0356] <Weight (g / m 2 )〉 A 10 cm x 10 cm square sample was cut from the separator for the power storage device from which the thermoplastic polymer layer had been removed, and the weights of the polyolefin substrate layer and the inorganic coating layer were measured using an electronic balance AEL-200 manufactured by Shimadzu Corporation. The weights obtained were multiplied by 100 to obtain the weight of 1 m 2 Weight of polyolefin base layer and inorganic coating layer per unit area (g / m 2Next, a 10 cm x 10 cm square sample was cut from the separator for the power storage device from which the coating layers (the inorganic coating layer and the thermoplastic polymer layer) had been removed, and the mass was measured using an electronic balance AEL-200 manufactured by Shimadzu Corporation. The mass thus obtained was multiplied by 100 to obtain the mass of 1 m 2 Weight of polyolefin base layer per unit area (g / m 2 ) (in the table, the basis weight of the base layer) was calculated. 2 Weight of polyolefin base layer and inorganic coating layer per unit area (g / m 2 ) to 1m 2 Weight of polyolefin base layer per unit area (g / m 2 ) to get 1m 2 The weight of the inorganic coating layer per unit area (the amount of inorganic coating layer supported on the polyolefin base layer, g / m 2 ) was calculated.
[0357] <Powder shedding (%)> A 10 cm x 10 cm square sample was cut from the separator for power storage devices, and the mass (g) was measured. One side was attached to cardboard and fixed, and then a 5 cm diameter, 900 g weight covered with cotton cloth was placed on the inorganic particle layer side, and these were rubbed together at a rotation speed of 50 rpm for 10 minutes. The mass (g) was then accurately measured again, and the powder shedding property was measured using the following formula. Powder shedding rate (mass%) = {(mass before rubbing (g) - mass after rubbing (g)) / mass before rubbing} x 100
[0358] <Capacity Retention Rate (%) of Battery in Cycle Test in First Embodiment> (1) Preparation of the positive electrode The positive electrode active material was nickel, manganese, and cobalt composite oxide (LiNiMnCoO2) (NMC) (Ni:Mn:Co = 6:2:2 (element ratio), density 3.50 g / cm 3 ) 90.4% by mass, and graphite powder (density 2.26 g / cm3) as a conductive additive 3 , number average particle diameter 6.5 μm) at 1.6 mass%, and acetylene black powder (density 1.95 g / cm 3, number average particle diameter 48 nm) 3.8 mass%, and PVDF (density 1.75 g / cm3) as a resin binder. 3 ) at a ratio of 4.2% by mass, and dispersed in NMP to prepare a slurry. This slurry was applied to one side of an aluminum foil having a thickness of 20 μm, which was to be a positive electrode current collector, using a die coater, and dried at 130° C. for 3 minutes, and then compression molded using a roll press to prepare a positive electrode. At this time, the amount of the positive electrode active material applied was 109 g / m 2 It was.
[0359] (2) Preparation of the negative electrode Graphite powder A (density 2.23 g / cm) was used as the negative electrode active material. 3 , number average particle size 12.7 μm) 87.6 mass%, graphite powder B (density 2.27 g / cm 3 A slurry was prepared by dispersing 9.7% by mass of carboxymethylcellulose (number average particle diameter 6.5 μm), 1.4% by mass (solid content equivalent) of ammonium salt of carboxymethylcellulose as a resin binder (aqueous solution with a solid content concentration of 1.83% by mass), and 1.7% by mass (solid content equivalent) of diene rubber latex (aqueous solution with a solid content concentration of 40% by mass) in purified water. This slurry was applied to one side of a copper foil with a thickness of 12 μm to serve as a negative electrode current collector using a die coater, dried at 120° C. for 3 minutes, and then compression molded using a roll press machine to produce a negative electrode. At this time, the amount of negative electrode active material applied was 52 g / m 2 It was.
[0360] (3) Preparation of non-aqueous electrolyte A nonaqueous electrolyte solution was prepared by adding 0.3 mol / L lithium hexafluorophosphate (LiPF6), 1 mol / L lithium bis(fluorosulfonyl)imide (LiN(SO2F)2), and 20 mass ppm lithium fluorosulfonate (LiFSO3) as electrolytes to a mixed solution of 5 vol% acetonitrile, 62.5 vol% ethyl methyl carbonate, 30 vol% ethylene carbonate, and 2.5 vol% vinylene carbonate.
[0361] (4) Fabrication of a single-layer laminate type non-aqueous secondary battery As described above, the positive electrode and the negative electrode were stacked with a separator (the separator of the embodiment or the separator of the comparative example) between them so that the composite coating surfaces of the electrodes faced each other to form a laminated electrode body. This laminated electrode body was housed in an aluminum laminate sheet exterior body of 100 mm x 60 mm, and vacuum dried at 80 ° C for 5 hours to remove moisture. After the nonaqueous electrolyte was injected into the exterior body, the exterior body was sealed to prepare a single-layer laminate type (pouch type) nonaqueous secondary battery. This single-layer laminate type nonaqueous secondary battery had a design capacity value of 3 Ah and a rated voltage value of 4.2 V.
[0362] (5) Measurement of capacity retention during cycle testing The single-layer laminated non-aqueous secondary battery obtained as described above was subjected to an initial charge treatment and cycle characteristic evaluation according to the following procedure. Charge and discharge were performed using a charge / discharge device ACD-M01A (product name) manufactured by Asuka Electronics Co., Ltd. and a programmable thermostatic chamber IN804 (product name) manufactured by Yamato Scientific Co., Ltd. 1C means a current value at which a fully charged battery is discharged at a constant current and expected to be discharged to completion in one hour. Specifically, in the following procedure, 1C means a current value at which a fully charged battery of 4.2V is discharged at a constant current to 3.0V and expected to be discharged to completion in one hour. First charge process The battery was set at an ambient temperature of 25°C, and charged at a constant current of 0.075A (equivalent to 0.025C) until it reached 3.1V, then charged at a constant voltage of 3.1V for 1.5 hours. After a 3-hour pause, the battery was charged at a constant current of 0.15A (equivalent to 0.05C) until it reached 4.2V, then charged at a constant voltage of 4.2V for 1.5 hours. The battery was then discharged to 3.0V at a constant current of 0.45A (equivalent to 0.15C). · Cycle test of single-layer laminate type non-aqueous secondary battery A cycle test was carried out on the battery that had been subjected to the initial charge / discharge treatment. The cycle test was started 3 hours after the ambient temperature of the battery was set to 25°C. First, the battery was charged at a constant current of 3A equivalent to 1C until it reached 4.2V, and then charged at a constant voltage of 4.2V for a total of 3 hours of charging. The battery was then discharged to 3.0V at a constant current of 3A. This process of charging and discharging once each constitutes one cycle, and 100 cycles of charging and discharging were carried out. The discharge capacity at the 100th cycle, when the discharge capacity at the first cycle was taken as 100%, was calculated as the capacity retention rate after 100 cycles (%).
[0363] <FUSE Temperature and SHORT Temperature (° C.) in the First Embodiment> The positive electrode, the separator for the storage device, and the negative electrode were cut into a circle with a diameter of 200 mm, and overlapped to obtain a laminate. A non-aqueous electrolyte was added to the obtained laminate and allowed to soak into the entire laminate. The laminate was sandwiched in the center between a circular aluminum heater with a diameter of 600 mm, and the aluminum heater was pressurized to 0.5 MPa from above and below with a hydraulic jack. The resistance (Ω) between the electrodes was measured while the laminate was heated with the aluminum heater at a temperature increase rate of 2°C / min. The temperature at which the resistance of the separator exceeded 1000Ω for the first time was taken as the FUSE temperature. Furthermore, the temperature at which the resistance dropped to 1000Ω or less after further heating was taken as the SHORT temperature.
[0364] <Battery Crush Test> The laminated cell after the low-temperature cycle test was set on the sample stage with a 1 mm step between them, and both ends of the cell were held. The cell was crushed with a 15.8 mm diameter stainless steel round bar at a crushing speed of 0.2 mm / s with a force of 1.95 tons, and the crushing test was continued until the voltage reached 4.0 V from 4.1 V, and the time it took for the voltage to reach 4.0 V from 4.1 V was measured. This test was performed on 100 cells, and the number of cells that took 5 seconds or more to reach 4.0 V from 4.1 V was compared.
[0365] <Electrode residual rate (%)> The produced single-layer laminate type nonaqueous secondary battery was disassembled, the separator and electrode were peeled off, the negative electrode was photographed with a digital camera, and the proportion (%) of the negative electrode mixture remaining on the copper foil was calculated.
[0366] <Thermal response index> A sample piece of 100mm TD x 100mm MD taken from a separator for power storage devices was placed in an oven at 150°C for a specified time. The sample piece was sandwiched between multiple papers to prevent hot air from directly hitting the sample piece. Furthermore, a heat label "10R-104" made by IP Giken was sandwiched between the multiple papers so that the temperature reached by the separator could be determined. The heating rate of the separator can be adjusted by adjusting the number of sheets of paper sandwiched. The number of sheets of paper sandwiched was adjusted so that the heating rate of the separator was 2°C / min. The sample piece was removed from the oven and cooled, after which the area of the sample piece was measured and the thermal response index at the indicated temperature of the heat label was calculated using the following formula. Thermal response index (%) = {(10,000(mm 2 )-Area of the sample piece after heating (mm 2 )) / 10,000(mm 2 )}×100 The experiment was repeated while varying the predetermined time from 5 seconds to 3 minutes in 5 second increments, and the thermal response index for each temperature was calculated.
[0367] Quantification of resin aggregates in separators The resin aggregate in the separator is defined as a region having an area of 100 μm or more in length and 100 μm or more in width and through which light does not pass, when the separator obtained through the film-forming process of the Examples and Comparative Examples described below is observed with a transmission optical microscope. 2 The number of resin aggregates per unit area was measured.
[0368] <Cycle test, nail penetration test, hot box test, and high-temperature bar impact fracture test in the second embodiment> (Preparation of batteries for use in safety tests) a. Preparation of the positive electrode Lithium nickel manganese cobalt composite oxide (LiNi) as the positive electrode active material 0.8 Mn 0.1 Co 0.1 A slurry was prepared by dispersing 92.2 mass% of O2, 2.3 mass% each of flake graphite and acetylene black as conductive materials, and 3.2 mass% of polyvinylidene fluoride (PVDF) as a binder in N-methylpyrrolidone (NMP). This slurry was applied to one side of an aluminum foil with a thickness of 20 μm, which serves as a positive electrode current collector, using a die coater, dried at 130 ° C for 3 minutes, and then compression molded using a roll press. At this time, the amount of active material applied to the positive electrode was 250 g / m 2 , the bulk density of the active material is 3.00 g / cm 3 It was adjusted to be.
[0369] b. Preparation of the negative electrode A slurry was prepared by dispersing 96.9% by mass of artificial graphite as the negative electrode active material, and 1.4% by mass of ammonium salt of carboxymethylcellulose and 1.7% by mass of styrene-butadiene copolymer latex as the binder in purified water. This slurry was applied to one side of a 12 μm-thick copper foil as the negative electrode current collector using a die coater, dried at 120° C. for 3 minutes, and then compression molded using a roll press. At this time, the amount of the active material applied to the negative electrode was 106 g / m 2 , the bulk density of the active material is 1.35 g / cm 3 It was adjusted to be.
[0370] c. Preparation of non-aqueous electrolyte The solution was prepared by dissolving LiPF6 as a solute in a mixed solvent of ethylene carbonate:ethyl methyl carbonate = 1:2 (volume ratio) to a concentration of 1.0 mol / L.
[0371] d. Battery assembly The separator was cut into a circle with a diameter of 18 mm, and the positive and negative electrodes were cut into a circle with a diameter of 16 mm. The positive electrode, separator, and negative electrode were stacked in this order so that the active material surfaces of the positive and negative electrodes faced each other, and then stored in a stainless steel metal container with a lid. The container and the lid were insulated, and the container was in contact with the copper foil of the negative electrode, and the lid was in contact with the aluminum foil of the positive electrode. The nonaqueous electrolyte obtained in c. above was poured into this container and sealed. After leaving it at room temperature for one day, the battery was charged at a current value of 3 mA (0.5 C) in an atmosphere of 25°C up to a battery voltage of 4.2 V, and after reaching the voltage, the current value was started to be reduced from 3 mA so as to maintain 4.2 V. In this way, the first charge after the preparation of the battery was performed for a total of 6 hours. Then, the battery was discharged at a current value of 3 mA (0.5 C) down to a battery voltage of 3.0 V.
[0372] (Cycle characteristic evaluation) The obtained battery was charged and discharged 1000 times in an atmosphere of 60°C. The battery was charged at a current value of 6.0mA (1.0C) until the battery voltage reached 4.2V, and then the current value was reduced from 6.0mA to maintain 4.2V, for a total of 3 hours. The battery was discharged at a current value of 6.0mA (1.0C) until the battery voltage reached 3.0V. The capacity retention rate was calculated from the discharge capacity at the 1000th cycle and the discharge capacity at the 1st cycle. A battery with a high capacity retention rate was evaluated as having good cycle characteristics.
[0373] (Nail penetration test) After the 1000 cycles, a test was conducted in which an iron nail was driven into the battery at a speed of 20 mm / sec, penetrating the battery that had been charged to 4.2 V, to cause an internal short circuit. This test can clarify the phenomenon that occurs during an internal short circuit by measuring the time-dependent change in the voltage drop of the battery due to an internal short circuit and the temperature rise on the surface of the battery due to an internal short circuit. In addition, the battery may suddenly heat up due to an insufficient shutdown function of the separator or rupture at low temperatures during an internal short circuit, which may cause the electrolyte to ignite, causing the battery to smoke and / or explode.
[0374] The nail penetration test was performed on 100 batteries with the same separator, and the number of batteries that did not catch fire, emit smoke, or explode was calculated as the pass rate (%).
[0375] (Hot Box Test) The batteries obtained by the above "d. Battery assembly" were stored in a hot box set at a high temperature of 150°C for one hour, and the state of the batteries was observed during and after storage.
[0376] When the polyolefin separator undergoes thermal shrinkage due to storage at high temperatures, an internal short circuit may occur in the positive and negative electrodes of the battery, resulting in ignition or explosion. Batteries in which ignition or explosion was observed were evaluated as failing the test. Batteries in which ignition or explosion was not observed were evaluated as passing the test.
[0377] This hot box test was carried out on 100 batteries using the same separator, and the pass rate (%) was calculated.
[0378] (High temperature bar impact destruction test) FIG. 12 is a schematic diagram of a high-temperature bar impact fracture test (shock test). In the impact test, a round bar (φ=15.8 mm) is placed on top of a sample placed on a test bench so that the sample and the round bar are roughly perpendicular to each other, and a 18.2 kg weight is dropped onto the top of the round bar from a position 61 cm above the bar to observe the effect of the impact on the sample. The procedure of the impact test in the examples and comparative examples will be described below with reference to FIG. The cylindrical batteries assembled as described above in "d. Battery assembly" and selected for evaluation were charged at a constant current and constant voltage (CCCV) for 3 hours under conditions of a current value of 3000 mA (1.0 C) and a final battery voltage of 4.2 V. Next, in an environment of 150°C, the cylindrical battery was placed horizontally on a flat surface, and a stainless steel round bar with a diameter of 15.8 mm was placed across the center of the battery. The round bar was placed so that its long axis was parallel to the MD of the separator. A weight of 18.2 kg was dropped from a height of 61 cm onto the battery so that the impact was perpendicular to the longitudinal axis of the battery from the round bar placed in the center of the battery. After the impact, the condition of the battery was observed, and the surface temperature of the battery was measured as necessary. The battery was evaluated as failing if ignition or explosion was observed in the battery, and passing if no ignition or explosion was observed in the battery.
[0379] This high-temperature bar impact destruction test was carried out on 100 batteries using the same separator, and the pass rate (%) was calculated.
[0380] <Fuse / Meltdown (F / MD) Characteristics in the Second Embodiment> The positive electrode, separator, and negative electrode are cut into a circular shape with a diameter of 200 mm, overlapped, and an electrolyte-containing electrolyte solution is added to the resulting laminate and spread throughout. The laminate is sandwiched in the center between a circular aluminum heater with a diameter of 600 mm, and the aluminum heater is pressurized to 0.5 MPa from above and below with a hydraulic jack, completing preparation for measurement. The resistance (Ω) between the electrodes is measured while heating the laminate with the aluminum heater at a temperature increase rate of 2°C / min. The temperature at which the resistance between the electrodes increases together with the separator fuse and the resistance exceeds 1000Ω for the first time is the fuse temperature (shutdown temperature). Furthermore, the temperature at which the resistance falls to 1000Ω or less after further heating is the meltdown temperature (film rupture temperature). Note that a wire for measuring resistance was attached to the back of the aluminum foil of the positive electrode prepared in the above-mentioned "Cycle test in the second embodiment" item "a. Preparation of positive electrode" with a conductive silver paste. A wire for measuring resistance was attached to the back of the copper foil of the negative electrode prepared in the above-mentioned "b. Preparation of negative electrode" in the "Cycle test in the second embodiment" with a conductive silver paste. Furthermore, the electrolyte-containing electrolyte prepared in the above-mentioned "c. Preparation of non-aqueous electrolyte" in the "Cycle test in the second embodiment" was also used for the F / MD characteristic test.
[0381] I. Examples and Comparative Examples of the First Embodiment
[0382] <<Production of separator for power storage device>> <Production of Silane-Grafted Polyolefin> Polyethylene with a viscosity average molecular weight (Mv) of 120,000 was used as the raw polyethylene for silane-modified polyethylene (resin a). While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) was added to generate radicals in the α-olefin polymer chain. Then, trimethoxyalkoxide-substituted vinylsilane was poured into the molten mixture to cause an addition reaction. By the addition reaction, an alkoxysilyl group was introduced into the α-olefin polymer to form a silane graft structure. At the same time, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl) propionate]) was added to adjust the radical concentration in the system, suppressing the chain reaction (gelation) in the α-olefin. The obtained silane-modified polyethylene molten resin was cooled in water and pelletized. The pellets were heated and dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinylsilane. The concentration of unreacted trimethoxyalkoxide-substituted vinylsilane remaining in the pellets was 3000 ppm or less.
[0383] <Preparation of base layer (layer A)> As the resin material for layer A, 30% by mass of the silane-modified polyethylene (resin a) obtained above, 30% by mass of ultra-high molecular weight polyethylene (resin b) which is a homopolymer having a viscosity average molecular weight of 4,500,000, and 40% by mass of ultra-high molecular weight polyethylene (resin c) which is a homopolymer having a viscosity average molecular weight of 700,000 were used. Furthermore, based on the total mass of the resin material, 1000 ppm by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant and 3000 ppm by mass of calcium stearate relative to the mass of ultra-high molecular weight polyethylene (resin b) were added, and the mixture was dry-blended using a tumbler blender to obtain a raw material mixture for layer A.
[0384] The obtained raw material mixture for layer A was fed to separate twin-screw extruders under a nitrogen atmosphere by feeders, and was mixed with liquid paraffin (kinematic viscosity at 37.78°C: 7.59 × 10 -5 m 2 / s) was injected into each extruder cylinder by a plunger pump. The raw material mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin was 70 mass% based on the total mass of the molten mixture to be extruded. The melt-kneading conditions were a set temperature of 230°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. The molten mixture was extruded through a T-die and extruded and cast onto a cooling roll whose surface temperature was controlled at 25°C, to obtain a gel sheet (sheet-shaped molded product) with a thickness of 1370 μm.
[0385] The gel sheet was introduced into a simultaneous biaxial tenter stretching machine, and biaxial stretching was performed to obtain a stretched product. The set stretching conditions were MD magnification 7.0 times, TD magnification 6.4 times (i.e., 7 x 6.3 times), and biaxial stretching temperature 122 ° C. The gel sheet after stretching was introduced into a dichloromethane tank and thoroughly immersed in dichloromethane to extract and remove liquid paraffin, and then the dichloromethane was dried and removed to obtain a porous sheet. The porous sheet was introduced into a TD tenter, and heat set (HS) was performed at a heat setting temperature of 133 ° C. and a stretching ratio of 1.9 times, and a relaxation operation was performed to TD 1.75 times to obtain a microporous membrane base material. The end of the microporous membrane base material was cut and wound up as a mother roll with a width of 1,100 mm and a length of 5,000 m. The obtained microporous membrane base material had a thickness of 10 μm.
[0386] <Formation of inorganic particle layer (layer B)> The acrylic latex used as the resin binder of the inorganic particle layer was produced by the following method. 70.4 parts by mass of ion-exchanged water, 0.5 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 0.5 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation) were added as emulsifiers to a reaction vessel equipped with a stirrer, a reflux condenser, a dripping tank, and a thermometer. Next, the temperature inside the reaction vessel was raised to 80°C, and 7.5 parts by mass of a 2% aqueous solution of ammonium persulfate was added while maintaining the temperature at 80°C to obtain an initial mixture. Five minutes after the addition of the aqueous solution of ammonium persulfate was completed, the emulsion was dripped from the dripping tank into the reaction vessel over 150 minutes. The above emulsion was prepared by mixing 70 parts by mass of butyl acrylate, 29 parts by mass of methyl methacrylate, 1 part by mass of methacrylic acid, 3 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.) and 3 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation) as emulsifiers, 7.5 parts by mass of 2% aqueous solution of ammonium persulfate, and 52 parts by mass of ion-exchanged water with a homomixer for 5 minutes. After the dropwise addition of the emulsion was completed, the temperature inside the reaction vessel was maintained at 80°C for 90 minutes, and then cooled to room temperature. The obtained emulsion was adjusted to pH=8.0 with a 25% aqueous solution of ammonium hydroxide, and a small amount of water was added to obtain an acrylic latex with a solid content of 40%. The obtained acrylic latex had a number average particle diameter of 145 nm and a glass transition temperature of -23°C.
[0387] 95 parts by mass of aluminum hydroxide oxide (boehmite, average particle size 1.4 μm) as inorganic particles and 0.4 parts by mass (solid content equivalent) of an aqueous solution of ammonium polycarboxylate (SN Dispersant 5468, manufactured by San Nopco, solid content concentration 40%) as an ionic dispersant were uniformly dispersed in 100 parts by mass of water to prepare a dispersion. The obtained dispersion was crushed with a bead mill (cell volume 200 cc, zirconia bead diameter 0.1 mm, filling amount 80%) to adjust the particle size distribution of the inorganic particles to D50 = 1.0 μm, and an inorganic particle-containing slurry was prepared. 2.0 parts by mass (solid content equivalent) of the acrylic latex produced above as a resin binder was added to the dispersion with the particle size distribution adjusted to obtain an inorganic particle-containing slurry. The substrate was continuously unwound from the mother roll of the microporous membrane substrate, and the inorganic particle-containing slurry was applied to both sides of the substrate with a gravure reverse coater. The coated substrate was dried in a dryer at 60°C to remove water, and a substrate having inorganic particle layers on both sides was obtained. This was wound up to obtain a mother roll of the substrate having inorganic particle layers. The aluminum hydroxide oxide contained in the inorganic particle layer was 95 mass%, and the film thickness of the inorganic particle layer was 5 μm in total on both sides (approximately 2.5 μm on one side).
[0388] <Formation of thermoplastic polymer layer (layer C)> An acrylic resin coating liquid was prepared as follows: 70.4 parts by mass of ion-exchanged water, 0.5 parts by mass of "Aqualon KH1025" (registered trademark, 25% aqueous solution manufactured by Daiichi Kogyo Seiyaku Co., Ltd.), and 0.5 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, 25% aqueous solution manufactured by ADEKA Corporation) were charged into a reaction vessel equipped with a stirrer, reflux condenser, dropping tank, and thermometer. The temperature inside the reaction vessel was raised to 80°C, and 7.5 parts by mass of ammonium persulfate (2% aqueous solution) was added while maintaining the temperature at 80°C. Five minutes after the addition of the ammonium persulfate aqueous solution, a mixture of 15.9 parts by mass of methyl methacrylate, 74.5 parts by mass of n-butyl acrylate, 2 parts by mass of 2-ethylhexyl acrylate, 0.1 parts by mass of methacrylic acid, 0.1 parts by mass of acrylic acid, 2 parts by mass of 2-hydroxyethyl methacrylate, 5 parts by mass of acrylamide, 0.4 parts by mass of glycidyl methacrylate, 0.4 parts by mass of trimethylolpropane triacrylate (A-TMPT, manufactured by Shin-Nakamura Chemical Co., Ltd.), 3 parts by mass of "Aqualon KH1025" (registered trademark, manufactured by Daiichi Kogyo Seiyaku Co., Ltd., 25% aqueous solution), 3 parts by mass of "ADEKA REASOAP SR1025" (registered trademark, manufactured by ADEKA Corporation, 25% aqueous solution), 0.05 parts by mass of sodium p-styrenesulfonate, 7.5 parts by mass of ammonium persulfate (2% aqueous solution), 0.3 parts by mass of γ-methacryloxypropyltrimethoxysilane, and 52 parts by mass of ion-exchanged water was mixed for 5 minutes using a homomixer to prepare an emulsion. The obtained emulsion was dripped from the drip tank into the reaction vessel over 150 minutes. After the emulsion was dripped, the temperature inside the reaction vessel was kept at 80°C for 90 minutes, and then cooled to room temperature. The obtained emulsion was adjusted to pH=9.0 with an aqueous ammonium hydroxide solution (25% aqueous solution) to obtain an acrylic resin (acrylic copolymer latex) with a concentration of 40%. This was diluted with ion-exchanged water to a solid content of 5% by weight to prepare a coating liquid.
[0389] A coating solution of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) was prepared as follows: PVDF-HFP copolymer emulsion (Kynarflex 2501-20, Tg: -40°C) manufactured by Arkema was diluted with ion-exchanged water to a solid content of 5% by weight to prepare a coating solution.
[0390] The acrylic resin or PVDF-HFP coating solution prepared above was applied to both sides of a mother roll of a substrate having an inorganic particle layer using a gravure coater to form a thermoplastic polymer layer with the thickness and coverage area ratio shown in Tables 8 to 14, and slit as necessary to obtain a separator for an electricity storage device.
[0391] Examples 1 to 68 As shown in Tables 8 to 14, separators for electricity storage devices were produced by the above method while changing the lamination method, materials, film thickness, etc. of Layers A to C. The evaluation results are shown in Tables 8 to 14.
[0392] In Example 66, instead of the positive electrode prepared in the above "a. Preparation of positive electrode", a positive electrode containing a LiCoO2 layer (LCO positive electrode) was used as a positive electrode material. In Example 67, when forming the inorganic particle layer in the above "Formation of inorganic particle layer (B layer)", "Epocross K-2010E" (registered trademark, Nippon Shokubai Co., Ltd., glass transition temperature -50°C) was used as a resin binder instead of acrylic latex when forming the inorganic particle layer in the above "Formation of inorganic particle layer (B layer)". In Example 68, when forming the inorganic particle layer in the above "Formation of inorganic particle layer (B layer)", "JE-1056" (registered trademark, Seiko PMC Co., Ltd., glass transition temperature 82°C) was used as a resin binder instead of acrylic latex when forming the inorganic particle layer.
[0393] Comparative Examples 1 to 6 As shown in Table 15, separators for electricity storage devices were manufactured by changing the lamination method, materials, film thickness, etc. of Layers A to C. Table 15 shows the evaluation results.
[0394] In Comparative Example 4, the obtained polyolefin microporous membrane was used and, prior to battery assembly, was irradiated with 120 kGy of electron beams for electron beam crosslinking using an EB irradiation device, i-Compact EB (trademark), manufactured by Iwasaki Electric Co., Ltd. The obtained electron beam crosslinked microporous membrane and battery were subjected to various evaluations according to the above-mentioned evaluation methods.
[0395] In Comparative Examples 5 and 6, in the preparation of the polyolefin microporous membrane, a catalyst for forming a tin-based siloxane bond was added to the extrusion material during the extrusion process, and crosslinking was performed by humidification after separator molding and in the liquid paraffin extraction process, respectively.
[0396] [Table 8]
[0397] [Table 9]
[0398] [Table 10]
[0399] [Table 11]
[0400] [Table 12]
[0401] [Table 13]
[0402] [Table 14]
[0403] [Table 15]
[0404] II. Examples and Comparative Examples of the Second Embodiment
[0405] <Production method of silane-grafted modified polyolefin> The raw polyolefin used for the silane graft modified polyolefin may have a viscosity average molecular weight (Mv) of 100,000 or more and 1,000,000 or less, a weight average molecular weight (Mw) of 30,000 or more and 920,000 or less, and a number average molecular weight of 10,000 or more and 150,000 or less, and may be a propylene or butene copolymerized α-olefin. While melt-kneading the raw polyethylene in an extruder, an organic peroxide (di-t-butyl peroxide) is added to generate radicals in the α-olefin polymer chain, and then trimethoxyalkoxide-substituted vinylsilane is injected to introduce alkoxysilyl groups into the α-olefin polymer by an addition reaction, forming a silane graft structure. At the same time, an appropriate amount of an antioxidant (pentaerythritol tetrakis [3-(3,5-di-t-butyl-4-hydroxyphenyl) propionate]) is added to adjust the radical concentration in the system, suppressing the chain reaction (gelation) in the α-olefin. The obtained silane-grafted polyolefin molten resin is cooled in water and pelletized, and then heated and dried at 80°C for 2 days to remove moisture and unreacted trimethoxyalkoxide-substituted vinylsilane. The residual concentration of unreacted trimethoxyalkoxide-substituted vinylsilane in the pellets is about 1000 to 1500 ppm. The silane-grafted modified polyolefin obtained by the above-mentioned production method is shown in Tables 16 to 23 as "Silane-modified polyethylene."
[0406] <Production method of modified PE and copolymers with various functional groups other than silane-modified PE> Modified PE and copolymers having various functional groups other than silane-modified PE were produced by the following methods. For each raw material, the molecular weight of the raw material used was adjusted so that the MI was within the range of 0.5 to 10. Modified PE with hydroxyl groups was produced by saponifying and neutralizing EVA copolymer. Modified resins such as amine-modified and oxazoline-modified resins were produced by reacting the terminal vinyl groups of PE polymerized using a chromium catalyst with a tungsten-based catalyst under hydrogen peroxide conditions to convert the vinyl groups to epoxy groups. After that, the target reaction site was converted to the desired functional group using a known organic reaction for functional group conversion to obtain various modified PEs. For example, in the case of amine-modified PE, primary or secondary amines were injected as a liquid while the modified PE with epoxy groups was melt-kneaded in an extruder at 200°C, and reacted. After that, unreacted amines were removed from the pressure reducing valve, and the obtained amine-modified resin was extruded into strands and cut into pellets. The modified PE obtained by the above-mentioned production method is shown in Tables 16 to 23 as a type of "Modified PE or copolymer (B)".
[0407] Example 2.1 <Preparation of polyolefin microporous membrane as substrate> A mixture was obtained by dry blending a mixture of 79.2% by mass of homopolymer polyethylene (UHMWPE (A)) with a weight average molecular weight of 720,000, 19.8% by mass of silane-grafted polyethylene (PE (B)) with an MFR of 0.44 g / min obtained by modifying polyolefin with a viscosity average molecular weight of 120,000 with trimethoxyalkoxide-substituted vinylsilane (resin compositions of (A) and (B) are 0.8 and 0.2, respectively), and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, using a tumbler blender. The mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C: 7.59×10 -5 m 2 / s) was pumped into the extruder cylinder by a plunger pump. The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. Next, the molten mixture was extruded through a T-die onto a cooling roll whose surface temperature was controlled to 25° C., to obtain a gel sheet (sheet-shaped molded product) having a film thickness of 1200 μm. Next, the sheet-shaped molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD magnification of 7.0 times, TD magnification of 7.0 times (i.e., 7.0 x 7.0 times), and the biaxial stretching temperature was 125°C. Next, the stretched gel sheet was introduced into a dichloromethane tank and thoroughly immersed in dichloromethane to extract and remove the liquid paraffin, and then the dichloromethane was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter for heat setting (HS), where HS was performed at a heat setting temperature of 123° C. and a stretch ratio of 2.0 times, and then a relaxation operation was performed to a stretch ratio of 1.8 times in the TD direction.
[0408] <Arrangement of Thermoplastic Polymer-Containing Layer> A coating solution was prepared by uniformly dispersing 7.5 parts by mass of a coating resin having the type and glass transition temperature shown in Table 16 in 92.5 parts by mass of water, and this coating solution was applied to one side of a polyolefin microporous membrane using a gravure coater to form a thermoplastic polymer-containing layer with the film thickness and coating area ratio shown in Table 16, thereby obtaining a composite separator.
[0409] Thereafter, the ends of the composite separator were cut off and wound up into a mother roll having a width of 1,100 mm and a length of 5,000 m. In the above evaluation, the composite separator unwound from the mother roll was slit as necessary and used as the evaluation separator. The separator and battery for evaluation were subjected to various evaluations according to the above-mentioned evaluation methods, and the evaluation results are shown in Table 16.
[0410] Examples 2.2 to 2.26 and Comparative Examples 2.1 to 2.5 As shown in Tables 16 to 23, separators and batteries shown in Tables 16 to 23 were obtained by the same operations as in Example 2.1, except that the conditions of the microporous membrane as a substrate, the composite configuration conditions, the presence or absence of crosslinking during preparation of the microporous membrane, and the presence or absence of crosslinking after assembly of the battery were changed as shown in Tables 16 to 23. Various evaluations were performed on the obtained separators and batteries according to the above-mentioned evaluation methods, and the evaluation results are also shown in Tables 16 to 23.
[0411] In Example 2.17, a positive electrode including a Li(Al,Co)O2 layer (LAC positive electrode) was used as the positive electrode material instead of the positive electrode prepared in the above "a. Preparation of positive electrode".
[0412] In Example 2.18, a nonaqueous electrolyte solution was used that had the same components as the nonaqueous electrolyte solution prepared in "c. Preparation of nonaqueous electrolyte solution" above, and that had LiPF6 adjusted to a concentration of 5.0 mol / L.
[0413] In Comparative Examples 2.1 and 2.2, the obtained polyolefin microporous membrane was irradiated with a predetermined dose of radiation before assembling a battery to perform electron beam crosslinking. The obtained electron beam crosslinked microporous membrane and battery were subjected to various evaluations according to the above-mentioned evaluation methods.
[0414] In addition, in Comparative Examples 2.4 and 2.5, in the production of polyolefin microporous membranes, a catalyst for forming a tin-based siloxane bond was added to the extrusion material during the extrusion process, and crosslinking was performed by humidification after separator molding and in the liquid paraffin extraction process, respectively.
[0415] [Table 16]
[0416] [Table 17]
[0417] [Table 18]
[0418] [Table 19]
[0419] [Table 20]
[0420] [Table 21]
[0421] [Table 22]
[0422] [Table 23]
[0423] Example 3.1 <Preparation of polyolefin microporous membrane as substrate> A mixture was obtained by dry blending 79.2% by mass of homopolymer polyethylene (UHMWPE (A)) with a weight average molecular weight of 730,000, 19.8% by mass of silane-grafted polyethylene (PE (B)) with an MFR of 0.40 g / min obtained by modifying polyolefin with a viscosity average molecular weight of 121,000 with trimethoxyalkoxide-substituted vinylsilane (resin compositions of (A) and (B) are 0.8 and 0.2, respectively), and 1% by mass of pentaerythrityl-tetrakis-[3-(3,5-di-t-butyl-4-hydroxyphenyl)propionate] as an antioxidant, using a tumbler blender. The mixture was fed to a twin-screw extruder by a feeder under a nitrogen atmosphere. Liquid paraffin (dynamic viscosity at 37.78°C: 7.59×10 -5 m2 / s) was pumped into the extruder cylinder by a plunger pump. The mixture and liquid paraffin were melt-kneaded in the extruder, and the feeder and pump were adjusted so that the liquid paraffin content in the extruded polyolefin composition was 70% by mass (i.e., the polymer concentration was 30% by mass). The melt-kneading conditions were a set temperature of 220°C, a screw rotation speed of 240 rpm, and a discharge rate of 18 kg / h. Next, the molten mixture was extruded through a T-die onto a cooling roll whose surface temperature was controlled to 25° C., to obtain a gel sheet (sheet-shaped molded product) having a film thickness of 1250 μm. Next, the sheet-shaped molded product was introduced into a simultaneous biaxial tenter stretching machine and biaxially stretched to obtain a stretched product. The stretching conditions were set to MD magnification of 7.0 times, TD magnification of 7.0 times (i.e., 7×7 times), and biaxial stretching temperature of 127° C. Next, the stretched gel sheet was introduced into a dichloromethane tank and thoroughly immersed in dichloromethane to extract and remove the liquid paraffin, and then the dichloromethane was dried and removed to obtain a porous body. Next, the porous body was introduced into a TD tenter for...
Claims
1. An electricity storage device having a separator for an electricity storage device, the separator comprising a polyolefin microporous membrane as a substrate and a surface layer formed on at least one surface of the polyolefin microporous membrane, the surface layer is a thermoplastic polymer-containing layer, an active layer containing a fluorine atom-containing vinyl compound, or a heat-resistant porous layer containing a heat-resistant resin; The polyolefin contained in the polyolefin microporous membrane has one or more functional groups, and The separator for an electricity storage device is characterized in that, after being housed in the electricity storage device, (1) the functional groups undergo a condensation reaction with each other, (2) the functional groups react with chemical substances inside the electricity storage device, or (3) the functional groups react with other types of functional groups to form a cross-linked structure.
2. 2. The electricity storage device according to claim 1, wherein the functional group is at least one selected from the group consisting of a carboxyl group, a hydroxyl group, a carbonyl group, a polymerizable unsaturated hydrocarbon group, an isocyanate group, an epoxy group, a silanol group, a hydrazide group, a carbodiimide group, an oxazoline group, an acetoacetyl group, an aziridine group, an ester group, an active ester group, a carbonate group, an azide group, a linear or cyclic heteroatom-containing hydrocarbon group, an amino group, a sulfhydryl group, a metal chelate group, and a halogen-containing group.
3. 3. The electricity storage device according to claim 1, wherein the surface layer is a thermoplastic polymer-containing layer, and the coverage area ratio of the thermoplastic polymer-containing layer to the substrate is 5% to 90%.
4. The electricity storage device according to claim 3 , wherein the thermoplastic polymer contained in the thermoplastic polymer-containing layer contains polymerized units of a (meth)acrylic acid ester or (meth)acrylic acid.
5. The electricity storage device according to claim 3 or 4, wherein the thermoplastic polymer contained in the thermoplastic polymer-containing layer has a glass transition temperature of -40°C to 105°C.
6. 3. The power storage device according to claim 1, wherein the surface layer is an active layer, and the active layer contains at least one fluorine atom-containing vinyl compound selected from the group consisting of polyvinylidene fluoride-hexafluoropropylene (PVDF-HFP) and polyvinylidene fluoride-chlorotrifluoroethylene (PVDF-CTFE), and inorganic particles.
7. The electricity storage device according to claim 6, wherein a mass ratio of the fluorine atom-containing vinyl compound to the inorganic particles in the active layer (fluorine atom-containing vinyl compound / inorganic particles) is 5 / 95 to 80 / 20.
8. The weight average molecular weight of the fluorine atom-containing vinyl compound is 0.6×10 6 ~2.5 x 10 6 The electricity storage device according to claim 6 or 7,
9. The power storage device according to claim 1 or 2, wherein the surface layer is a heat-resistant porous layer containing a heat-resistant resin, and the heat-resistant porous layer contains 30% by mass to 90% by mass of an inorganic filler having an average particle diameter of 0.2 μm to 0.9 μm.
10. The electricity storage device according to claim 9 , wherein the heat-resistant resin comprises at least one selected from the group consisting of wholly aromatic polyamide, polyimide, polyamideimide, polysulfone, polyketone, polyether, polyetherketone, polyetherimide, and cellulose.
11. The electricity storage device according to claim 9 or 10, wherein the heat-resistant resin contains a para-type aromatic polyamide and / or a meta-type aromatic polyamide.
12. The electricity storage device according to claim 1 , wherein the chemical substance is any one of an electrolyte, an electrolytic solution, an electrode active material, an additive, or a decomposition product thereof contained in the polyolefin microporous membrane.
13. The electricity storage device according to any one of claims 1 to 12, wherein the crosslinked structure is an amorphous part crosslinked structure in which an amorphous part of the polyolefin is crosslinked.
14. The electricity storage device according to claim 13 , wherein the amorphous portion is selectively crosslinked.
15. The power storage device according to any one of claims 1 to 14, wherein the polyolefin is a functional group-modified polyolefin or a polyolefin copolymerized with a monomer having a functional group.
16. The electricity storage device according to any one of claims 1 to 15, wherein the crosslinked structure is formed by a reaction via any one of a covalent bond, a hydrogen bond, or a coordinate bond.
17. The reaction via the covalent bond is represented by the following reactions (I) to (IV): (I) Condensation reactions of multiple identical functional groups; (II) Reactions between multiple different functional groups; (III) a chain condensation reaction between the functional group and the electrolyte; and (IV) reaction of a functional group with an additive; The power storage device according to claim 16, which is at least one selected from the group consisting of:
18. The reaction via a coordinate bond is the following reaction (V): (V) A reaction in which a plurality of identical functional groups crosslink through coordinate bonds with metal ions; The power storage device according to claim 17 .
19. 20. The electrical storage device according to claim 18, wherein the reactions (I) and / or (II) are catalytically promoted by chemicals within the electrical storage device.
20. The electricity storage device according to claim 19 , wherein the reaction (I) is a condensation reaction of a plurality of silanol groups.
21. The reaction (IV) is a nucleophilic substitution reaction, a nucleophilic addition reaction, or a ring-opening reaction between a compound Rx constituting the electricity storage device separator and a compound Ry constituting the additive, the compound Rx having a functional group x, and the compound Ry having a linking reaction unit y 1 The power storage device according to claim 17 .
22. The reaction (IV) is a nucleophilic substitution reaction, The functional group x of the compound Rx is -OH, -NH 2 At least one selected from the group consisting of -NH-, -COOH and -SH; The linking reaction unit y of the compound Ry 1 But, CH 3 SO 2 -, CF 3 SO 2 -, ArSO 2 -, CH 3 SO 3 -, CF 3 SO 3 -, ArSO 3 - and the following formula (y 1 −1) to (y 1 -6): 【Chemistry 1】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 2】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 3】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 4】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 5】 {In the formula, X is a hydrogen atom or a monovalent substituent.} 【Chemistry 6】 {In the formula, X is a hydrogen atom or a monovalent substituent.} The power storage device according to claim 21 , wherein the at least two are selected from the group consisting of monovalent groups represented by the following formula:
23. The reaction (IV) is a nucleophilic substitution reaction, The compound Ry is the ligation reaction unit y 1 In addition to the chain unit y 2 and The chain unit y 2 is expressed by the following formula (y 2 −1) to (y 2 -6): 【Chemistry 7】 {wherein m is an integer from 0 to 20, and n is an integer from 1 to 20.} 【Chemistry 8】 {wherein n is an integer from 1 to 20.} 【Chemistry 9】 {wherein n is an integer from 1 to 20.} 【Chemistry 10】 {wherein n is an integer from 1 to 20.} 【Chemistry 11】 {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} 【Chemistry 12】 {In the formula, X is an alkylene group or an arylene group having 1 to 20 carbon atoms, and n is an integer of 1 to 20.} The power storage device according to claim 21 or 22, wherein the divalent group is at least one selected from the group consisting of divalent groups represented by the following formula:
24. The reaction (IV) is a nucleophilic addition reaction, The functional group x of the compound Rx is -OH, -NH 2 At least one selected from the group consisting of -NH-, -COOH and -SH; The linking reaction unit y of the compound Ry 1 is expressed by the following formula (Ay 1 -1) to (Ay 1 -6): 【Chemistry 13】 【Chemistry 14】 【Chemistry 15】 【Chemistry 16】 In the formula, R is a hydrogen atom or a monovalent organic group. 【Chemistry 17】 【Chemistry 18】 The power storage device according to claim 21 , wherein the at least one group is selected from the group consisting of groups represented by:
25. The reaction (IV) is a ring-opening reaction, The functional group x of the compound Rx is -OH, -NH 2 At least one selected from the group consisting of -NH-, -COOH and -SH; The linking reaction unit y of the compound Ry 1 is expressed by the following formula (ROy 1 -1): 【Chemistry 19】 In the formula, each of the multiple Xs is independently a hydrogen atom or a monovalent substituent. The power storage device according to claim 21 , wherein the at least two groups are represented by the following formula:
26. In the reaction (V), the metal ion is Zn 2+ , Mn 2+ , Co 3+ , Ni 2+ and Li + The power storage device according to claim 18, which is at least one selected from the group consisting of:
27. The power storage device according to any one of claims 1 to 26, wherein the polyolefin having a functional group is not a masterbatch resin containing a dehydration condensation catalyst that forms a crosslinked structure of the functional group.
28. The positive electrode is at least one selected from the group consisting of a nickel-manganese-cobalt (NMC)-based lithium-containing positive electrode, an olivine-type lithium iron phosphate (LFP)-based positive electrode, a lithium cobalt oxide (LCO)-based positive electrode, a nickel-cobalt-aluminum (NCA)-based lithium-containing positive electrode, and a lithium manganese oxide (LMO)-based positive electrode. The power storage device according to any one of claims 1 to 27.